Carbon-carbon bond formation method

By supporting the platinum group metal catalyst in a non-particle organic porous ion exchanger, the carbon-carbon bond formation reaction is carried out using a fixed bed continuous flow method, the lack of activity and reaction of the platinum group metal catalyst in the prior art in the aqueous solvent is solved. The problem of low efficiency achieves high selectivity and short reaction time.

CN113825735BActive Publication Date: 2025-01-07ORGANO CORP
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202080035833.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-15
Filing Date
2020-04-22
Publication Date
2025-01-07
Estimated Expiration
2040-04-22

AI Technical Summary

Technical Problem

In the existing carbon-carbon bond formation reaction, it is difficult to achieve high selectivity and short reaction time for the high catalytic activity of the platinum group metal catalyst in aqueous solvents, and there are problems of byproducts and low production efficiency.

Method used

The platinum group metal catalyst is supported in a non-particle organic porous ion exchanger with a specific structure, and the reaction is carried out through a fixed bed continuous flow, adjust the contact time and structure of the reaction raw materials and the catalyst, and improve the selectivity and reaction efficiency of the target product .

Benefits of technology

High selectivity and short reaction time of the target product in the carbon-carbon bond formation reaction are achieved, production efficiency is improved, and the generation of by-products is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003352139560000641
    Figure BDA0003352139560000641
  • Figure BDA0003352139560000642
    Figure BDA0003352139560000642
  • Figure BDA0003352139560000643
    Figure BDA0003352139560000643
Patent Text Reader

Abstract

A carbon-carbon bond forming method, wherein a platinum group metal loaded catalyst is filled in a filling container, and a raw material liquid is passed to the platinum group metal loaded catalyst in a continuous flow-through manner, thereby reacting, wherein the platinum group metal loaded catalyst is a platinum group metal loaded catalyst in which nanoparticles of platinum group metals with an average particle size of 1 to 100 nm are loaded in a non-granular organic porous ion exchanger, the non-granular organic porous ion exchanger comprises a continuous skeleton phase and a continuous pore phase, the thickness of the continuous skeleton is 1 to 100 μm, the average diameter of the continuous pores is 1 to 1000 μm, the total pore volume of the non-granular organic porous ion exchanger is 0.5 to 50 ml / g, the ion exchange capacity per unit weight in a dry state is 1 to 6 mg equivalent / g, the ion exchange groups are uniformly distributed in the organic porous ion exchanger, and the loading amount of the platinum group metal in a dry state is 0.004 to 20 wt %. According to the present invention, a carbon-carbon bond forming method for obtaining a desired compound for forming a carbon-carbon bond is provided, and the selectivity of the target product is high. In addition, a method for forming a carbon-carbon bond to obtain a target product can be provided, which has a short reaction time and a high yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carbon-carbon bond forming method, which comprises passing a raw material liquid of a reaction through a platinum group metal catalyst to carry out a reaction for generating a carbon-carbon bond. Background Art

[0002] In recent years, carbon-carbon formation reactions (coupling reactions) using platinum group metals such as palladium as catalysts, represented by the Suzuki-Miyaura coupling reaction, the Sonogashira coupling reaction, and the Mizoroki-Herck coupling reaction, have become increasingly important in the synthesis of high-functional materials such as pharmaceutical intermediates and liquid crystals.

[0003] In the past, the above-mentioned platinum group metal catalysts were mostly used in uniform systems, showing high catalytic activity, but there was a shortcoming that it was difficult to recover the catalyst, and the product was polluted by the metal as the catalyst. Therefore, the above-mentioned catalyst was developed to be loaded on a carrier, so that the recovery of the catalyst becomes easy and the metal pollution of the product is reduced. In recent years, a method for continuously forming a carbon-carbon bond by passing a reaction substrate solution through a non-uniform catalyst has also been developed. For example, Japanese Patent No. 5638862 Gazette reports a method for continuously forming a carbon-carbon bond in a catalyst formed by loading palladium in a porous silica carrier, but actual reaction examples are not disclosed. In addition, although Japanese Patent No. 5255215 and Japanese Patent Application No. 2008-212765 disclose a method of forming a carbon-carbon bond using a catalyst formed by supporting a platinum group metal on the wall surface of a fine flow channel with a width of 1 mm and a depth of 20 μm, the reason is not clear. The disclosed reaction examples do not use water as a solvent. In addition, the reaction is carried out only at a liquid flow rate of 1 μm / minute for the reaction substrate solution, which poses problems in terms of environmental load and production efficiency.

[0004] On the other hand, we have developed a catalyst in which a platinum group metal is supported in a non-granular organic ion exchanger having three-dimensional continuous pores. Japanese Patent Publication No. 2014-15420 or Japanese Patent Publication No. 2016-190853 reports that the catalyst exhibits high catalytic activity in an aqueous solvent in a carbon-carbon bond formation reaction.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 5638862 (claims)

[0008] Patent Document 2: Japanese Patent No. 5255215 (claims)

[0009] Patent Document 3: Japanese Patent Application Publication No. 2008-212765 (claims)

[0010] Patent Document 4: Japanese Patent Application Publication No. 2014-15420

[0011] Patent Document 5: Japanese Patent Application Publication No. 2016-190853 Summary of the invention

[0012] (Problems to be solved by the invention)

[0013] According to the methods disclosed in Patent Documents 4 and 5, a carbon-carbon bond forming reaction can be carried out in a water-based solvent with high yield by using a platinum group metal-supported catalyst in which a platinum group metal is supported on a non-granular organic ion exchanger as a catalyst.

[0014] However, there is a demand for high yields, and on the other hand, in the fields of medicine, pesticides, high-performance materials, etc., the generation of by-products is sometimes undesirable, and in synthetic reactions, selectivity is sometimes more important than yield. Therefore, a reaction method with high selectivity is sometimes required.

[0015] On the other hand, from the perspective of production efficiency, a reaction method with a short reaction time is required. In particular, in the Suzuki-Miyaura reaction, the Sonogashira coupling reaction, and the Mizoroki-Herck coupling reaction, the reactivity varies depending on the reaction raw materials, and sometimes it is difficult to react in a short time. Therefore, a reaction method with a short reaction time is sometimes also required.

[0016] Therefore, an object of the present invention is to provide a method for forming a carbon-carbon bond for obtaining a desired compound by forming a carbon-carbon bond, wherein the method has high selectivity for a target product.

[0017] Another object of the present invention is to provide a method for forming a carbon-carbon bond to obtain a target product by forming a carbon-carbon bond, which method has a short reaction time and a high yield.

[0018] Means for solving problems

[0019] In this actual situation, the present inventors conducted intensive research and found that in the conventional carbon-carbon bond forming reaction in which a platinum group metal such as palladium or platinum functions as a catalyst, a platinum group metal-loaded catalyst in which a platinum group metal is loaded on a non-granular organic porous ion exchanger having a specific structure is filled in a filling container, and a raw liquid of the reaction is introduced into the filling container and passed through the platinum group metal-loaded catalyst to carry out a carbon-carbon bond forming reaction. That is, by carrying out the reaction in a fixed bed continuous flow mode, (1) the selectivity of the target product can be improved, or (2) by selecting the type of ion exchange groups and salt forms of the non-granular organic porous ion exchanger as a carrier, a carbon-carbon bond forming reaction can occur even if the contact time between the reaction raw materials and the platinum group metal-loaded catalyst is short, thereby completing the present invention.

[0020] That is, the present invention (1) provides a carbon-carbon bond forming method, characterized in that (1) an aromatic halide is reacted with an organic boron compound, (2) an aromatic halide is reacted with a compound having an alkynyl group at the terminal, or (3) an aromatic halide is reacted with a compound having an alkenyl group to form a carbon-carbon bond,

[0021] A raw material solution (i) containing an aromatic halide and an organic boron compound, a raw material solution (ii) containing an aromatic halide and a compound having an alkynyl group at the terminal, or a raw material solution (iii) containing an aromatic halide and a compound having an alkenyl group is introduced into the filled container from an introduction path of the filled container filled with a platinum group metal supported catalyst, the raw material solution is passed through the platinum group metal supported catalyst, and the reaction solution is discharged from the discharge path of the filled container, thereby performing a carbon-carbon bond forming reaction.

[0022] The platinum group metal supported catalyst is a platinum group metal supported catalyst in which nanoparticles of platinum group metal with an average particle size of 1 to 100 nm are supported in a non-granular organic porous ion exchanger. The non-granular organic porous ion exchanger comprises a continuous skeleton phase and a continuous pore phase. The thickness of the continuous skeleton is 1 to 100 μm, the average diameter of the continuous pores is 1 to 1000 μm, the total pore volume is 0.5 to 50 ml / g, the ion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, the ion exchange groups are uniformly distributed in the organic porous ion exchanger, and the supported amount of the platinum group metal in a dry state is 0.004 to 20 weight percent.

[0023] In addition, the present invention (2) provides a carbon-carbon bond forming reaction of (1), characterized in that the above-mentioned non-granular organic porous ion exchanger has a continuous bubble structure with common openings (mesopores) with an average diameter of 1 to 1000 μm in the macropores connected to each other and in the walls of the macropores, a total pore volume of 1 to 50 ml / g, an ion exchange capacity per unit weight in a dry state of 1 to 9 mg equivalent / g, and ion exchange groups are uniformly distributed in the organic porous ion exchanger.

[0024] In addition, the present invention (3) provides a carbon-carbon bond forming reaction of (1), characterized in that the above-mentioned non-granular organic porous ion exchanger is: organic polymer particles with an average particle size of 1 to 50 μm are agglomerated to form a three-dimensional continuous skeleton part, and there are three-dimensional continuous pores with an average diameter of 20 to 100 μm between the skeletons, the total pore volume is 1 to 10 ml / g, the ion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, and the ion exchange groups are uniformly distributed in the organic porous ion exchanger.

[0025] In addition, the present invention (4) provides a carbon-carbon bond forming reaction of (1), characterized in that the above-mentioned non-granular organic porous ion exchanger is a bubble-shaped macropore overlapping each other, and the overlapping part forms a continuous macroporous structure with openings with an average diameter of 30 to 300 μm, the total pore volume is 0.5 to 10 ml / g, the ion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, the ion exchange groups are uniformly distributed in the organic porous ion exchanger, and in the SEM image of the cross section of the continuous macroporous structure (dried body), the area of ​​the skeleton part shown in the cross section is 25 to 50% in the image area.

[0026] In addition, the present invention (5) provides a carbon-carbon bond forming reaction of (1), characterized in that the above-mentioned non-granular organic porous ion exchanger is a co-continuous structure of a skeleton and pores, the above-mentioned skeleton is a three-dimensional continuous skeleton with an average thickness of 1 to 60 μm containing an aromatic vinyl polymer, the above-mentioned aromatic vinyl polymer contains 0.1 to 5.0 mol% of cross-linked structural units relative to all structural units introduced with ion exchange groups, the above-mentioned pores are three-dimensional continuous pores with an average diameter of 10 to 200 μm between the skeleton, the total pore volume is 0.5 to 10 ml / g, the ion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, and the ion exchange groups are uniformly distributed in the organic porous ion exchanger.

[0027] In addition, the present invention (6) provides a carbon-carbon bond formation reaction of (1), characterized in that the above-mentioned non-granular organic porous ion exchanger comprises a continuous skeleton phase and a continuous pore phase, the skeleton has a plurality of granular bodies with a diameter of 4 to 40 μm fixed to the surface or a plurality of protrusions with a size of 4 to 40 μm formed on the surface of the skeleton of the organic porous body, the average diameter of the continuous pores is 10 to 200 μm, the total pore volume is 0.5 to 10 ml / g, the ion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, and the ion exchange groups are uniformly distributed in the organic porous ion exchanger.

[0028] In addition, the present invention (7) provides a carbon-carbon bond forming method according to any one of (1) to (6), characterized in that the non-granular organic porous ion exchanger is a non-granular organic porous anion exchanger, and the anion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, and the anion exchange groups are uniformly distributed in the organic porous anion exchanger.

[0029] In addition, the present invention (8) provides the carbon-carbon bond forming method of (7), characterized in that the anion exchange group of the non-granular organic porous anion exchanger is a weakly basic anion exchange group.

[0030] In addition, the present invention (9) provides the carbon-carbon bond forming method of (7), characterized in that the anion exchange group of the non-granular organic porous anion exchanger is a strongly basic anion exchange group, and the counter anion is a halide ion.

[0031] In addition, the present invention (10) provides a carbon-carbon bond forming method according to any one of (1) to (6), characterized in that the non-granular organic porous ion exchanger is a non-granular organic porous cation exchanger having a cation exchange capacity per unit weight in a dry state of 1 to 9 mg equivalent / g, and the cation exchange groups are uniformly distributed in the organic porous cation exchanger.

[0032] Effects of the Invention

[0033] According to the present invention, a method for forming a carbon-carbon bond for obtaining a desired compound by forming a carbon-carbon bond can be provided, wherein the method has high selectivity for a target product.

[0034] Furthermore, according to the present invention, a carbon-carbon bond forming method for forming a carbon-carbon bond to obtain a target product can be provided, which has a short reaction time and a high yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM photograph of the first overall morphological example.

[0036] Figure 2 This is a SEM photograph of the second overall morphology example.

[0037] Figure 3 This is a SEM photograph of the third overall morphology example.

[0038] Figure 4 Is the transfer Figure 3 The SEM photograph obtained by cross-section shows the skeleton part.

[0039] Figure 5 This is a SEM photograph of the fourth overall morphological example.

[0040] Figure 6 It is a schematic diagram of the co-continuous structure of the fourth monolith and the monolith ion exchanger.

[0041] Figure 7 This is a SEM photograph of a morphological example of the overall intermediate (4).

[0042] Figure 8 is a schematic cross-sectional view of a protrusion.

[0043] Fig. 9 This is a SEM photograph of the overall morphology example of No. 5-1.

[0044] Fig.10This is a SEM photograph of the entire intermediate of Reference Example 1.

[0045] Fig.11 This is a SEM photograph of the entire Reference Example 1.

[0046] Fig.12 This is the EPMA analysis result of the whole cation exchanger of Reference Example 1.

[0047] Fig.13 This is the EPMA analysis result of the whole cation exchanger of Reference Example 1.

[0048] Fig.14 These are the EPMA analysis results of the platinum group metal-supported catalyst of Reference Example 2.

[0049] Fig.15 This is a TEM image of the platinum group metal-supported catalyst of Reference Example 2.

[0050] Fig.16 This is the EPMA analysis result of the whole anion exchanger of Reference Example 3.

[0051] Fig.17 This is the EPMA analysis result of the whole anion exchanger of Reference Example 3.

[0052] Fig.18 These are the results of EPMA analysis of the platinum group metal-supported catalyst of Reference Example 4.

[0053] Fig.19 This is a TEM image of the platinum group metal-supported catalyst of Reference Example 4.

[0054] Fig. 20 It is a flow chart of an example of a reaction apparatus for implementing the carbon-carbon bond forming method of the present invention. DETAILED DESCRIPTION

[0055] The carbon-carbon bond forming method of the present invention is a carbon-carbon bond forming method comprising: (1) reacting an aromatic halide with an organic boron compound, (2) reacting an aromatic halide with a compound having an alkynyl group at a terminal, or (3) reacting an aromatic halide with a compound having an alkenyl group to form a carbon-carbon bond.

[0056] A raw material solution (i) containing an aromatic halide and an organic boron compound, a raw material solution (ii) containing an aromatic halide and a compound having an alkynyl group at the terminal, or a raw material solution (iii) containing an aromatic halide and a compound having an alkenyl group is introduced into the filled container from an introduction path of the filled container filled with a platinum group metal supported catalyst, the raw material solution is passed through the platinum group metal supported catalyst, and the reaction solution is discharged from the discharge path of the filled container, thereby performing a carbon-carbon bond forming reaction.

[0057] The platinum group metal supported catalyst is a platinum group metal supported catalyst in which nanoparticles of platinum group metal with an average particle size of 1 to 100 nm are supported in a non-granular organic porous ion exchanger. The non-granular organic porous ion exchanger comprises a continuous skeleton phase and a continuous pore phase. The thickness of the continuous skeleton is 1 to 100 μm, the average diameter of the continuous pores is 1 to 1000 μm, the total pore volume is 0.5 to 50 ml / g, the ion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, the ion exchange groups are uniformly distributed in the organic porous ion exchanger, and the supported amount of the platinum group metal in a dry state is 0.004 to 20 weight percent.

[0058] In the platinum group metal supported catalyst involved in the carbon-carbon bond forming reaction of the present invention, the carrier loaded with the platinum group metal is a non-granular organic porous ion exchanger, and the non-granular organic porous ion exchanger is a monolithic organic porous ion exchanger. The monolithic organic porous body is a porous body whose skeleton is formed by an organic polymer and has a plurality of connected holes between the skeletons to form a flow path of the reaction solution. Then, the monolithic organic porous ion exchanger is a porous body in which ion exchange groups are introduced in a uniformly distributed manner in the skeleton of the monolithic organic porous body. It should be noted that in this specification, the "monolithic organic porous body" is also referred to as "monolithic", the "monolithic organic porous ion exchanger" is also referred to as "monolithic ion exchanger", and in addition, the "monolithic organic porous intermediate" as an intermediate (precursor) in the manufacture of the monolith is also referred to as "monolithic intermediate".

[0059] The integral ion exchanger involved in the platinum group metal loaded catalyst is obtained by integrally introducing ion exchange groups, and its structure is an organic porous body comprising a continuous skeleton phase and a continuous pore phase, the thickness of the continuous skeleton is 1 to 100 μm, the average diameter of the continuous pores is 1 to 1000 μm, and the total pore volume is 0.5 to 50 ml / g.

[0060] The thickness of the continuous skeleton of the integral ion exchanger in the dry state of the platinum group metal supported catalyst is 1 to 100 μm. If the thickness of the continuous skeleton of the integral ion exchanger is less than 1 μm, there is a disadvantage of reduced ion exchange capacity per unit volume, and the mechanical strength is reduced, especially when the liquid is passed at a high flow rate, the integral ion exchanger is greatly deformed, so it is not preferred. In addition, the contact efficiency between the reaction liquid and the integral ion exchanger is reduced, and the catalytic activity is reduced, so it is not preferred. On the other hand, if the thickness of the continuous skeleton of the integral ion exchanger exceeds 100 μm, the skeleton becomes too thick, the diffusion of the substrate takes time, and the catalytic activity is reduced, so it is not preferred. It should be noted that the thickness of the continuous skeleton is determined by SEM observation.

[0061] The average diameter of the continuous pores in the dry state of the integral ion exchanger involving the platinum group metal supported catalyst is 1 to 1000 μm. If the average diameter of the continuous pores of the integral ion exchanger is less than 1 μm, the pressure loss during the liquid flow becomes large, so it is not preferred. On the other hand, if the average diameter of the continuous pores of the integral ion exchanger exceeds 1000 μm, the contact between the reaction liquid and the integral ion exchanger becomes insufficient, and the catalytic activity decreases, so it is not preferred. It should be noted that the average diameter of the continuous pores in the dry state of the integral ion exchanger refers to the maximum value of the pore distribution curve obtained by the mercury penetration method as measured by the mercury penetration method.

[0062] The total pore volume of the whole ion exchanger in the dry state involving the platinum group metal supported catalyst is 0.5 to 50 ml / g. If the total pore volume of the whole ion exchanger is less than 0.5 ml / g, the pressure loss during liquid flow becomes large, so it is not preferred. In addition, the amount of permeate per unit cross-sectional area becomes small, and the processing volume is reduced, so it is not preferred. On the other hand, if the total pore volume of the whole ion exchanger exceeds 50 ml / g, the ion exchange capacity per unit volume is reduced, the loading amount of platinum group metal nanoparticles is also reduced, and the catalytic activity is reduced, so it is not preferred. In addition, the mechanical strength is reduced, especially when the liquid is passed at a high speed, the whole ion exchanger is greatly deformed, and the pressure loss during liquid flow increases sharply, so it is not preferred. In addition, since the contact efficiency between the reaction liquid and the whole ion exchanger is reduced, the reduction in catalytic activity becomes significant. It should be noted that the total pore volume is measured by mercury penetration method.

[0063] Examples of the structure of the above-mentioned monolithic ion exchanger include the continuous bubble structure disclosed in Japanese Patent Application Laid-Open Nos. 2002-306976 and 2009-62512, the co-continuous structure disclosed in Japanese Patent Application Laid-Open No. 2009-67982, the particle agglomerate structure disclosed in Japanese Patent Application Laid-Open No. 2009-7550, and the particle composite structure disclosed in Japanese Patent Application Laid-Open No. 2009-108294.

[0064] The ion exchange capacity per unit weight of the whole ion exchanger in the dry state of the platinum group metal supported catalyst is 1 to 9 mg equivalent / g. If the ion exchange capacity of the whole ion exchanger in the dry state is less than 1 mg equivalent / g, the amount of platinum group metal that can be loaded is reduced, so it is not preferred. On the other hand, if it exceeds 9 mg equivalent / g, the ion exchange group introduction reaction becomes a harsh condition, and the overall oxidative degradation is significantly carried out, so it is not preferred. In the case where the whole ion exchanger is a whole anion exchanger, anion exchange groups are introduced into the whole anion exchanger, and the anion exchange capacity per unit weight in the dry state is 1 to 9 mg equivalent / g, preferably 1 to 8 mg equivalent / g, and particularly preferably 1 to 7 mg equivalent / g. In addition, in the case where the whole ion exchanger is a whole cation exchanger, cation exchange groups are introduced into the whole cation exchanger, and the cation exchange capacity per unit weight in the dry state is 1 to 9 mg equivalent / g, preferably 1 to 7 mg equivalent / g. The ion exchange capacity of a porous body having ion exchange groups introduced only on the surface of the skeleton cannot be determined uniformly depending on the type of the porous body or ion exchange group, but is at most 500 μg equivalent / g.

[0065] In the single ion exchanger to which the platinum group metal supported catalyst is related, the ion exchange groups introduced are not only uniformly distributed on the surface of the whole, but also uniformly distributed inside the whole skeleton. Here, the so-called "uniform distribution of ion exchange groups" refers to that the distribution of ion exchange groups is at least uniformly distributed on the surface and inside the skeleton at the μm level. The distribution of ion exchange groups is simply confirmed by using EPMA. In addition, if the ion exchange groups are not only uniformly distributed on the surface of the whole, but also uniformly distributed inside the whole skeleton, the physical properties and chemical properties of the surface and the inside can be made uniform, so the durability for swelling and shrinkage is improved.

[0066] The ion exchange group introduced into the overall ion exchanger related to the platinum group metal supported catalyst is a cation exchange group or an anion exchange group. As the cation exchange group, carboxylic acid group, iminodiacetic acid group, sulfonic acid group, phosphoric acid group, phosphate ester group etc. can be enumerated. As the anion exchange group, quaternary ammonium groups such as trimethylammonium group, triethylammonium group, tributylammonium group, dimethylhydroxyethylammonium group, dimethylhydroxypropylammonium group, methyldihydroxyethylammonium group, dimethylamino, diethylamino, dipropylamino, dibutylamino, methylhydroxyethylamino, methylhydroxypropylamino and other tertiary amino groups, methylamino, ethylamino, propylamino, butylamino, hydroxyethylamino, hydroxybutylamino and other secondary amino groups, primary amino, tertiary sulfonium group, phosphonium group etc. can be enumerated.

[0067] In the integral ion exchanger involved in the platinum group metal supported catalyst of the present invention, the material constituting the continuous skeleton is an organic polymer material having a cross-linked structure. The cross-linking density of the polymer material is not particularly limited, and it contains 0.1 to 30 mol%, preferably 0.1 to 20 mol% of the cross-linked structural unit relative to all the structural units constituting the polymer material. If the cross-linked structural unit is less than 0.1 mol%, the mechanical strength is insufficient, so it is not preferred. On the other hand, if it exceeds 30 mol%, it is difficult to introduce ion exchange groups, so it is not preferred. The type of the polymer material is not particularly limited, for example, aromatic vinyl polymers such as polystyrene, poly(α-methylstyrene), polyvinyl toluene, polyvinyl benzyl chloride, polyvinyl biphenyl, polyvinyl naphthalene; polyolefins such as polyethylene and polypropylene; poly(halogenated polyolefins) such as polyvinyl chloride and polytetrafluoroethylene; nitrile polymers such as polyacrylonitrile; cross-linked polymers such as (meth) acrylic polymers such as polymethyl methacrylate, polyglycidyl methacrylate, and polyethyl acrylate. The polymer may be a polymer obtained by copolymerizing a single vinyl monomer and a crosslinking agent, a polymer obtained by polymerizing a plurality of vinyl monomers and a crosslinking agent, or a material obtained by blending two or more polymers. Among the above organic polymer materials, crosslinked polymers of aromatic vinyl polymers are preferred from the perspective of ease of forming a continuous structure, ease of introducing ion exchange groups, high mechanical strength, and high stability to acids or alkalis, and styrene-divinylbenzene copolymers and vinylbenzyl chloride-divinylbenzene copolymers are particularly preferred.

[0068] <Examples of the form of monolithic organic porous body and monolithic organic porous ion exchanger>

[0069] Examples of the form of the bulk include the first to fifth bulks shown below. In addition, examples of the bulk ion exchanger include the first to fifth bulk ion exchangers shown below.

[0070] <Description of the first bulk and the first bulk ion exchanger>

[0071] In the platinum group metal supported catalyst of the present invention, the first integral ion exchanger serving as a carrier of platinum group metal particles has a continuous bubble structure having common openings (mesopores) with an average diameter of 1 to 1000 μm in a dry state in the walls of the interconnected macropores and macropores, a total pore volume of 1 to 50 ml / g in a dry state, and an integral ion exchanger having ion exchange groups, the ion exchange groups being uniformly distributed, and an ion exchange capacity per unit weight in a dry state of 1 to 9 mg equivalent / g. In addition, the first integral body is an integral body before the introduction of ion exchange groups, and is an organic porous body having a continuous bubble structure having common openings (mesopores) with an average diameter of 1 to 1000 μm in a dry state in the walls of the interconnected macropores and macropores, and a total pore volume of 1 to 50 ml / g in a dry state.

[0072] The first integral ion exchanger is a continuous macroporous structure in which bubble-shaped macropores overlap each other, and the overlapping portions form a common opening (mesopore) with an average diameter of 1 to 1000 μm, preferably 10 to 200 μm, and particularly preferably 20 to 100 μm in a dry state, and most of the macroporous structure is an open-pore structure. In the open-pore structure, if water is allowed to flow, a flow path is formed in the bubbles formed by the macropores and the mesopores. The number of overlaps between macropores is 1 to 12 in one macropore, and in most cases is 3 to 10. Figure 1 A scanning electron microscope (SEM) photograph showing a morphological example of the first bulk ion exchanger. Figure 1 The first integral ion exchanger shown is a continuous macroporous structure having a plurality of bubble-shaped macropores, which overlap with each other, and the overlapping portions become common openings (mesopores), most of which are open-pore structures. If the average diameter of the mesopores in a dry state is less than 1 μm, the pressure loss during liquid flow becomes significantly larger, so it is not preferred. If the average diameter of the mesopores in a dry state exceeds 1000 μm, the contact between the reaction liquid and the overall ion exchange becomes insufficient, and the catalytic activity decreases, so it is not preferred. By making the structure of the first integral ion exchanger the above-mentioned continuous bubble structure, macropore groups and mesopore groups can be uniformly formed, and compared with the particle agglomeration type porous body recorded in Japanese Patent Publication No. 8-252579, the pore volume and specific surface area can be significantly increased.

[0073] In the present invention, the average diameter of the openings of the first integral body in a dry state and the average diameter of the openings of the first integral ion exchanger in a dry state refer to the maximum value of the pore distribution curve obtained by mercury penetration porosimetry.

[0074] The total pore volume per unit weight of the first integral ion exchanger in a dry state is 1 to 50 ml / g, preferably 2 to 30 ml / g. If the total pore volume is less than 1 ml / g, the pressure loss during liquid flow increases, so it is not preferred. In addition, the amount of permeation per unit cross-sectional area decreases, and the processing capacity decreases, so it is not preferred. On the other hand, if the total pore volume exceeds 50 ml / g, the mechanical strength decreases, especially when the liquid is passed at a high flow rate, the integral ion exchanger is greatly deformed, so it is not preferred. In addition, the contact efficiency between the reaction liquid and the integral ion exchanger and the platinum group metal particles loaded thereon is reduced, so the catalytic effect is also reduced, so it is not preferred. The total pore volume is at most 0.1 to 0.9 ml / g in the previous granular porous ion exchange resin, so a material with a high pore volume and a high specific surface area of ​​1 to 50 ml / g that has not been previously available beyond the above range can be used.

[0075] In the first integral ion exchanger, the material constituting the skeleton is an organic polymer material having a cross-linked structure. The cross-linking density of the polymer material is not particularly limited, and contains 0.3 to 10 mol%, preferably 0.3 to 5 mol% of cross-linked structural units relative to all structural units constituting the polymer material. If the cross-linked structural unit is less than 0.3 mol%, the mechanical strength is insufficient, so it is not preferred. On the other hand, if it exceeds 10 mol%, it is sometimes difficult to introduce the ion exchange group, so it is not preferred.

[0076] The type of organic polymer material constituting the skeleton of the first integral ion exchanger is not particularly limited. For example, aromatic vinyl polymers such as polystyrene, poly(α-methylstyrene), polyvinyltoluene, polyvinylbenzyl chloride, polyvinylbiphenyl, and polyvinylnaphthalene can be cited; polyolefins such as polyethylene and polypropylene; poly(halogenated polyolefins) such as polyvinyl chloride and polytetrafluoroethylene; nitrile polymers such as polyacrylonitrile; and crosslinked polymers such as (meth)acrylic polymers such as polymethyl methacrylate, polyglycidyl methacrylate, and polyethyl acrylate. The above-mentioned organic polymers can be polymers obtained by copolymerizing a single vinyl monomer and a crosslinking agent, or polymers obtained by polymerizing a plurality of vinyl monomers and a crosslinking agent, or can be a material obtained by blending two or more polymers. Among the above-mentioned organic polymer materials, crosslinked polymers of aromatic vinyl polymers are preferred from the perspective of ease of forming a continuous macroporous structure, ease of introducing ion exchange groups, high mechanical strength, and high stability to acid or alkali. In particular, styrene-divinylbenzene copolymers and vinylbenzyl chloride-divinylbenzene copolymers can be cited as preferred materials.

[0077] The ion exchange groups introduced into the first integral ion exchanger are the same in the second to fifth integral ion exchangers. The ion exchange groups are cation exchange groups or anion exchange groups. Examples of cation exchange groups include carboxylic acid groups, iminodiacetic acid groups, sulfonic acid groups, phosphoric acid groups, and phosphate groups. Examples of anion exchange groups include quaternary ammonium groups such as trimethylammonium groups, triethylammonium groups, tributylammonium groups, dimethylhydroxyethylammonium groups, dimethylhydroxypropylammonium groups, and methyldihydroxyethylammonium groups, tertiary sulfonium groups, and phosphonium groups.

[0078] In the first integral ion exchanger (the same applies to the second to fifth integral ion exchangers), the introduced ion exchange groups are uniformly distributed not only on the surface of the porous body but also inside the skeleton of the porous body. The so-called "uniform distribution of ion exchange groups" here means that the distribution of ion exchange groups is uniformly distributed on the surface and inside the skeleton at least at the μm level. The distribution status of ion exchange groups is confirmed by using EPMA. In addition, if the ion exchange groups are uniformly distributed not only on the surface of the whole but also inside the skeleton of the porous body, the physical and chemical properties of the surface and the inside can be made uniform, thereby improving the durability against swelling and shrinkage.

[0079] The ion exchange capacity per unit weight of the first integral ion exchanger in a dry state is 1 to 9 mg equivalent / g. By making the ion exchange capacity per unit weight in a dry state in the above range, the environment around the catalytic active point such as pH inside the catalyst can be changed, thereby increasing the catalytic activity. In the case where the first integral ion exchanger is an integral anion exchanger, an anion exchange group is introduced into the first integral anion exchanger, and the anion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, preferably 1 to 8 mg equivalent / g, and particularly preferably 1 to 7 mg equivalent / g. In addition, in the case where the first integral ion exchanger is an integral cation exchanger, a cation exchange group is introduced into the first integral cation exchanger, and the cation exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, preferably 1 to 7 mg equivalent / g. It should be noted that the ion exchange capacity of the porous body into which the ion exchange group is introduced only on the surface cannot be generalized due to the type of the porous body and the ion exchange group, but is at most 500 μg equivalent / g.

[0080] <First bulk and method for producing first bulk ion exchanger>

[0081] There are no particular restrictions on the method for producing the first whole, and an example of a method for producing the first whole is shown below according to the method described in Japanese Patent Application Laid-Open No. 2002-306976. That is, the first whole is obtained by mixing an oil-soluble monomer that does not contain an ion exchange group, a surfactant, water, and a polymerization initiator as required to obtain an oil-in-water emulsion, and polymerizing it to form a whole. The above-mentioned method for producing the first whole is preferred in terms of easy control of the porous structure of the whole.

[0082] As the oil-soluble monomer not containing ion exchange groups used in the manufacture of the first whole, it refers to a monomer that does not contain any of the ion exchange groups such as carboxylic acid groups and sulfonic acid groups and anion exchange groups such as quaternary ammonium groups, and has low solubility in water and is lipophilic. As specific examples of the above-mentioned monomers, styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, divinylbenzene, ethylene, propylene, isobutylene, butadiene, isoprene, chloroprene, vinyl chloride, vinyl bromide, vinylidene chloride, tetrafluoroethylene, acrylonitrile, methacrylonitrile, vinyl acetate, methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, trimethylolpropane triacrylate, butanediol diacrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, glycidyl methacrylate, ethylene glycol di(methacrylate), etc. can be cited. These monomers can be used alone or in combination of two or more. Among them, in the present invention, cross-linking monomers such as divinylbenzene and ethylene glycol di(methacrylate) are selected as at least one component of the oil-soluble monomers, and their content is 0.3 to 10 mol%, preferably 0.3 to 5 mol%, in all oil-soluble monomers. This is preferred from the perspective of quantitatively introducing ion exchange groups in subsequent steps and ensuring sufficient mechanical strength in practical use.

[0083] The surfactant used in the manufacture of the first whole is not particularly limited as long as it is a surfactant that can form an oil-in-water (W / O) emulsion when an oil-soluble monomer that does not contain an ion exchange group is mixed with water. Nonionic surfactants such as sorbitan monooleate, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan trioleate, polyoxyethylene nonylphenyl ether, polyoxyethylene stearyl ether, polyoxyethylene sorbitan monooleate, etc.; anionic surfactants such as potassium oleate, sodium dodecylbenzenesulfonate, and sodium sulfosuccinate dioctyl ester; cationic surfactants such as distearyl dimethyl ammonium chloride; amphoteric surfactants such as lauryl dimethyl betaine. These surfactants can be used alone or in combination of two or more. It should be noted that the oil-in-water emulsion refers to an emulsion in which the oil phase is a continuous phase and water droplets are dispersed therein. The amount of the surfactant added varies greatly depending on the type of oil-soluble monomer and the size of the target emulsion particles (macropores), so it cannot be generalized, but can be selected in the range of about 2 to 70% relative to the total amount of the oil-soluble monomer and the surfactant. In addition, although not essential, in order to control the overall bubble shape and size, alcohols such as methanol and stearyl alcohol; carboxylic acids such as stearic acid; hydrocarbons such as octane, dodecane, and toluene; and cyclic ethers such as tetrahydrofuran and dioxane may also coexist in the system.

[0084] In addition, in the manufacture of the first whole, when forming a whole by polymerization, the polymerization initiator used as required preferably uses a compound that generates free radicals by heat and light irradiation. The polymerization initiator can be water-soluble or oil-soluble, and for example, azobisisobutyronitrile, azobisdimethylvaleronitrile, azobiscyclohexanenitrile, azobis(cyclohexanecarbonitrile), benzoyl peroxide, potassium persulfate, ammonium persulfate, hydrogen peroxide-ferrous chloride, sodium persulfate-acid sodium sulfite, tetramethylthiuram disulfide, etc. can be cited. Wherein, according to the circumstances, since there is also a system in which a polymerization initiator is not added and only polymerized by heating or only by light irradiation, it is not necessary to add a polymerization initiator in the above-mentioned system.

[0085] In the manufacture of the first overall, as a mixing method for mixing an oil-soluble monomer, a surfactant, water and a polymerization initiator that do not contain an ion exchange group to form an oil-in-water emulsion, there is no particular restriction, and a method of mixing all the components at once can be used; a method of mixing the components after the oil-soluble monomer, the surfactant and the oil-soluble polymerization initiator, i.e., the oil-soluble component, and the water, the water-soluble polymerization initiator, i.e., the water-soluble component are uniformly dissolved respectively. There is no particular restriction on the mixing device used to form the emulsion, and a conventional mixer, a homogenizer, a high-pressure homogenizer, a so-called planetary stirring device that puts the processed object into a mixing container and rotates around the revolution axis while tilting the mixing container, thereby stirring and mixing the processed object, etc., as long as a device suitable for obtaining the target emulsion particle size is selected. In addition, the mixing conditions are not particularly limited, and the stirring speed and stirring time that can obtain the target emulsion particle size can be arbitrarily set. Among these mixing devices, the planetary stirring device can make the water droplets in the W / O emulsion uniformly generated, and its average diameter can be arbitrarily set in a wide range, so it is preferably used.

[0086] In the preparation of the first integral body, the polymerization conditions for polymerizing the oil-in-water emulsion thus obtained can be selected from various conditions according to the type of monomer and the initiator system. For example, when azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, etc. are used as polymerization initiators, the polymerization can be carried out by heating at 30 to 100° C. for 1 to 48 hours in a sealed container under an inert atmosphere. When hydrogen peroxide-ferrous chloride, sodium persulfate-acid sodium sulfite, etc. are used as initiators, the polymerization can be carried out at 0 to 30° C. for 1 to 48 hours in a sealed container under an inert atmosphere. After the polymerization is completed, the contents are taken out and Soxhlet extraction is performed using a solvent such as isopropanol to remove unreacted monomers and residual surfactants to obtain the first integral body.

[0087] There are no particular restrictions on the method for producing the first integral ion exchanger. Among the methods for producing the first integral porous body, the following methods can be cited: a method in which a monomer not containing an ion exchange group is used in place of a monomer not containing an ion exchange group, for example, a monomer containing an ion exchange group such as a carboxylic acid group or a sulfonic acid group is introduced into an oil-soluble monomer not containing the ion exchange group, and then polymerized to form an integral ion exchanger in one step; a method in which a monomer not containing an ion exchange group is polymerized to form the first integral body, and then an ion exchange group is introduced, etc. Among these methods, the method in which a monomer not containing an ion exchange group is polymerized to form the first integral body, and then an ion exchange group is introduced is preferred because it is easy to control the porous structure of the integral ion exchanger and can also quantitatively introduce ion exchange groups.

[0088] There is no particular limitation on the method for introducing ion exchange groups into the first whole, and known methods such as polymer reaction and graft polymerization can be used. For example, as a method for introducing quaternary ammonium groups, there are: if the whole is a styrene-divinylbenzene copolymer, etc., a method of introducing chloromethyl groups by chloromethyl methyl ether or the like, and then reacting with tertiary amines to introduce; a method of preparing the whole by copolymerizing chloromethyl styrene and divinylbenzene, and then reacting with tertiary amines to introduce; a method of introducing free radical initiators and chain transfer groups into the whole, and graft-polymerizing N,N,N-trimethylammonium ethyl acrylate and N,N,N-trimethylammonium propyl acrylamide; a method of introducing quaternary ammonium groups by functional group conversion after graft polymerization of glycidyl methacrylate, etc. Among these methods, as a method for introducing quaternary ammonium groups, a method of introducing chloromethyl groups into styrene-divinylbenzene copolymers by chloromethyl methyl ether or the like, and then reacting with tertiary amines; a method of preparing the whole by copolymerizing chloromethyl styrene and divinylbenzene, and then reacting with tertiary amines is preferred in terms of being able to uniformly and quantitatively introduce ion exchange groups. It should be noted that as the anion exchange group introduced, quaternary ammonium groups such as trimethylammonium, triethylammonium, tributylammonium, dimethylhydroxyethylammonium, dimethylhydroxypropylammonium, and methyldihydroxyethylammonium, tertiary sulfonium, and phosphonium groups can be cited. In addition, for example, as a method for introducing a sulfonic acid group, there can be cited: if the whole is a styrene-divinylbenzene copolymer, etc., a method of sulfonation using chlorosulfonic acid, concentrated sulfuric acid, and fuming sulfuric acid; a method of uniformly introducing free radical initiating groups and chain transfer groups into the surface and inside of the skeleton in the whole, and grafting and polymerizing sodium styrene sulfonate and acrylamide-2-methylpropanesulfonic acid; a method of similarly grafting and polymerizing glycidyl methacrylate, and then introducing a sulfonic acid group by functional group conversion, etc. Among these methods, the method of introducing sulfonic acid in a styrene-divinylbenzene copolymer using chlorosulfonic acid is preferred in terms of being able to uniformly and quantitatively introduce ion exchange groups. Examples of the cation exchange group to be introduced include cation exchange groups such as a carboxylic acid group, an iminodiacetic acid group, a sulfonic acid group, a phosphoric acid group, and a phosphoric acid ester group.

[0089] <Description of the Second Whole Body and the Second Whole Body Ion Exchanger>

[0090] In the platinum group metal supported catalyst of the present invention, the second integral ion exchanger that serves as a support for platinum group metal particles is a particle agglomeration integral body, which is an organic porous body in which organic polymer particles having an average particle diameter of 1 to 50 μm in a dry state are agglomerated to form a three-dimensional continuous skeleton portion, and between the skeletons there are three-dimensional continuous pores having an average diameter of 20 to 100 μm in a dry state, and a total pore volume of 1 to 10 ml / g in a dry state, and is an integral ion exchanger having ion exchange groups, an ion exchange capacity per unit weight in a dry state of 1 to 9 mg equivalent / g, and ion exchange groups are uniformly distributed in the organic porous ion exchanger. In addition, the second integral body is an integral body before the introduction of ion exchange groups, which is a particle agglomeration integral body, which is an organic porous body in which organic polymer particles having an average particle diameter of 1 to 50 μm in a dry state are agglomerated to form a three-dimensional continuous skeleton portion, and between the skeletons there are three-dimensional continuous pores having an average diameter of 20 to 100 μm in a dry state, and a total pore volume of 1 to 10 ml / g in a dry state.

[0091] The basic structure of the second integral ion exchanger is: organic polymer particles having cross-linked structural units with an average particle diameter of 1 to 50 μm, preferably 1 to 30 μm in a dry state, are aggregated to form a three-dimensional continuous skeleton part, and between the skeletons there are three-dimensional continuous pores with an average diameter of 20 to 100 μm, preferably 20 to 90 μm in a dry state, forming a particle aggregation structure, and the three-dimensional continuous pores become flow paths for liquids and gases. Figure 2 This is a SEM photograph showing an example of the second overall ion exchanger. Figure 2 The second integral ion exchanger shown is a particle agglomeration structure in which organic polymer particles are aggregated to form a three-dimensional continuous skeleton portion, and there are three-dimensional continuous pores between the skeletons. If the average particle size of the organic polymer particles is less than 1 μm in a dry state, the average diameter of the continuous pores between the skeletons is less than 20 μm in a dry state, which is not preferred. If it exceeds 50 μm, the contact between the reaction solution and the integral ion exchanger becomes insufficient, and as a result, the catalytic activity is reduced, which is not preferred. In addition, if the average diameter of the three-dimensional continuous pores between the skeletons is less than 20 μm in a dry state, the pressure loss when the reaction solution passes through becomes large, which is not preferred. On the other hand, if it exceeds 100 μm, the contact between the reaction solution and the integral ion exchanger becomes insufficient, and the catalytic activity is reduced, which is not preferred.

[0092] It should be noted that the average particle size of the organic polymer particles constituting the second integral body and the skeleton portion of the second integral ion exchanger in a dry state can be easily measured by using SEM. Specifically, an SEM photograph of an arbitrarily extracted portion of the cross section of the second integral ion exchanger in a dry state is taken, and the diameters of the organic polymer particles of all particles in the SEM photograph are measured, and the average value thereof is taken as the average particle size.

[0093] The average diameter of the three-dimensional continuous pores existing between the skeletons of the second integral body in a dry state or the average diameter of the three-dimensional continuous pores existing between the skeletons of the second integral ion exchanger in a dry state refers to the maximum value of the pore distribution curve obtained by the mercury penetration method.

[0094] The total pore volume per unit weight of the second overall ion exchanger in a dry state is 1 to 10 ml / g. If the total pore volume is less than 1 ml / g, the pressure loss during liquid flow increases, which is not preferred. In addition, the amount of permeation per unit cross-sectional area decreases, and the processing capacity decreases, which is not preferred. On the other hand, if the total pore volume exceeds 10 ml / g, the mechanical strength decreases, and the overall ion exchanger is greatly deformed, especially when liquid is passed at a high flow rate, which is not preferred.

[0095] In the second integral ion exchanger, the material of the skeleton part is an organic polymer material having a cross-linked structural unit. That is, the organic polymer material has a structural unit containing a vinyl monomer and a cross-linking agent structural unit having two or more vinyl groups in the molecule, and the polymer material contains 1 to 5 mol%, preferably 1 to 4 mol% of the cross-linked structural unit relative to all the structural units constituting the polymer material. If the cross-linked structural unit is less than 1 mol%, the mechanical strength is insufficient, so it is not preferred. On the other hand, if it exceeds 5 mol%, the diameter of the pores that exist three-dimensionally continuously between the above-mentioned skeletons becomes smaller, and the pressure loss becomes larger, so it is not preferred.

[0096] The type of polymer material constituting the skeleton of the second integral ion exchanger is not particularly limited, and examples thereof include styrene polymers such as polystyrene, poly(α-methylstyrene), and polyvinylbenzyl chloride; polyolefins such as polyethylene and polypropylene; poly(halogenated polyolefins) such as polyvinyl chloride and polytetrafluoroethylene; nitrile polymers such as polyacrylonitrile; (meth)acrylic polymers such as polymethyl methacrylate, polyglycidyl methacrylate, and polyethyl acrylate; styrene-divinylbenzene copolymers, vinylbenzyl chloride-divinylbenzene copolymers, and the like. The above polymers may be polymers obtained by copolymerizing a single monomer and a crosslinking agent, polymers obtained by polymerizing a plurality of monomers and a crosslinking agent, or materials obtained by blending two or more polymers. Among these organic polymer materials, styrene-divinylbenzene copolymers and vinylbenzyl chloride-divinylbenzene copolymers are preferred materials in terms of ease of forming a particle aggregation structure, ease of introducing ion exchange groups, high mechanical strength, and high stability to acid or alkali.

[0097] The ion exchange groups introduced into the second bulk ion exchanger are the same as the ion exchange groups introduced into the first bulk ion exchanger.

[0098] In the second monolithic ion exchanger, the introduced ion exchange groups are uniformly distributed not only on the surface of the porous body but also inside the framework of the porous body, similarly to the first monolithic ion exchanger.

[0099] The ion exchange capacity of the second integral ion exchanger is 1 to 9 mg equivalents / g per unit weight in a dry state. The second integral ion exchanger can significantly increase the ion exchange capacity per unit weight while suppressing the pressure loss to a low level. By making the ion exchange capacity per unit weight in a dry state within the above range, the environment around the catalytic active point such as pH inside the catalyst can be changed, thereby increasing the catalytic activity. In the case where the second integral ion exchanger is an integral anion exchanger, an anion exchange group is introduced into the second integral anion exchanger, and the anion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalents / g, preferably 1 to 8 mg equivalents / g, and particularly preferably 1 to 7 mg equivalents / g. In addition, in the case where the second integral ion exchanger is an integral cation exchanger, a cation exchange group is introduced into the second integral cation exchanger, and the cation exchange capacity per unit weight in a dry state is 1 to 9 mg equivalents / g, preferably 1 to 7 mg equivalents / g.

[0100] <Second integral body and method for producing second integral body ion exchanger>

[0101] As a method for producing the second whole, there is mentioned a method of mixing a vinyl monomer, a specific amount of a crosslinking agent, an organic solvent, and a polymerization initiator, and polymerizing the mixture in a static state to obtain the second whole.

[0102] As the vinyl monomer used in the manufacture of the second whole, there is no particular restriction as long as it is a lipophilic monomer with high solubility in organic solvents and contains a vinyl group that can be polymerized in the molecule. As specific examples of these vinyl monomers, styrene monomers such as styrene, α-methylstyrene, vinyltoluene, and vinylbenzyl chloride; α-olefins such as ethylene, propylene, 1-butene, and isobutylene; diene monomers such as butadiene, isoprene, and chloroprene; halogenated olefins such as vinyl chloride, vinyl bromide, vinylidene chloride, and tetrafluoroethylene; nitrile monomers such as acrylonitrile and methacrylonitrile; vinyl esters such as vinyl acetate and vinyl propionate; (meth) acrylic acid monomers such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, and glycidyl methacrylate. These monomers can be used alone or in combination of two or more. The vinyl monomer preferably used is a styrene-based monomer such as styrene and vinylbenzyl chloride.

[0103] The cross-linking agent used in the manufacture of the second whole preferably contains at least 2 vinyl groups that can be polymerized in the molecule, and a cross-linking agent with high solubility in an organic solvent. As specific examples of cross-linking agents, divinylbenzene, divinylnaphthalene, divinylbiphenyl, ethylene glycol di(methacrylate), trimethylolpropane triacrylate, butanediol diacrylate, etc. can be cited. These cross-linking agents can be used alone or in combination of two or more. From the height of mechanical strength and stability relative to hydrolysis, the preferred cross-linking agent is an aromatic polyvinyl compound such as divinylbenzene, divinylnaphthalene, and divinylbiphenyl. The amount of the cross-linking agent used is 1 to 5 mol% relative to the total amount of the vinyl monomer and the cross-linking agent ({cross-linking agent / (vinyl monomer+cross-linking agent)}×100), preferably 1 to 4 mol%. The amount of the cross-linking agent used has a great influence on the overall porous structure obtained. If the amount of the cross-linking agent used exceeds 5 mol%, the size of the continuous pores formed between the skeletons becomes smaller, so it is not preferred. On the other hand, if the amount of the cross-linking agent used is less than 1 mol%, the overall mechanical strength is insufficient, and it is greatly deformed or causes overall destruction during liquid flow, so it is not preferred.

[0104] The organic solvent used in the manufacture of the second whole is an organic solvent in which the vinyl monomer and the cross-linking agent are dissolved but the polymer generated by the polymerization of the vinyl monomer is not dissolved. In other words, it is a poor solvent for the polymer generated by the polymerization of the vinyl monomer. The organic solvent is significantly different due to the type of the vinyl monomer, so it is difficult to cite a common specific example. For example, when the vinyl monomer is styrene, as an organic solvent, alcohols such as methanol, ethanol, propanol, butanol, hexanol, cyclohexanol, octanol, 2-ethylhexanol, decanol, dodecanol, ethylene glycol, tetramethylene glycol, and glycerol can be cited; chain ethers such as diethyl ether and ethylene glycol dimethyl ether; chain saturated hydrocarbons such as hexane, octane, decane, and dodecane. Among them, alcohols are easy to form a particle aggregation structure by standing polymerization, and the three-dimensional continuous pores become larger, so it is preferred. In addition, even good solvents for polystyrene such as benzene and toluene can be used as organic solvents when used together with the above-mentioned poor solvents and when the amount used is small.

[0105] As the polymerization initiator used in the manufacture of the second whole, a compound that generates free radicals by heat and light irradiation is preferred. The polymerization initiator is preferably oil-soluble. As a specific example of the polymerization initiator, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(dimethyl isobutyrate), 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexane-1-carbonitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, ammonium persulfate, tetramethylthiuram disulfide, etc. can be cited. The amount of the polymerization initiator used varies greatly depending on the type of monomer, polymerization temperature, etc., and is about 0.01 to 5 mol % relative to the total amount of the vinyl monomer and the crosslinking agent ({polymerization initiator / (vinyl monomer+crosslinking agent)}×100).

[0106] In the manufacture of the second whole, various conditions can be selected as polymerization conditions according to the type of monomer and the type of initiator. For example, when 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, etc. are used as initiators, the polymerization can be carried out by heating at 30 to 100°C in a sealed container under an inert atmosphere for 1 to 48 hours. After the polymerization is completed, the contents are taken out, and in order to remove the unreacted vinyl monomer and the organic solvent, the second whole is obtained by extraction with a solvent such as acetone.

[0107] In the manufacture of the second whole, if the polymerization of the vinyl monomer dissolved in the organic solvent is carried out quickly, the organic polymer particles close to the average particle size of 1 μm will settle and agglomerate, and a three-dimensional continuous skeleton part can be formed. The conditions for the rapid polymerization of the vinyl monomer refer to: although it cannot be generalized due to differences in the vinyl monomer, cross-linking agent, polymerization initiator and polymerization temperature, in order to increase the cross-linking agent, increase the monomer concentration, increase the temperature, etc. Considering the above-mentioned polymerization conditions, it is sufficient to appropriately determine the polymerization conditions that cause the organic polymer particles with an average particle size of 1 to 50 μm to agglomerate. In addition, when a three-dimensional continuous pore with an average diameter of 20 to 100 μm is formed between the skeleton, as shown above, the amount of the cross-linking agent used relative to the total amount of the vinyl monomer and the cross-linking agent is set to a specific amount. In addition, when the overall total pore volume is 1 to 5 ml / g, although it cannot be generalized due to differences in vinyl monomer, cross-linking agent, polymerization initiator and polymerization temperature, polymerization can be carried out under the condition that the amount of organic solvent used relative to the total amount of organic solvent, monomer and cross-linking agent ({organic solvent / (organic solvent+monomer+cross-linking agent)}×100) is 30 to 80% by weight, preferably 40 to 70% by weight.

[0108] As a method for producing the second integral ion exchanger, there can be cited a method in which, in the above-mentioned method for producing the second integral body, a monomer containing an ion exchange group, for example, a carboxylic acid group, a sulfonic acid group or other ion exchange group is introduced into a vinyl monomer not containing an ion exchange group, and the monomer is polymerized to produce the integral ion exchanger in one stage; a method in which a vinyl monomer not containing an ion exchange group is polymerized to form the second integral body, and then an ion exchange group is introduced, etc.

[0109] The method for introducing the ion exchange groups into the second whole is the same as the method for introducing the ion exchange groups into the first whole.

[0110] <Description of the third entity and the third entity ion exchanger>

[0111] In the platinum group metal loaded catalyst of the present invention, the third integral ion exchanger which serves as a carrier of the platinum group metal particles is a continuous macroporous structure in which bubble-shaped macropores overlap with each other, and the overlapping parts form openings with an average diameter of 30 to 300 μm in a dry state. The total pore volume in a dry state is 0.5 to 10 ml / g, and in the SEM image of the cross section of the continuous macroporous structure (dried body), the area of ​​the skeleton portion shown in the cross section is 25 to 50% of the image area. The structure has ion exchange groups, and the ion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, and the ion exchange groups are uniformly distributed in the organic porous ion exchanger. In addition, the third whole is the whole before the introduction of ion exchange groups, which is a continuous macroporous structure in which bubble-shaped macropores overlap each other, and the overlapping parts form openings with an average diameter of 30 to 300 μm in a dry state. The total pore volume in a dry state is 0.5 to 10 ml / g, and the area of ​​the skeleton part shown in the cross-section in the SEM image of the cross-section of the continuous macroporous structure (dried body) is an organic porous body that accounts for 25 to 50% of the image area.

[0112] The third integral ion exchanger is a continuous macroporous structure in which bubble-like macropores overlap each other, and the overlapping portions form openings (mesopores) with an average diameter of 30 to 300 μm, preferably 30 to 200 μm, and particularly preferably 40 to 100 μm in a dry state. Figure 3 This is a SEM photograph showing a morphological example of the third monolithic ion exchanger. Figure 3 The third monolithic ion exchanger shown is a continuous macroporous structure having a plurality of bubble-shaped macropores, the bubble-shaped macropores overlap each other, and the overlapping portions form a common opening (mesopore), most of which are open-pore structures. If the average diameter of the openings in a dry state is less than 30 μm, the pressure loss during the passage of liquid increases, which is not preferred. If the average diameter of the openings in a dry state is too large, the contact between the reaction liquid and the monolithic ion exchanger and the supported platinum group metal particles becomes insufficient, resulting in a decrease in catalytic activity, which is not preferred.

[0113] It should be noted that the average diameter of the openings of the third whole in a dry state, the average diameter of the openings of the third whole ion exchanger in a dry state, and the average diameter of the openings of the third whole intermediate (3) in a dry state obtained in the I step of manufacturing the third whole described below refer to: measured by mercury penetration porosimetry, and the maximum value of the pore distribution curve obtained by the mercury penetration porosimetry.

[0114] In the third integral ion exchanger, in the SEM image of the cross section of the continuous macroporous structure (dried body), the area of ​​the skeleton portion shown in the cross section is 25 to 50% in the image area, preferably 25 to 45%. If the area of ​​the skeleton portion shown in the cross section is less than 25% in the image area, it becomes a thin skeleton, the mechanical strength is reduced, and the integral ion exchanger is greatly deformed when the liquid is passed through at a high flow rate, so it is not preferred. In addition, the contact efficiency between the reaction liquid and the integral ion exchanger and the platinum group metal particles loaded thereon is reduced, and the catalytic effect is reduced, so it is not preferred. If it exceeds 50%, the skeleton becomes too thick, and the pressure loss during the liquid passing increases, so it is not preferred.

[0115] The conditions for obtaining the SEM image are any conditions under which the skeleton shown in the cross section is clearly displayed, such as a magnification of 100 to 600 and a photographic area of ​​about 150 mm × 100 mm. SEM observation can be performed in three or more, preferably five or more images obtained by photographing the cut portion at any position of any cross section of the third integral ion exchanger excluding the subjective. The cut third integral ion exchanger is provided to the electron microscope and is therefore in a dry state. Reference Figure 3 and Figure 4 The skeleton part of the cut surface in the SEM image is described. Figure 4 Is the transfer Figure 3 The cross section of the SEM photograph shows the skeleton part. Figure 3 and Figure 4 In the figure, the irregular shape and the cross section thereof are the "skeleton portion (symbol 12) shown in the cross section" of the present invention. Figure 3 The circular holes shown are openings (mesopores), and the ones with larger curvatures and curved surfaces are macropores ( Figure 4 The symbol in 13). Figure 4 The area of ​​the skeleton portion shown in the cross section is 28% in the rectangular image region 11. In this way, the skeleton portion can be clearly identified.

[0116] In the SEM image, the method for measuring the area of ​​the skeleton part shown as a cross section is not particularly limited, and the skeleton part can be determined by subjecting it to known computer processing, etc., and then automatically calculated or manually calculated by a computer, etc. As a manual calculation, an irregular shape can be replaced with an aggregate such as a quadrilateral, triangle, circle or trapezoid, and these can be stacked to obtain the area.

[0117] In addition, the total pore volume per unit weight of the third integral ion exchanger in a dry state is 0.5 to 10 ml / g, preferably 0.8 to 8 ml / g. If the total pore volume is less than 0.5 ml / g, the pressure loss during liquid flow increases, so it is not preferred. In addition, the amount of fluid passing through per unit cross-sectional area decreases, and the processing capacity decreases, so it is not preferred. On the other hand, if the total pore volume exceeds 10 ml / g, the mechanical strength decreases, especially when the liquid is passed at a high flow rate, the integral ion exchanger is greatly deformed, so it is not preferred. In addition, the contact efficiency between the reaction liquid and the integral ion exchanger and the platinum group metal particles loaded thereon is reduced, so the catalytic effect is also reduced, so it is not preferred.

[0118] In the third integral ion exchanger, the material constituting the skeleton is an organic polymer material having a cross-linked structure. The cross-linking density of the polymer material is not particularly limited, and contains 0.3 to 10 mol%, preferably 0.3 to 5 mol% of cross-linked structural units relative to all structural units constituting the polymer material. If the cross-linked structural unit is less than 0.3 mol%, the mechanical strength is insufficient, so it is not preferred. On the other hand, if it exceeds 10 mol%, it is sometimes difficult to introduce ion exchange groups, so it is not preferred.

[0119] The type of polymer material constituting the skeleton of the third integral ion exchanger is not particularly limited. For example, aromatic vinyl polymers such as polystyrene, poly(α-methylstyrene), polyvinyltoluene, polyvinylbenzyl chloride, polyvinylbiphenyl, and polyvinylnaphthalene can be cited; polyolefins such as polyethylene and polypropylene; poly(halogenated polyolefins) such as polyvinyl chloride and polytetrafluoroethylene; nitrile polymers such as polyacrylonitrile; and crosslinked polymers such as (meth)acrylic polymers such as polymethyl methacrylate, polyglycidyl methacrylate, and polyethyl acrylate. The above polymers may be polymers obtained by copolymerizing a single vinyl monomer and a crosslinking agent, or may be polymers obtained by polymerizing a plurality of vinyl monomers and a crosslinking agent, or may be materials obtained by blending two or more polymers. Among these organic polymer materials, crosslinked polymers of aromatic vinyl polymers are preferred from the perspective of ease of forming a continuous macroporous structure, ease of introducing ion exchange groups when introducing ion exchange groups, high mechanical strength, and high stability to acids or alkalis. In particular, styrene-divinylbenzene copolymers and vinylbenzyl chloride-divinylbenzene copolymers can be cited as preferred materials.

[0120] The ion exchange groups introduced into the third bulk ion exchanger are the same as the ion exchange groups introduced into the first bulk ion exchanger.

[0121] In the third monolithic ion exchanger, the introduced ion exchange groups are uniformly distributed not only on the surface of the porous body but also inside the framework of the porous body.

[0122] The ion exchange capacity per unit weight of the third integral ion exchanger in a dry state is 1 to 9 mg equivalent / g. The third integral ion exchanger can further increase the opening diameter and make the skeleton of the continuous macroporous structure (the wall of the thickened skeleton) thicker, so that the ion exchange capacity per unit volume can be increased dramatically while suppressing the pressure loss to a low level. By making the ion exchange capacity per unit weight in a dry state in the above range, the environment around the catalytic active point such as pH inside the catalyst can be changed, thereby increasing the catalytic activity. In the case where the third integral ion exchanger is an integral anion exchanger, an anion exchange group is introduced into the third integral anion exchanger, and the anion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, preferably 1 to 8 mg equivalent / g, and particularly preferably 1 to 7 mg equivalent / g. In addition, in the case where the third integral ion exchanger is an integral cation exchanger, a cation exchange group is introduced into the third integral cation exchanger, and the cation exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, preferably 1 to 7 mg equivalent / g.

[0123] <Third integral body and method for producing third integral body ion exchanger>

[0124] The third entity is obtained by carrying out the following steps: step I, in which a mixture of an oil-soluble monomer not containing an ion exchange group, a surfactant and water is stirred to prepare an oil-in-water emulsion, and then the oil-in-water emulsion is polymerized to obtain an integral organic porous intermediate having a continuous macroporous structure with a total pore volume of 5 to 16 ml / g (hereinafter also referred to as the integral intermediate (3)); step II, in which a mixture comprising a vinyl monomer, a cross-linking agent having at least two vinyl groups in one molecule, an organic solvent and a polymerization initiator is prepared, and the organic solvent is an organic solvent in which the vinyl monomer and the cross-linking agent are dissolved but the polymer generated by polymerization of the vinyl monomer is not dissolved; step III, in which the mixture obtained in step II is allowed to stand and polymerization is carried out in the presence of the integral intermediate (3) obtained in step I to obtain a third entity having a skeleton coarser than the skeleton of the integral intermediate (3).

[0125] In the third overall manufacturing method, step I may be performed according to the method described in Japanese Patent Application Laid-Open No. 2002-306976.

[0126] In the manufacture of the overall intermediate (3) of step I involved in the manufacturing method of the third overall, as an oil-soluble monomer that does not contain an ion exchange group, for example, a lipophilic monomer that does not contain an ion exchange group such as a carboxylic acid group, a sulfonic acid group, a quaternary ammonium group, and has low solubility in water can be cited. As preferred monomers of these monomers, styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, divinylbenzene, ethylene, propylene, isobutylene, butadiene, ethylene glycol dimethacrylate, etc. can be cited. These monomers can be used alone or in combination of two or more. Among them, cross-linking monomers such as divinylbenzene and ethylene glycol dimethacrylate are selected as at least one component of the oil-soluble monomer, and the content thereof is 0.3 to 10 mol%, preferably 0.3 to 5 mol%, relative to all oil-soluble monomers. In the case of introducing ion exchange groups, the amount of ion exchange groups can be quantitatively introduced, so it is preferred.

[0127] The surfactant used in the first step of the manufacturing method of the third whole is not particularly limited as long as it is a surfactant that can form an oil-in-water (W / O) emulsion when an oil-soluble monomer that does not contain an ion exchange group is mixed with water. Nonionic surfactants such as sorbitan monooleate, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan trioleate, polyoxyethylene nonylphenyl ether, polyoxyethylene stearyl ether, and polyoxyethylene sorbitan monooleate can be used; anionic surfactants such as potassium oleate, sodium dodecylbenzenesulfonate, and sodium sulfosuccinate dioctyl ester; cationic surfactants such as distearyl dimethyl ammonium chloride; and amphoteric surfactants such as lauryl dimethyl betaine. These surfactants can be used alone or in combination of two or more. It should be noted that the oil-in-water emulsion refers to an emulsion in which the oil phase is a continuous phase and water droplets are dispersed therein. The amount of the surfactant to be added varies greatly depending on the type of oil-soluble monomer and the target emulsion particle (macroporous) size and cannot be generalized, but can be selected within the range of about 2 to 70% relative to the total amount of the oil-soluble monomer and the surfactant.

[0128] In addition, in the first step involved in the third overall manufacturing method, when forming an oil-in-water emulsion, a polymerization initiator can be used as needed. The polymerization initiator preferably uses a compound that generates free radicals by heat and light irradiation. The polymerization initiator can be water-soluble or oil-soluble, for example, azobisisobutyronitrile, azobisdimethylvaleronitrile, azobiscyclohexanecarbonitrile, azobis(cyclohexanecarbonitrile), benzoyl peroxide, potassium persulfate, ammonium persulfate, hydrogen peroxide-ferrous chloride, sodium persulfate-acidic sodium sulfite, tetramethylthiuram disulfide, etc.

[0129] In the process I involved in the manufacturing method of the third overall, there is no particular restriction on the mixing method when mixing an oil-soluble monomer, a surfactant, water and a polymerization initiator that do not contain an ion exchange group to form an oil-in-water type emulsion. A method of mixing all the components at once can be used; a method of mixing the components after the oil-soluble monomer, the surfactant and the oil-soluble polymerization initiator, i.e., the oil-soluble component, and the water, the water-soluble polymerization initiator, i.e., the water-soluble component are uniformly dissolved. There is no particular restriction on the mixing device used to form the emulsion. A common mixer, homogenizer, high-pressure homogenizer, etc. can be used, and a device suitable for obtaining the target emulsion particle size can be selected. In addition, the mixing conditions are not particularly limited, and the stirring speed and stirring time that can obtain the target emulsion particle size can be arbitrarily set.

[0130] The overall intermediate (3) obtained in step I of the manufacturing method of the third whole has a continuous macroporous structure. If it is made to coexist with the polymerization system, a porous structure with a coarse skeleton can be formed using the structure of the overall intermediate (3) as a mold. In addition, the overall intermediate (3) is an organic polymer material having a cross-linked structure. The cross-linking density of the polymer material is not particularly limited, and it contains 0.3 to 10 mol%, preferably 0.3 to 5 mol% of cross-linked structural units relative to all structural units constituting the polymer material. If the cross-linked structural unit is less than 0.3 mol%, the mechanical strength is insufficient, so it is not preferred. In particular, when the total pore volume is as large as 10 to 16 ml / g, in order to maintain a continuous macroporous structure, it is preferably contained more than 2 mol% of cross-linked structural units. On the other hand, if it exceeds 10 mol%, it is difficult to introduce ion exchange groups, so it is not preferred.

[0131] In step I of the method for producing the third whole, the type of polymer material used as the whole intermediate (3) is not particularly limited, and the same polymer material as the first whole can be used. Thus, the same polymer can be formed in the skeleton of the whole intermediate (3), and the third whole having a thicker and more uniform skeleton structure can be obtained.

[0132] The total pore volume per unit weight of the overall intermediate (3) obtained in step I of the manufacturing method of the third overall body in a dry state is 5 to 16 ml / g, preferably 6 to 16 ml / g. If the total pore volume is too small, the total pore volume of the overall body obtained after polymerization of the vinyl monomer becomes too small, and the pressure loss during fluid passage becomes large, which is not preferred. On the other hand, if the total pore volume is too large, the overall structure obtained after polymerization of the vinyl monomer deviates from the continuous macroporous structure, which is not preferred. When the total pore volume of the overall intermediate (3) is within the above numerical range, the ratio of monomer to water can be approximately 1:5 to 1:20.

[0133] In addition, the average diameter of the openings (mesopores) of the integral intermediate (3) obtained in step I of the manufacturing method of the third integral body, which are the overlapping parts of the macropores and the macropores, is 20 to 200 μm in a dry state. If the average diameter of the openings in a dry state is less than 20 μm, the opening diameter of the entire body obtained after polymerization of the vinyl monomer becomes smaller, and the pressure loss during liquid flow becomes larger, so it is not preferred. On the other hand, if it exceeds 200 μm, the opening diameter of the entire body obtained after polymerization of the vinyl monomer becomes too large, and the contact between the reaction liquid and the integral anion exchanger becomes insufficient, resulting in a decrease in catalytic activity, so it is not preferred. The integral intermediate (3) is preferably a uniform structure with a uniform size of macropores and opening diameters, but is not limited to this, and non-uniform macropores larger than the uniform macropore size may be dispersed in the uniform structure.

[0134] The step II involved in the third overall manufacturing method is a step of preparing a mixture comprising a vinyl monomer, a cross-linking agent having at least two vinyl groups in one molecule, a vinyl monomer, an organic solvent, and a polymerization initiator; the organic solvent is an organic solvent in which the cross-linking agent is dissolved but the polymer generated by polymerization of the vinyl monomer is not dissolved. In addition, there is no order between the steps I and II, and the step II may be performed after the step I, or the step I may be performed after the step II.

[0135] The vinyl monomer used in step II involved in the manufacturing method of the third whole is not particularly limited as long as it is a lipophilic vinyl monomer containing a polymerizable vinyl group in the molecule and having high solubility in organic solvents. It is preferred to select a vinyl monomer of the same type or a similar polymer material as the whole intermediate (3) coexisting in the above-mentioned polymerization system. As specific examples of these vinyl monomers, aromatic vinyl monomers such as styrene, α-methylstyrene, vinyl toluene, vinyl benzyl chloride, vinyl biphenyl, and vinyl naphthalene can be cited; α-olefins such as ethylene, propylene, 1-butene, and isobutylene; diene monomers such as butadiene, isoprene, and chloroprene; halogenated olefins such as vinyl chloride, vinyl bromide, vinylidene chloride, and tetrafluoroethylene; nitrile monomers such as acrylonitrile and methacrylonitrile; vinyl esters such as vinyl acetate and vinyl propionate; (meth) acrylic acid monomers such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, and glycidyl methacrylate. These monomers can be used alone or in combination of two or more. The preferred vinyl monomers are aromatic vinyl monomers such as styrene and vinyl benzyl chloride.

[0136] The amount of the vinyl monomer used in the step II of the manufacturing method of the third whole is 3 to 50 times, preferably 4 to 40 times, by weight relative to the whole intermediate (3) coexisting during polymerization. If the amount of the vinyl monomer added is less than 3 times relative to the whole intermediate, the generated whole skeleton (the thickness of the wall of the whole skeleton) cannot be thickened. In addition, when the ion exchange group is introduced, the ion exchange capacity per unit volume after the introduction becomes smaller, so it is not preferred. On the other hand, if the amount of the vinyl monomer added exceeds 50 times, the opening diameter becomes smaller, and the pressure loss during the liquid flow becomes larger, so it is not preferred.

[0137] The cross-linking agent used in the II process involved in the manufacturing method of the third whole is preferably a cross-linking agent containing at least 2 vinyl groups that can be polymerized in the molecule and having high solubility in an organic solvent. As a specific example of a cross-linking agent, divinylbenzene, divinylnaphthalene, divinylbiphenyl, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, butanediol diacrylate, etc. can be cited. These cross-linking agents can be used alone or in combination of two or more. From the height of mechanical strength and stability to hydrolysis, the preferred cross-linking agent is an aromatic polyvinyl compound such as divinylbenzene, divinylnaphthalene, and divinylbiphenyl. The amount of cross-linking agent used is preferably 0.3 to 10 mol% relative to the total amount of vinyl monomer and cross-linking agent, and is particularly preferably 0.3 to 5 mol%. If the amount of cross-linking agent used is less than 0.3 mol%, the overall mechanical strength is insufficient, so it is not preferred. On the other hand, if it exceeds 10 mol%, the amount of ion exchange group introduced is sometimes reduced, so it is not preferred. It should be noted that the amount of the crosslinking agent is preferably used in a manner that is substantially equal to the crosslinking density of the overall intermediate (3) coexisting during the vinyl monomer / crosslinking agent polymerization. If the amount of the two differs too much, a deviation in the crosslinking density distribution will occur in the resulting overall structure, and cracks will be easily generated during the ion exchange group introduction reaction.

[0138] The organic solvent used in step II of the third overall manufacturing method is an organic solvent that dissolves the vinyl monomer and the crosslinking agent but does not dissolve the polymer generated by the polymerization of the vinyl monomer. In other words, it is a poor solvent for the polymer generated by the polymerization of the vinyl monomer. The organic solvent varies depending on the type of the vinyl monomer, so it is difficult to give a general specific example. For example, when the vinyl monomer is styrene, the organic solvent includes alcohols such as methanol, ethanol, propanol, butanol, hexanol, cyclohexanol, octanol, 2-ethylhexanol, decanol, dodecanol, ethylene glycol, propylene glycol, tetramethylene glycol, and glycerol; chain (poly) ethers such as diethyl ether, ethylene glycol dimethyl ether, cellosolve, methyl cellosolve, butyl cellosolve, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; chain saturated hydrocarbons such as hexane, heptane, octane, isooctane, decane, and dodecane; and esters such as ethyl acetate, isopropyl acetate, cellosolve acetate, and ethyl propionate. In addition, even if it is a good solvent for polystyrene such as dioxane, THF, toluene, it can also be used as an organic solvent when used together with the above-mentioned poor solvent and its usage amount is small. The usage amount of these organic solvents is preferably used in a manner such that the concentration of the above-mentioned vinyl monomer becomes 30 to 80 weight %. If the organic solvent usage amount departs from the above-mentioned scope and makes the vinyl monomer concentration less than 30 weight %, the polymerization rate decreases, or the overall structure after the polymerization departs from the scope of the 3rd overall, so it is not preferred. On the other hand, if the vinyl monomer concentration exceeds 80 weight %, the polymerization is likely to be out of control, so it is not preferred.

[0139] As the polymerization initiator used in the II step involved in the manufacturing method of the third overall, it is preferred to use a compound that generates free radicals by heat or light irradiation. The polymerization initiator is preferably oil-soluble. As specific examples of the polymerization initiator, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(dimethyl isobutyrate), 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexane-1-carbonitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, ammonium persulfate, tetramethylthiuram disulfide, etc. can be cited. The amount of the polymerization initiator used varies greatly depending on the type of monomer, polymerization temperature, etc., and can be used in the range of about 0.01 to 5% relative to the total amount of the vinyl monomer and the crosslinking agent.

[0140] The step III involved in the method for producing the third whole is a step of allowing the mixture obtained in the step II to stand and polymerizing in the presence of the monolithic intermediate (3) obtained in the step I to obtain a third whole having a skeleton coarser than that of the monolithic intermediate (3). The monolithic intermediate (3) used in the step III plays a very important role in forming the third whole, and if the monolithic intermediate (3) having a continuous macroporous structure exists in the above-mentioned polymerization system, the third whole can be obtained.

[0141] In the manufacturing method of the third whole, the internal volume of the reaction container is not particularly limited as long as it is a size that allows the whole intermediate (3) to exist in the reaction container. It can be any of the following: when the whole intermediate (3) is placed in the reaction container, a gap can be formed around the whole when viewed from above, and the internal volume of the whole intermediate (3) can be placed in the reaction container without a gap. Among them, the whole with a thick skeleton after polymerization will not be pressed from the inner wall of the container, and placing it in the reaction container without a gap will not cause strain on the whole, there is no waste of reaction raw materials, etc., and it is efficient. It should be noted that even if the internal volume of the reaction container is large and there is a gap around the whole after polymerization, the vinyl monomer and the cross-linking agent will be adsorbed and distributed on the whole intermediate (3), so that the particle aggregation structure will not be generated in the gap part in the reaction container.

[0142] In step III of the manufacturing method involved in the third whole, the whole intermediate (3) is placed in a reaction container in a state of being impregnated with a mixture (solution). The mixing ratio of the mixture obtained in step II and the whole intermediate (3) is as shown above, and the amount of vinyl monomer added is preferably 3 to 50 times by weight, preferably 4 to 40 times by weight relative to the whole intermediate (3). In this way, a third whole having a moderate opening diameter and a coarse skeleton can be obtained. In the reaction container, the vinyl monomer and the cross-linking agent in the mixture are adsorbed and distributed on the skeleton of the whole intermediate after standing, and polymerization is carried out within the skeleton of the whole intermediate (3).

[0143] In the step III involved in the method for producing the third whole, various conditions are selected for polymerization conditions depending on the type of monomer and the type of initiator. For example, when 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, etc. are used as initiators, heating polymerization is performed at 30 to 100°C in a sealed container under an inert atmosphere for 1 to 48 hours. By heating polymerization, the vinyl monomer and crosslinking agent adsorbed and distributed on the skeleton of the whole intermediate (3) are polymerized in the skeleton, making the skeleton thicker. After the polymerization is completed, the contents are taken out, and in order to remove the unreacted vinyl monomer and the organic solvent, extraction is performed using a solvent such as acetone to obtain the third whole.

[0144] The third monolithic ion exchanger is obtained by performing the following step IV, that is, introducing ion exchange groups into the third monolithic body having a coarse skeleton, which is obtained in step III.

[0145] The method for introducing ion exchange groups into the third entity is the same as the method for introducing ion exchange groups into the first entity.

[0146] The third body and the ion exchanger of the third body have a particularly large opening diameter, but have a thick skeleton and thus have high mechanical strength.

[0147] <Description of the Fourth Whole and the Fourth Whole Ion Exchanger>

[0148] In the platinum group metal supported catalyst of the present invention, the fourth integral ion exchanger which serves as a carrier of the platinum group metal particles is a co-continuous structure comprising a three-dimensional continuous skeleton and three-dimensional continuous pores, the total pore volume in a dry state is 0.5 to 10 ml / g, and the ion exchange group has an ion exchange capacity per unit weight in a dry state of 1 to 9 mg equivalent / g, and the ion exchange groups are uniformly distributed in the organic porous ion exchanger as an integral ion exchanger; the above-mentioned three-dimensional continuous skeleton is a skeleton comprising an aromatic vinyl polymer having an average thickness of 1 to 60 μm in a dry state, the aromatic vinyl polymer contains 0.1 to 5.0 mol% of cross-linked structural units relative to all structural units, and the above-mentioned three-dimensional continuous pores are pores having an average diameter of 10 to 200 μm between the skeletons in a dry state. In addition, the fourth whole is the whole before the introduction of ion exchange groups, which is a co-continuous structure comprising a three-dimensional continuous skeleton and three-dimensional continuous pores, and is an organic porous body with a total pore volume in a dry state of 0.5 to 10 ml / g; the above-mentioned three-dimensional continuous skeleton is a skeleton comprising an aromatic vinyl polymer with an average coarseness of 1 to 60 μm in a dry state, and the above-mentioned aromatic vinyl polymer contains 0.1 to 5.0 mol% of cross-linked structural units relative to all structural units, and the above-mentioned three-dimensional continuous pores are pores with an average diameter of 10 to 200 μm between the skeleton in a dry state.

[0149] The fourth integral ion exchanger is a co-continuous structure comprising a three-dimensional continuous skeleton and three-dimensional continuous pores, wherein the skeleton has an average thickness of 1 to 60 μm in a dry state, preferably a skeleton having a thickness of 3 to 58 μm, and the pores have an average diameter of 10 to 200 μm in a dry state, preferably 15 to 180 μm, and particularly preferably 20 to 150 μm. Figure 5 This is a SEM photograph showing a morphological example of the fourth monolithic ion exchanger. Figure 6 A schematic diagram showing the co-continuous structure of the fourth integral ion exchanger. Figure 6As shown in the schematic diagram of FIG. 1 , the co-continuous structure is a continuous skeleton phase 1 and a continuous pore phase 2 that are intertwined, each of which is a three-dimensional continuous structure 10. Compared with the conventional continuous bubble type or particle aggregation type, the continuous pores 2 have high pore continuity and no deviation in size. In addition, the co-continuous structure has high mechanical strength because the skeleton is thick.

[0150] If the average diameter of the three-dimensional continuous pores is less than 10 μm in a dry state, the pressure loss during liquid flow becomes large, so it is not preferred. If it exceeds 200 μm, the contact between the reaction solution and the overall ion exchanger becomes insufficient, and as a result, the catalytic activity becomes insufficient, so it is not preferred. In addition, if the average thickness of the skeleton is less than 1 μm in a dry state, the overall ion exchanger is greatly deformed when the liquid is passed at a high flow rate, so it is not preferred. In addition, the contact efficiency between the reaction solution and the overall ion exchanger is reduced, and the catalytic effect is reduced, so it is not preferred. On the other hand, if the thickness of the skeleton exceeds 60 μm, the skeleton becomes too thick, and the pressure loss during liquid flow increases, so it is not preferred.

[0151] The average diameter of the opening of the fourth whole in a dry state, the average diameter of the opening of the fourth whole ion exchanger in a dry state, and the average diameter of the opening of the fourth whole intermediate (4) in a dry state obtained in the first step of manufacturing the fourth whole described below refer to: measured by mercury penetration method, and the maximum value of the pore distribution curve obtained by the mercury penetration method. In addition, the average roughness of the skeleton of the fourth whole ion exchanger in a dry state is obtained by SEM observation of the fourth whole ion exchanger in a dry state. Specifically, at least three SEM observations of the fourth whole ion exchanger in a dry state are performed, and the roughness of the skeleton in the obtained image is measured, and their average value is set as the average roughness. It should be noted that the skeleton is rod-shaped and has a circular cross-sectional shape, but it can also include skeletons with different diameter cross-sections such as elliptical cross-sectional shapes. The roughness at this time is the average of the short diameter and the long diameter.

[0152] In addition, the total pore volume per unit weight of the fourth integral ion exchanger in a dry state is 0.5 to 10 ml / g. If the total pore volume is less than 0.5 ml / g, the pressure loss during liquid flow increases, so it is not preferred. In addition, the amount of permeation per unit cross-sectional area decreases, and the processing volume decreases, so it is not preferred. On the other hand, if the total pore volume exceeds 10 ml / g, the mechanical strength decreases, especially when the liquid is passed at a high flow rate, the overall ion exchanger is greatly deformed, so it is not preferred. In addition, the contact efficiency between the reaction liquid and the integral ion exchanger decreases, so the catalyst efficiency is also reduced, so it is not preferred. If the size of the three-dimensional continuous pores and the total pore volume are within the above range, the contact with the reaction liquid is very uniform, the contact area is also large, and liquid can be passed under low pressure loss.

[0153] In the fourth integral ion exchanger, the material constituting the skeleton is an aromatic vinyl polymer containing 0.1 to 5 mol%, preferably 0.5 to 3.0 mol% of cross-linked structural units relative to all structural units and is hydrophobic. If the cross-linked structural unit is less than 0.1 mol%, the mechanical strength is insufficient, so it is not preferred. On the other hand, if it exceeds 5 mol%, the structure of the porous body is easily separated from the co-continuous structure. There is no particular restriction on the type of aromatic vinyl polymer, for example, polystyrene, poly (α-methylstyrene), polyvinyl toluene, polyvinyl benzyl chloride, polyvinyl biphenyl, polyvinyl naphthalene, etc. can be cited. The above polymer can be a polymer obtained by copolymerizing a single vinyl monomer and a cross-linking agent, or a polymer obtained by polymerizing a plurality of vinyl monomers and a cross-linking agent, and in addition, it can also be a substance obtained by blending two or more polymers. Among these organic polymer materials, styrene-divinylbenzene copolymers and vinylbenzyl chloride-divinylbenzene copolymers are preferred from the ease of forming a co-continuous structure, the ease of introducing ion exchange groups, the height of mechanical strength, and the height of stability to acid or alkali.

[0154] The ion exchange groups introduced into the fourth bulk ion exchanger are the same as the ion exchange groups introduced into the first bulk ion exchanger.

[0155] In the fourth monolithic ion exchanger, the introduced ion exchange groups are uniformly distributed not only on the surface of the porous body but also inside the framework of the porous body.

[0156] The fourth integral ion exchanger has an ion exchange capacity of 1 to 9 mg equivalent / g per unit weight in a dry state. The continuity and uniformity of the three-dimensional continuous pores of the fourth integral ion exchanger are high, so even if the total pore volume is reduced, the pressure loss does not increase that much. Therefore, the ion exchange capacity per unit volume can be increased dramatically while suppressing the pressure loss to a low level. By making the ion exchange capacity per unit weight within the above range, the environment around the catalytic active points such as the pH inside the catalyst can be changed, thereby increasing the catalytic activity. In the case where the fourth integral ion exchanger is an integral anion exchanger, an anion exchange group is introduced into the fourth integral anion exchanger, and the anion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, preferably 1 to 8 mg equivalent / g, and particularly preferably 1 to 7 mg equivalent / g. When the fourth monolithic ion exchanger is a monolithic cation exchanger, cation exchange groups are introduced into the fourth monolithic cation exchanger, and the cation exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, preferably 1 to 7 mg equivalent / g.

[0157] <Fourth integral body and method for producing fourth integral ion exchanger>

[0158] The fourth entity is obtained by carrying out the following steps: step I, wherein a water-in-oil emulsion is prepared by stirring a mixture of an oil-soluble monomer not containing an ion exchange group, a surfactant and water, and then the water-in-oil emulsion is polymerized to obtain a monolithic organic porous intermediate having a continuous macroporous structure with a total pore volume exceeding 16 ml / g and not more than 30 ml / g (hereinafter also referred to as the monolithic intermediate (4)); step II, wherein a mixture containing an aromatic vinyl monomer, a cross-linking agent having at least two vinyl groups in one molecule in an amount of 0.3 to 5 mol % relative to the total oil-soluble monomers, an organic solvent and a polymerization initiator is prepared; the organic solvent is an organic solvent in which the aromatic vinyl monomer and the cross-linking agent are dissolved but the polymer generated by polymerization of the aromatic vinyl monomer is not dissolved; and step III, wherein the mixture obtained in step II is polymerized while standing and in the presence of the monolithic intermediate (4) obtained in step I to obtain an organic porous body as a co-continuous structure, namely the fourth entity.

[0159] In the step I of the fourth overall production method, the step I of obtaining the overall intermediate (4) may be carried out according to the method described in Japanese Patent Application Laid-Open No. 2002-306976.

[0160] That is, in step I involved in the fourth overall manufacturing method, as the oil-soluble monomer not containing an ion exchange group, for example, there can be mentioned a lipophilic monomer that does not contain an ion exchange group such as a carboxylic acid group, a sulfonic acid group, a tertiary amino group, a quaternary ammonium group, and has low solubility in water. Specific examples of these monomers include aromatic vinyl monomers such as styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, vinylbiphenyl, and vinylnaphthalene; α-olefins such as ethylene, propylene, 1-butene, and isobutylene; diene monomers such as butadiene, isoprene, and chloroprene; halogenated olefins such as vinyl chloride, vinyl bromide, vinylidene chloride, and tetrafluoroethylene; nitrile monomers such as acrylonitrile and methacrylonitrile; vinyl esters such as vinyl acetate and vinyl propionate; (meth) acrylic acid monomers such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, and glycidyl methacrylate. Among these monomers, aromatic vinyl monomers such as styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, and divinylbenzene can be cited as preferred monomers. These monomers can be used alone or in combination of two or more. Among them, crosslinking monomers such as divinylbenzene and ethylene glycol dimethacrylate are selected as at least one component of the oil-soluble monomers, and their content is 0.3 to 5 mol%, preferably 0.3 to 3 mol%, relative to all oil-soluble monomers, which is conducive to the formation of a co-continuous structure and is therefore preferred.

[0161] The surfactant used in step I of the fourth overall production method is the same as the surfactant used in step I of the third overall production method, and the description thereof is omitted.

[0162] In addition, in the process I involved in the manufacturing method of the fourth overall, when forming an oil-in-water emulsion, a polymerization initiator can be used as needed. The polymerization initiator preferably uses a compound that generates free radicals by heat or light irradiation. The polymerization initiator can be water-soluble or oil-soluble, for example, 2,2'-azobis (isobutyronitrile), 2,2'-azobis (2,4-dimethylvaleronitrile), 2,2'-azobis (2-methylbutyronitrile), 2,2'-azobis (4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis (dimethyl isobutyrate), 4,4'-azobis (4-cyanovaleric acid), 1,1'-azobis (cyclohexane-1-carbonitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, ammonium persulfate, tetramethylthiuram disulfide, hydrogen peroxide-ferrous chloride, sodium persulfate-acid sodium sulfite, etc. can be cited.

[0163] In step I involved in the manufacturing method of the fourth overall structure, the mixing method for mixing an oil-soluble monomer that does not contain an ion exchange group, a surfactant, water and a polymerization initiator to form an oil-in-water emulsion is the same as the mixing method in step I involved in the manufacturing method of the third overall structure, and its description is omitted.

[0164] The overall intermediate (4) obtained in step I of the manufacturing method of the fourth overall structure is an organic polymer material having a cross-linked structure, preferably an aromatic vinyl polymer. The cross-linking density of the polymer material is not particularly limited, and contains 0.1 to 5 mol%, preferably 0.3 to 3 mol% of cross-linked structural units relative to all structural units constituting the polymer material. If the cross-linked structural unit is less than 0.3 mol%, the mechanical strength is insufficient, so it is not preferred. On the other hand, if it exceeds 5 mol%, the overall structure is easy to deviate from the co-continuous structure, so it is not preferred. In particular, when the total pore volume is 16 to 20 ml / g, in order to form a co-continuous structure, the cross-linked structural unit is preferably less than 3 mol%.

[0165] In step I of the fourth overall manufacturing method, the type of polymer material of the overall intermediate (4) is the same as the type of polymer material of the overall intermediate (4) of the third overall manufacturing method, and its description is omitted.

[0166] The total pore volume per unit weight of the monolithic intermediate (4) obtained in step I of the manufacturing method of the fourth monolith in a dry state exceeds 16 ml / g and is 30 ml / g or less, preferably exceeds 16 ml / g and is 25 ml / g or less. That is, the monolithic intermediate (4) is basically a continuous macroporous structure, but the overlapping part of the macropores, that is, the opening (mesopore) is particularly large, so the skeleton constituting the monolithic structure has a structure that is infinitely close to a one-dimensional rod-like skeleton from a two-dimensional wall surface. Figure 7 The SEM photograph of the morphological example of the integral intermediate (4) is shown, but it has a skeleton close to a rod shape. If it is made to coexist with the polymerization system, a porous body with a co-continuous structure is formed using the structure of the integral intermediate (4) as a mold. If the total pore volume is too small, the overall structure obtained after the polymerization of the vinyl monomer changes from a co-continuous structure to a continuous macroporous structure, so it is not preferred. On the other hand, if the total pore volume is too large, the overall mechanical strength obtained after the polymerization of the vinyl monomer is reduced, or when the ion exchange group is introduced, the ion exchange capacity per unit volume is reduced, so it is not preferred. In order to make the total pore volume of the integral intermediate (4) within the above range, it is sufficient to make the ratio of monomer to water approximately 1:20 to 1:40.

[0167] In addition, the overall intermediate (4) obtained in step I of the manufacturing method of the fourth overall body has an average diameter of the overlapping portion of the macropores, i.e., the opening (mesopore) is 5 to 100 μm in a dry state. If the average diameter of the opening is less than 5 μm in a dry state, the overall opening diameter obtained after the polymerization of the vinyl monomer becomes smaller, and the pressure loss during fluid permeation becomes larger, so it is not preferred. On the other hand, if it exceeds 100 μm, the overall opening diameter obtained after the polymerization of the vinyl monomer becomes too large, and the contact between the reaction liquid and the overall ion exchanger becomes insufficient, resulting in a decrease in catalytic activity, so it is not preferred. The overall intermediate (4) preferably has a uniform structure in which the size of the macropores and the diameter of the openings are consistent, but it is not limited to this. Non-uniform macropores larger than the uniform macropore size may be dispersed in the uniform structure.

[0168] The step II involved in the fourth overall manufacturing method is a step of preparing a mixture containing an aromatic vinyl monomer, a cross-linking agent having at least two vinyl groups in one molecule in an amount of 0.3 to 5 mol% relative to the total oil-soluble monomers, an organic solvent, and a polymerization initiator, wherein the organic solvent is an organic solvent in which the aromatic vinyl monomer and the cross-linking agent are dissolved but the polymer generated by polymerization of the aromatic vinyl monomer is not dissolved. In addition, there is no order between the steps I and II, and the step II may be performed after the step I, or the step I may be performed after the step II.

[0169] The aromatic vinyl monomer used in step II of the manufacturing method of the fourth whole is not particularly limited as long as it is a lipophilic aromatic vinyl monomer containing a polymerizable vinyl group in the molecule and having high solubility in organic solvents. It is preferred to select a vinyl monomer of the same type or similar to the whole intermediate (4) coexisting in the above-mentioned polymerization system to generate a polymer material. Specific examples of these vinyl monomers include styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, vinylbiphenyl, vinylnaphthalene, etc. These monomers can be used alone or in combination of two or more. The preferred aromatic vinyl monomers are styrene, vinylbenzyl chloride, etc.

[0170] The amount of the aromatic vinyl monomer used in the step II of the fourth overall manufacturing method is 5 to 50 times, preferably 5 to 40 times, by weight relative to the overall intermediate (4) coexisting during polymerization. If the amount of the aromatic vinyl monomer added is less than 5 times relative to the overall intermediate (4), the rod-shaped skeleton cannot be thickened. In addition, when the ion exchange group is introduced, the ion exchange capacity per unit volume after the ion exchange group is introduced becomes smaller, so it is not preferred. On the other hand, if the amount of the aromatic vinyl monomer added exceeds 50 times, the diameter of the continuous pore becomes smaller, and the pressure loss during the liquid flow becomes larger, so it is not preferred.

[0171] The cross-linking agent used in the II process involved in the manufacturing method of the fourth whole is preferably used: a cross-linking agent with high solubility in an organic solvent and containing at least two vinyl groups that can be polymerized in the molecule. As specific examples of cross-linking agents, divinylbenzene, divinylnaphthalene, divinylbiphenyl, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, butanediol diacrylate, etc. can be cited. These cross-linking agents can be used alone or in combination of two or more. From the height of mechanical strength and stability to hydrolysis, the preferred cross-linking agent is an aromatic polyvinyl compound such as divinylbenzene, divinylnaphthalene, and divinylbiphenyl. The amount of cross-linking agent used is 0.3 to 5 mol% relative to the total amount of vinyl monomer and cross-linking agent (all oil-soluble monomers), especially 0.3 to 3 mol%. If the amount of cross-linking agent used is less than 0.3 mol%, the overall mechanical strength is insufficient, so it is not preferred. On the other hand, if it is too much, when introducing ion exchange groups, the quantitative introduction of ion exchange groups sometimes becomes difficult, so it is not preferred. It should be noted that the amount of the crosslinking agent used is preferably used in a manner that is substantially equal to the crosslinking density of the overall intermediate (4) coexisting during the polymerization of the vinyl monomer / crosslinking agent. If the difference between the amounts used of the two is too large, uneven crosslinking density distribution will occur in the resulting overall structure, and in addition, when an ion exchange group is introduced, cracks are likely to occur during the ion exchange group introduction reaction.

[0172] The organic solvent used in step II of the fourth overall manufacturing method is an organic solvent that dissolves the aromatic vinyl monomer and the crosslinking agent but does not dissolve the polymer generated by the polymerization of the aromatic vinyl monomer. In other words, it is a poor solvent for the polymer generated by the polymerization of the aromatic vinyl monomer. The organic solvent varies significantly depending on the type of the aromatic vinyl monomer, so it is difficult to list general specific examples. For example, when the aromatic vinyl monomer is styrene, the organic solvent includes alcohols such as methanol, ethanol, propanol, butanol, hexanol, cyclohexanol, octanol, 2-ethylhexanol, decanol, dodecanol, propylene glycol, and tetramethylene glycol; chain (poly) ethers such as diethyl ether, butyl cellosolve, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; chain saturated hydrocarbons such as hexane, heptane, octane, isooctane, decane, and dodecane; esters such as ethyl acetate, isopropyl acetate, cellosolve acetate, and ethyl propionate. In addition, even if it is a good solvent for polystyrene such as dioxane, THF, toluene, it can also be used as an organic solvent when used together with the above-mentioned poor solvent and its usage amount is small. The usage amount of these organic solvents is preferably used in a manner such that the concentration of the above-mentioned aromatic vinyl monomer becomes 30 to 80 weight %. If the usage amount of the organic solvent deviates from the above-mentioned range and makes the aromatic vinyl monomer concentration less than 30 weight %, the polymerization rate decreases, or the overall structure after polymerization deviates from the scope of the fourth overall structure, so it is not preferred. On the other hand, if the aromatic vinyl monomer concentration exceeds 80 weight %, the polymerization is likely to be out of control, so it is not preferred.

[0173] The polymerization initiator used in step II of the fourth overall production method is the same as the polymerization initiator used in step II of the third overall production method, and the description thereof is omitted.

[0174] The process III involved in the method for manufacturing the fourth integral body is: polymerizing the mixture obtained in the process II under standing and in the presence of the integral intermediate (4) obtained in the process I, so that the continuous macroporous structure of the integral intermediate (4) changes to a co-continuous structure, thereby obtaining a co-continuous structure integral body, i.e., the fourth integral body. The integral intermediate (4) used in the process III plays a very important role in manufacturing the integral body having the novel structure of the present invention. As disclosed in Japanese Patent Publication No. 7-501140, if a vinyl monomer and a cross-linking agent are allowed to stand and polymerize in a specific organic solvent in the absence of the integral intermediate (4), a particle agglomerate-type integral organic porous body can be obtained. In contrast, if a specific continuous macroporous structure integral intermediate (4) is present in the above-mentioned polymerization system as in the fourth integral body, the structure of the entire body after polymerization changes drastically, the particle agglomerate structure disappears, and the fourth integral body having the above-mentioned co-continuous structure is obtained. Although the reason is not explained in detail, it is believed that in the absence of the overall intermediate (4), the cross-linked polymer produced by polymerization is precipitated and deposited in particles, thereby forming a particle agglomeration structure. In contrast, if a porous body (intermediate) with a large total pore volume exists in the polymerization system, the vinyl monomer and the cross-linking agent are adsorbed or distributed from the liquid phase to the skeleton of the porous body, and polymerization is carried out in the porous body. The skeleton constituting the overall structure changes from a two-dimensional wall surface to a one-dimensional rod-shaped skeleton, thereby forming a fourth whole having a co-continuous structure.

[0175] In the fourth overall manufacturing method, the internal volume of the reaction container is the same as the description of the internal volume of the reaction container according to the third overall manufacturing method, and the description thereof is omitted.

[0176] In step III of the method for manufacturing the fourth integral body, the integral intermediate (4) is placed in a reaction container in a state of being impregnated with a mixture (solution). The mixing ratio of the mixture obtained in step II to the integral intermediate (4) is as described above, and the amount of the aromatic vinyl monomer added is 5 to 50 times, preferably 5 to 40 times by weight relative to the integral intermediate (4). Thus, a fourth integral body having a co-continuous structure in which pores of appropriate size are three-dimensionally continuous and a coarse skeleton is three-dimensionally continuous can be obtained. In the reaction container, the aromatic vinyl monomer and the cross-linking agent in the mixture are adsorbed and distributed on the skeleton of the stationary integral intermediate (4), and polymerization is carried out within the skeleton of the integral intermediate (4).

[0177] The polymerization conditions of the step III of the fourth overall production method are the same as those described in the step III of the third overall production method, and the description thereof is omitted. The fourth overall production method is obtained by performing the step III.

[0178] The fourth bulk ion exchanger is obtained by performing the following step IV, wherein ion exchange groups are introduced into the fourth bulk obtained in step III.

[0179] The method for introducing ion exchange groups into the fourth entity is the same as the method for introducing ion exchange groups into the first entity.

[0180] The fourth integral body and the fourth integral ion exchanger have a large three-dimensional continuous pore size, but have a coarse skeleton, so they have high mechanical strength. In addition, the coarse skeleton of the fourth integral ion exchanger can increase the ion exchange capacity per unit volume in a dry state, and can allow the reaction solution to pass through for a long time under low pressure and high flow conditions.

[0181] <Description of the fifth entity and the fifth entity ion exchanger>

[0182] In the platinum group metal loaded catalyst of the present invention, the 5th integral ion exchanger which serves as a carrier of the platinum group metal particles is a composite structure of an organic porous body and a plurality of granular bodies or a plurality of protrusions, wherein the average diameter of the pores in a dry state is 10 to 200 μm, the total pore volume in a dry state is 0.5 to 10 ml / g, the ion exchange group is an integral ion exchanger having an ion exchange capacity per unit weight in a dry state of 1 to 9 mg equivalent / g, and the ion exchange groups are uniformly distributed in the organic porous ion exchanger; the above-mentioned organic porous body comprises a continuous skeleton phase and a continuous pore phase, the above-mentioned plurality of granular bodies are a plurality of granular bodies having a diameter of 4 to 40 μm in a dry state fixed to the skeleton surface of the organic porous body, and the above-mentioned plurality of protrusions are a plurality of protrusions having a size of 4 to 40 μm in a dry state formed on the skeleton surface of the organic porous body. In addition, the 5th whole is the whole before the introduction of ion exchange groups, which is a composite structure of an organic porous body and a plurality of granules or a plurality of protrusions. It is an organic porous body having an average pore diameter of 10 to 200 μm in a dry state and a total pore volume of 0.5 to 10 ml / g in a dry state; the above-mentioned organic porous body comprises a continuous skeleton phase and a continuous porous phase, the above-mentioned plurality of granules are a plurality of granules having a diameter of 4 to 40 μm in a dry state which are fixed to the skeleton surface of the organic porous body, and the above-mentioned plurality of protrusions are a plurality of protrusions having a size of 4 to 40 μm in a dry state which are formed on the skeleton surface of the organic porous body.

[0183] The fifth integral ion exchanger is a composite structure of an organic porous body and a plurality of granular bodies or a plurality of protrusions, wherein the organic porous body comprises a continuous skeleton phase and a continuous pore phase, the plurality of granular bodies are a plurality of granular bodies having a diameter of 4 to 40 μm in a dry state fixed to the skeleton surface of the organic porous body, and the plurality of protrusions are a plurality of protrusions having a size of 4 to 40 μm in a dry state formed on the skeleton surface of the organic porous body. It should be noted that in this specification, "granular bodies" and "protrusions" are collectively referred to as "granular bodies, etc."

[0184] The continuous skeleton phase and continuous pore phase of the fifth integral ion exchanger can be observed by SEM images. As the basic structure of the fifth integral ion exchanger, a continuous macroporous structure and a co-continuous structure can be cited. The skeleton phase of the fifth integral ion exchanger is a columnar continuum, a concave wall continuum, or a composite thereof, which is a shape that is clearly different from a granular shape or a protrusion shape.

[0185] As preferred structures of the fifth integral ion exchanger, there can be cited a continuous macroporous structure in which bubble-shaped macropores overlap each other, and the overlapping portion becomes an opening with an average diameter of 10 to 120 μm in a dry state (hereinafter, also referred to as the "fifth-first integral ion exchanger"), and a co-continuous structure including a three-dimensional continuous skeleton with an average thickness of 0.8 to 40 μm in a dry state and three-dimensional continuous pores with an average diameter of 8 to 80 μm in a dry state between the skeletons (hereinafter, also referred to as the "fifth-second integral ion exchanger"). In addition, as the fifth integral, among the fifth-first integral ion exchanger, the integral before the introduction of ion exchange groups (hereinafter, also referred to as the "fifth-first integral") and the fifth-second integral ion exchanger, the integral before the introduction of ion exchange groups (hereinafter, also referred to as the "fifth-second integral") is preferred.

[0186] In the case of the 5-1 integral ion exchanger, the 5-1 integral ion exchanger is a continuous macroporous structure in which bubble-shaped macropores overlap each other, and the overlapping portion forms an opening (mesopore) with an average diameter of 20 to 150 μm, preferably 30 to 150 μm, and particularly preferably 35 to 150 μm in a dry state, and the inside of the bubble formed by the macropore and the opening (mesopore) forms a flow path. The continuous macroporous structure is preferably a uniform structure in which the size of the macropores and the diameter of the openings are consistent, but it is not limited to this, and non-uniform macropores larger than the uniform macropore size may be dispersed in the uniform structure. If the average diameter of the openings in the dry state of the 5-1 integral ion exchanger is less than 20 μm, the pressure loss during the passage of the liquid becomes large, so it is not preferred. In addition, if the average diameter of the openings in the dry state exceeds 150 μm, the contact between the reaction liquid and the integral ion exchanger and the supported platinum group metal particles becomes insufficient, and as a result, the catalytic activity is reduced, so it is not preferred.

[0187] It should be noted that the average diameter of the openings of the 5th whole in a dry state, the average diameter of the openings of the 5th whole ion exchanger in a dry state, and the average diameter of the openings of the dry whole intermediate (5) obtained in the I step of manufacturing the 5th whole described below refer to: the maximum value of the pore distribution curve obtained by the mercury penetration method.

[0188] In the case of the 5-2 integral ion exchanger, the 5-2 integral ion exchanger is a co-continuous structure having a three-dimensional continuous skeleton and three-dimensional continuous pores, wherein the skeleton is a three-dimensional continuous skeleton having an average thickness of 1 to 50 μm, preferably 5 to 50 μm, in a dry state, and the pores are three-dimensional continuous pores having an average diameter of 10 to 100 μm, preferably 10 to 90 μm, in a dry state between the skeletons. If the average diameter of the three-dimensional continuous pores of the 5-2 integral ion exchanger in a dry state is less than 10 μm, the pressure loss during liquid flow increases, which is not preferred. In addition, if it exceeds 100 μm, the contact between the reaction liquid and the integral ion exchanger and the supported platinum group metal particles becomes insufficient, resulting in a decrease in catalytic activity, which is not preferred. In addition, if the average thickness of the skeleton of the 5-2 integral ion exchanger is less than 1 μm in a dry state, the mechanical strength decreases, and the integral ion exchanger is greatly deformed, especially when liquid is passed at a high flow rate, which is not preferred. On the other hand, if the average thickness of the skeleton of the 5-2 bulk ion exchanger exceeds 50 μm in a dry state, the skeleton becomes too thick and the pressure loss during the passage of liquid increases, which is not preferable.

[0189] The average roughness of the skeleton of the 5-2 integral ion exchanger in a dry state is obtained by SEM observation of the 5-2 integral ion exchanger in a dry state. Specifically, the SEM observation of the 5-2 integral ion exchanger in a dry state is performed at least 3 times, the roughness of the skeleton in the obtained image is measured, and the average value thereof is set as the average roughness. It should be noted that the skeleton is rod-shaped and has a circular cross-sectional shape, but it can also include skeletons with different diameter cross-sections such as an elliptical cross-sectional shape. The roughness at this time is the average of the short diameter and the long diameter.

[0190] The average diameter of the pores of the 5th integral ion exchanger in a dry state is 10 to 200 μm. In the case of the 5-1st integral ion exchanger, the preferred value of the pore diameter of the 5-1st integral ion exchanger in a dry state is 30 to 150 μm, and in the case of the 5-2nd integral ion exchanger, the preferred value of the pore diameter of the 5-2nd integral ion exchanger in a dry state is 10 to 90 μm.

[0191] In the fifth integral ion exchanger, the diameter of the granules and the size of the protrusions in the dry state are 4 to 40 μm, preferably 4 to 30 μm, and particularly preferably 4 to 20 μm. It should be noted that in the present invention, both the granules and the protrusions are observed as protrusions on the surface of the skeleton, and the material observed as granules is referred to as granules, and the protrusions that cannot be said to be granules are referred to as protrusions. Figure 8 Schematic cross-sectional view of a protrusion. Figure 8As shown in (A) to (E) in the figure, the protrusion-like substances protruding from the skeleton surface 21 are protrusions 22. Examples of the protrusions 22 include protrusions with a shape close to granules such as the protrusion 22a shown in (A), hemispherical protrusions such as the protrusion 22b shown in (B), and protrusions protruding on the skeleton surface such as the protrusion 22c shown in (C). In addition, the protrusions 22 also include protrusions with a shape that is longer in a direction perpendicular to the skeleton surface 21 than in the planar direction of the skeleton surface 21 such as the protrusion 22d shown in (D), and protrusions with a shape that protrudes in multiple directions such as the protrusion 22e shown in (E). In addition, the size of the protrusion refers to the length of the widest part in the SEM image of each protrusion, as determined by the SEM image during SEM observation. In addition, Fig. 9 The SEM photograph showing the fifth example of the morphology of the monolithic ion exchanger shows that a large number of protrusions are formed on the surface of the skeleton of the organic porous body.

[0192] In the fifth integral ion exchanger, the proportion of particles of 4 to 40 μm in the dry state in all particles is 70% or more, preferably 80% or more. It should be noted that the proportion of particles of 4 to 40 μm in the dry state in all particles refers to the proportion of the number of particles of 4 to 40 μm in the dry state in the total number of particles. In addition, the surface of the skeleton phase is covered by all particles by more than 40%, preferably more than 50%. It should be noted that the proportion of the surface of the skeleton layer covered by all particles refers to the area ratio on the SEM image when the surface is observed by SEM, that is, the area ratio when the surface is viewed from above. If the size of the particles covering the wall and the skeleton is out of the above range, the effect of improving the contact efficiency between the fluid and the skeleton surface and the inside of the skeleton of the integral ion exchanger is likely to be reduced. It should be noted that all particles refer to all particles and protrusions in the size range other than particles of 4 to 40 μm in the dry state, and all particles and protrusions formed on the surface of the skeleton layer.

[0193] The diameter or size of the particles attached to the surface of the skeleton of the fifth integral ion exchanger in a dry state is the diameter or size of the particles obtained by observing the SEM image of the fifth integral ion exchanger in a dry state. Then, the diameter or size of all the particles observed in the SEM image of the fifth integral ion exchanger in a dry state is measured, and the diameter or size of all the particles in the SEM image of one field of view in a dry state is calculated based on the value. The SEM observation of the fifth integral ion exchanger in a dry state is performed at least three times, and the diameter or size of all the particles in the SEM image in a dry state is calculated in all fields of view to confirm whether particles with a diameter or size of 4 to 40 μm are observed. If they are confirmed in all fields of view, it is judged that particles with a diameter or size of 4 to 40 μm in a dry state are formed on the surface of the skeleton of the fifth integral ion exchanger. Furthermore, according to the above contents, the diameter or size of all the granules, etc. in the SEM image in the dry state is calculated for each field of view, and the proportion of granules, etc. of 4 to 40 μm in the dry state among all the granules, etc. is calculated for each field of view. When the proportion of granules, etc. of 4 to 40 μm in the dry state among all the granules, etc. in the whole field of view is 70% or more, it is determined that the proportion of granules, etc. of 4 to 40 μm in the dry state among all the granules, etc. formed on the surface of the skeleton of the fifth monolithic ion exchanger is 70% or more. Furthermore, according to the above contents, the proportion of the surface of the skeleton layer covered by all the granules, etc. in the SEM image is calculated for each field of view. When the proportion of the surface of the skeleton layer covered by all the granules, etc. in the whole field of view is 40% or more, it is determined that the proportion of the surface of the skeleton layer of the fifth monolithic ion exchanger covered by all the granules, etc. is 40% or more.

[0194] In the fifth integral ion exchanger, if the coverage of the skeleton phase surface by the granules is less than 40%, the effect of improving the contact efficiency between the reaction solution and the skeleton interior and the skeleton surface of the integral ion exchanger is likely to be reduced. As a method for measuring the coverage by the granules, an image analysis method based on a SEM image of the fifth integral ion exchanger can be cited.

[0195] The total pore volume per unit weight of the 5th integral ion exchanger in a dry state is 0.5 to 10 ml / g, preferably 0.8 to 8 ml / g. If the total pore volume of the integral ion exchanger is less than 0.5 ml / g, the pressure loss during liquid flow becomes large, so it is not preferred. In addition, the amount of fluid passing through per unit cross-sectional area becomes small, and the processing capacity is reduced, so it is not preferred. On the other hand, if the total pore volume of the integral ion exchanger exceeds 10 ml / g, the mechanical strength is reduced, especially when the liquid is passed at a high flow rate, the integral ion exchanger is greatly deformed, so it is not preferred. In addition, the contact efficiency between the reaction liquid and the integral ion exchanger and the platinum group metal particles loaded thereon is reduced, so the catalytic effect is also reduced, so it is not preferred.

[0196] In the fifth integral ion exchanger, the material constituting the skeleton phase of the continuous pore structure is an organic polymer material having a cross-linked structure. The cross-linking density of the polymer material is not particularly limited, and it contains 0.3 to 10 mol%, preferably 0.3 to 5 mol% of cross-linked structural units relative to all structural units constituting the polymer material. If the cross-linked structural unit is less than 0.3 mol%, the mechanical strength is insufficient, so it is not preferred. On the other hand, if it exceeds 10 mol%, when the ion exchange group is introduced, the introduction of the ion exchange group becomes difficult, and sometimes the amount of introduction is reduced, so it is not preferred.

[0197] The types of polymer materials used in the manufacture of the fifth whole are not particularly limited. For example, aromatic vinyl polymers such as polystyrene, poly(α-methylstyrene), polyvinyltoluene, polyvinylbenzyl chloride, polyvinylbiphenyl, and polyvinylnaphthalene can be cited; polyolefins such as polyethylene and polypropylene; poly(halogenated polyolefins) such as polyvinyl chloride and polytetrafluoroethylene; nitrile polymers such as polyacrylonitrile; cross-linked polymers such as (meth)acrylic polymers such as polymethyl methacrylate, polyglycidyl methacrylate, and polyethyl acrylate. The above polymers can be polymers obtained by copolymerizing a single vinyl monomer and a cross-linking agent, or polymers obtained by polymerizing a plurality of vinyl monomers and a cross-linking agent, or materials obtained by blending two or more polymers. Among these organic polymer materials, cross-linked polymers of aromatic vinyl polymers are preferred, based on the ease of forming a continuous pore structure, the ease of introducing ion exchange groups, the high mechanical strength, and the high stability to acids and alkalis. In particular, styrene-divinylbenzene copolymers and vinylbenzyl chloride-divinylbenzene copolymers are cited as preferred materials.

[0198] In the fifth integral ion exchanger, the material constituting the skeleton phase of the organic porous body and the granules formed on the surface of the skeleton phase may include materials of the same material with the same continuous structure, materials of different materials with different continuous structures, etc. As materials of different continuous structures with different continuous structures, there may be materials of different types of vinyl monomers, materials of the same types of vinyl monomers and cross-linking agents but with different proportions, etc.

[0199] The ion exchange groups introduced into the fifth bulk ion exchanger are the same as the ion exchange groups introduced into the first bulk ion exchanger.

[0200] In the fifth integral ion exchanger, the introduced ion exchange groups are uniformly distributed not only on the surface of the organic porous body but also inside the skeleton of the organic porous body. If the ion exchange groups are uniformly distributed not only on the fifth integral ion exchanger but also inside the skeleton, the physical and chemical properties of the surface and the inside can be made uniform, thereby improving the durability against swelling and shrinkage.

[0201] The fifth integral ion exchanger has an ion exchange capacity of 1 to 9 mg equivalent / g per unit weight in a dry state. By making the ion exchange capacity per unit weight of the fifth integral ion exchanger within the above range, the environment surrounding the catalytic active point such as the pH inside the catalyst can be changed, thereby increasing the catalytic activity. In the case where the fifth integral ion exchanger is an integral anion exchanger, an anion exchange group is introduced into the fifth integral anion exchanger, and the anion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, preferably 1 to 8 mg equivalent / g, and particularly preferably 1 to 7 mg equivalent / g. In addition, in the case where the fifth integral ion exchanger is an integral cation exchanger, a cation exchange group is introduced into the fifth integral cation exchanger, and the cation exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g, preferably 1 to 7 mg equivalent / g.

[0202] The thickness of the fifth integral ion exchanger is 1 mm or more, which is different from a film-like porous body. If the thickness is less than 1 mm, the ion exchange capacity of each porous body is extremely reduced, so it is not preferred. The thickness of the fifth integral ion exchanger is preferably 3 to 1000 mm. In addition, the basic structure of the skeleton of the fifth integral ion exchanger is a continuous pore structure, so the mechanical strength is high.

[0203] <Fifth integral body and method for producing fifth integral body ion exchanger>

[0204] The fifth entity is obtained by carrying out the following steps: step I, wherein a water-in-oil emulsion is prepared by stirring a mixture of an oil-soluble monomer not containing an ion exchange group, a surfactant and water, and then the water-in-oil emulsion is polymerized to obtain an integral organic porous intermediate having a continuous macroporous structure with a total pore volume of 5 to 30 ml / g (hereinafter also referred to as the integral intermediate (5)); step II, wherein a mixture comprising a vinyl monomer, a cross-linking agent having at least two vinyl groups in one molecule, an organic solvent and a polymerization initiator is prepared; the organic solvent is an organic solvent in which the vinyl monomer and the cross-linking agent are dissolved but the polymer generated by the polymerization of the vinyl monomer is not dissolved; and step III, wherein the mixture obtained in step II is polymerized while standing and in the presence of the integral intermediate (5) obtained in step I to obtain a composite entity having a composite structure, namely the fifth entity.

[0205] The step I involved in the fifth overall manufacturing method may be performed according to the method described in Japanese Patent Application Laid-Open No. 2002-306976.

[0206] In the manufacture of the overall intermediate (5) of step I involved in the manufacturing method of the fifth overall, as an oil-soluble monomer that does not contain an ion exchange group, for example, an oleophilic monomer that does not contain an ion exchange group such as a carboxylic acid group, a sulfonic acid group, a tertiary amino group, a quaternary ammonium group, and has low solubility in water can be cited. As preferred monomers of these monomers, styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, divinylbenzene, ethylene, propylene, isobutylene, butadiene, ethylene glycol dimethacrylate, etc. can be cited. These monomers can be used alone or in combination of two or more. Among them, cross-linking monomers such as divinylbenzene and ethylene glycol dimethacrylate are selected as at least one component of the oil-soluble monomer, and their content is 0.3 to 10 mol% relative to all oil-soluble monomers, preferably 0.3 to 5 mol%, and when the ion exchange group is introduced in the subsequent process, the amount of ion exchange group can be quantitatively introduced, so it is preferred.

[0207] The surfactant used in the step I of the manufacturing method of the fifth whole is not particularly limited as long as it forms an oil-in-water (W / O) emulsion when mixing an oil-soluble monomer not containing an ion exchange group with water. Nonionic surfactants such as sorbitan monooleate, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan trioleate, polyoxyethylene nonylphenyl ether, polyoxyethylene stearyl ether, polyoxyethylene sorbitan monooleate, etc.; anionic surfactants such as potassium oleate, sodium dodecylbenzenesulfonate, sodium sulfosuccinate dioctyl ester; cationic surfactants such as distearyl dimethyl ammonium chloride; amphoteric surfactants such as lauryl dimethyl betaine. These surfactants can be used alone or in combination of two or more. It should be noted that the water-in-oil emulsion refers to an emulsion in which the oil phase is a continuous phase and water droplets are dispersed therein. The amount of the surfactant to be added varies greatly depending on the type of oil-soluble monomer and the size of the target emulsion particles (macropores), and therefore cannot be generalized, but can be selected within the range of about 2 to 70% relative to the total amount of the oil-soluble monomer and the surfactant.

[0208] In addition, in the step I involved in the manufacturing method of the fifth overall, when forming an oil-in-water emulsion, a polymerization initiator can be used as needed. The polymerization initiator preferably uses a compound that generates free radicals by heat or light irradiation. The polymerization initiator can be water-soluble or oil-soluble, and for example, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(dimethyl isobutyrate), 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexane-1-carbonitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, ammonium persulfate, hydrogen peroxide-ferrous chloride, sodium persulfate-acidic sodium sulfite, etc. can be cited.

[0209] In the 1st process involved in the manufacturing method of the 5th whole, as the mixing method when mixing the oil-soluble monomer, surfactant, water and polymerization initiator which do not contain ion exchange groups to form the water-in-oil type emulsion, there is no particular restriction, and the method of mixing all the components at once can be used, and the method of mixing the respective components after the oil-soluble monomer, surfactant and oil-soluble polymerization initiator, i.e. the oil-soluble component and water, water-soluble polymerization initiator, i.e. the water-soluble component are uniformly dissolved respectively. There is no particular restriction on the mixing device for forming the emulsion, and a common mixer, homogenizer, high-pressure homogenizer, etc. can be used, and the device suitable for obtaining the target emulsion particle size can be selected. In addition, the mixing conditions are not particularly limited, and the stirring speed and stirring time that can obtain the target emulsion particle size can be arbitrarily set.

[0210] The overall intermediate (5) obtained in step I of the manufacturing method of the fifth whole has a continuous macroporous structure. If it is made to coexist with a polymerization system, the structure of the overall intermediate (5) is used as a casting mold to form granules on the surface of the skeleton phase of the continuous macroporous structure, or to form granules on the surface of the skeleton phase of the co-continuous structure. In addition, the overall intermediate (5) is an organic polymer material with a cross-linked structure. The cross-linking density of the polymer material is not particularly limited, and it contains 0.3 to 10 mol%, preferably 0.3 to 5 mol% of cross-linked structural units relative to all structural units constituting the polymer material. If the cross-linked structural unit is less than 0.3 mol%, the mechanical strength is insufficient, so it is not preferred. On the other hand, if it exceeds 10 mol%, the softness of the porous body is lost. In addition, when an ion exchange group is introduced, it is sometimes difficult to introduce an ion exchange group, so it is not preferred.

[0211] In step I of the method for producing the fifth whole, the type of polymer material of the whole intermediate (5) is not particularly limited, and the same polymer material as that of the aforementioned whole 5 can be used. Thus, the same polymer can be formed on the skeleton of the whole intermediate (5) to obtain a whole of a composite structure, i.e., the fifth whole.

[0212] The total pore volume per unit weight of the overall intermediate (5) obtained in step I of the manufacturing method of the fifth overall body in a dry state is 5 to 30 ml / g, preferably 6 to 28 ml / g. If the total pore volume of the overall intermediate is too small, the total pore volume of the overall body obtained after polymerization of the vinyl monomer becomes too small, and the pressure loss during fluid permeation becomes large, so it is not preferred. On the other hand, if the total pore volume of the overall intermediate is too large, the overall structure obtained after polymerization of the vinyl monomer tends to become uneven, and sometimes causes structural collapse, so it is not preferred. When the total pore volume of the overall intermediate (5) is set to the above-mentioned numerical range, the ratio (weight) of the monomer to water can be approximately 1:5 to 1:35.

[0213] In the step I of the method for producing the fifth whole, if the ratio of the monomer to water is set to approximately 1:5 to 1:20, a whole having a continuous macroporous structure with a total pore volume of 5 to 16 ml / g of the whole intermediate (5) can be obtained, and the whole obtained through the step III is the fifth whole. In addition, if the mixing ratio is set to approximately 1:20 to 1:35, a whole having a continuous macroporous structure with a total pore volume of more than 16 ml / g and less than 30 ml / g of the whole intermediate (5) can be obtained, and the whole obtained through the step III is the fifth whole.

[0214] In addition, the overall intermediate (5) obtained in step I of the manufacturing method of the fifth overall body has an average diameter of the overlapping portion of the macropores, i.e., the openings (mesopores) in the dry state of 20 to 200 μm. If the average diameter of the openings in the overall intermediate in the dry state is less than 20 μm, the overall opening diameter obtained after the polymerization of the vinyl monomer becomes smaller, and the pressure loss during the liquid flow becomes larger, so it is not preferred. On the other hand, if the average diameter of the openings in the overall intermediate in the dry state exceeds 200 μm, the overall opening diameter obtained after the polymerization of the vinyl monomer becomes too large, and the contact between the reaction liquid and the overall ion exchanger becomes insufficient, resulting in a decrease in catalytic activity, so it is not preferred. The overall intermediate (5) preferably has a uniform structure in which the size of the macropores and the diameter of the openings are consistent, but it is not limited to this. It is also possible to disperse uneven macropores larger than the uniform macropore size in the uniform structure.

[0215] The step II involved in the fifth overall manufacturing method is a step of preparing a mixture containing a vinyl monomer, a second cross-linking agent having at least two vinyl groups in one molecule, an organic solvent, and a polymerization initiator; the organic solvent is an organic solvent in which the vinyl monomer and the second cross-linking agent are dissolved but the polymer generated by polymerization of the vinyl monomer is not dissolved. It should be noted that there is no order between the steps I and II, and the step II may be performed after the step I, or the step I may be performed after the step II.

[0216] As the vinyl monomer used in the II step involved in the manufacturing method of the fifth whole, there is no particular restriction as long as it is a lipophilic vinyl monomer with high solubility in organic solvents and contains a vinyl group that can be polymerized in the molecule. As specific examples of these vinyl monomers, there can be cited aromatic vinyl monomers such as styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, vinylbiphenyl, and vinylnaphthalene; α-olefins such as ethylene, propylene, 1-butene, and isobutylene; diene monomers such as butadiene, isoprene, and chloroprene; halogenated olefins such as vinyl chloride, vinyl bromide, vinylidene chloride, and tetrafluoroethylene; nitrile monomers such as acrylonitrile and methacrylonitrile; vinyl esters such as vinyl acetate and vinyl propionate; (meth) acrylic acid monomers such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, and glycidyl methacrylate. These monomers can be used alone or in combination of two or more. The vinyl monomer preferably used is an aromatic vinyl monomer such as styrene and vinylbenzyl chloride.

[0217] The amount of the vinyl monomer used in the step II of the manufacturing method of the fifth whole is 3 to 50 times, preferably 4 to 40 times, by weight relative to the whole intermediate (5) coexisting during polymerization. If the amount of the vinyl monomer added is less than 3 times relative to the porous body, it is impossible to form a granular body in the generated whole skeleton. In addition, when the ion exchange group is introduced, the ion exchange capacity per unit volume after the ion exchange group is introduced becomes smaller, so it is not preferred. On the other hand, if the amount of the vinyl monomer added exceeds 50 times, the opening diameter becomes smaller, and the pressure loss during the liquid flow becomes larger, so it is not preferred.

[0218] The cross-linking agent used in the II process involved in the manufacturing method of the 5th whole preferably uses a cross-linking agent containing at least 2 polymerizable vinyl groups in the molecule and having high solubility in an organic solvent. As a specific example of the cross-linking agent, divinylbenzene, divinylnaphthalene, divinylbiphenyl, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, butanediol diacrylate, etc. can be cited. These cross-linking agents can be used alone or in combination of two or more. From the height of mechanical strength and stability to hydrolysis, the preferred cross-linking agent is an aromatic polyvinyl compound such as divinylbenzene, divinylnaphthalene, and divinylbiphenyl. The amount of the cross-linking agent used is preferably 0.3 to 20 mol% relative to the total amount of the vinyl monomer and the cross-linking agent, and is particularly preferably 0.3 to 10 mol%. If the amount of the cross-linking agent used is less than 0.3 mol%, the overall mechanical strength is insufficient, so it is not preferred. On the other hand, if it exceeds 20 mol%, the overall embrittlement occurs and the flexibility is lost. In addition, when an ion exchange group is introduced, the amount of the ion exchange group introduced is sometimes reduced, so it is not preferred.

[0219] The organic solvent used in step II of the fifth overall manufacturing method is an organic solvent that dissolves the vinyl monomer and the crosslinking agent but does not dissolve the polymer generated by the polymerization of the vinyl monomer. In other words, it is a poor solvent for the polymer generated by the polymerization of the vinyl monomer. The organic solvent varies significantly depending on the type of the vinyl monomer, so it is difficult to list general specific examples. For example, when the vinyl monomer is styrene, as an organic solvent, alcohols such as methanol, ethanol, propanol, butanol, hexanol, cyclohexanol, octanol, 2-ethylhexanol, decanol, dodecanol, propylene glycol, and tetramethylene glycol can be cited; chain (poly) ethers such as diethyl ether, butyl cellosolve, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; chain saturated hydrocarbons such as hexane, heptane, octane, isooctane, decane, and dodecane; esters such as ethyl acetate, isopropyl acetate, cellosolve acetate, and ethyl propionate. In addition, even good solvents for polystyrene such as dioxane, THF, and toluene can be used as organic solvents when used together with the above-mentioned poor solvents and in small amounts. The amount of these organic solvents used is preferably used in a manner such that the concentration of the above-mentioned vinyl monomers becomes 5 to 80% by weight. If the amount of the organic solvent used deviates from the above range and the vinyl monomer concentration is less than 5% by weight, the polymerization rate is reduced, so it is not preferred. On the other hand, if the vinyl monomer concentration exceeds 80% by weight, the polymerization may be out of control, so it is not preferred.

[0220] As the polymerization initiator used in step II of the manufacturing method of the fifth whole, it is preferred to use a compound that generates free radicals by heat or light irradiation. The polymerization initiator is preferably oil-soluble. As specific examples of the polymerization initiator, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(dimethyl 2,2'-azobisisobutyrate), 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexane-1-carbonitrile), benzoyl peroxide, lauroyl peroxide, tetramethylthiuram disulfide, etc. can be cited. The amount of the polymerization initiator used varies greatly depending on the type of monomer, polymerization temperature, etc., and can be used in the range of about 0.01 to 5% relative to the total amount of the vinyl monomer and the crosslinking agent.

[0221] The step III involved in the method for producing the fifth whole is a step of polymerizing the mixture obtained in the step II under standing and in the presence of the monolithic intermediate (5) obtained in the step I to obtain the fifth whole. The monolithic intermediate (5) used in the step III plays a very important role in producing the fifth whole. As disclosed in Japanese Unexamined Patent Publication No. 7-501140, if a vinyl monomer and a crosslinking agent are allowed to stand and polymerize in a specific organic solvent in the absence of the monolithic intermediate (5), a particle aggregation type monolithic organic porous body can be obtained. In contrast, if a monolithic intermediate (5) having a continuous macroporous structure is present in the above-mentioned polymerization system as in the present invention, the structure of the composite whole after polymerization changes drastically, and the fifth whole having the above-mentioned specific skeleton structure but not having a particle aggregation structure is obtained. The internal volume of the reaction container is not particularly limited as long as it is a size that allows the monolithic intermediate (5) to exist in the reaction container. When the monolithic intermediate (5) is placed in the reaction container, it can be any of the internal volume that can produce a gap around the whole when viewed from above and the internal volume that the monolithic intermediate (5) can enter without a gap in the reaction container. Among them, the fifth whole after polymerization is not pressed from the inner wall of the container and the internal volume that enters the reaction container without gaps does not cause strain in the fifth whole, and there is no waste of reaction raw materials, etc., which is effective. It should be noted that even if the internal volume of the reaction container is large and there are gaps around the fifth whole after polymerization, the vinyl monomer and the cross-linking agent are adsorbed and distributed in the whole intermediate (5), so that the particle aggregation structure is not generated in the gap part in the reaction container.

[0222] In step III of the method for producing the fifth integral body, the integral intermediate (5) is placed in a reaction container in a state of being impregnated with a mixture (solution). The mixing ratio of the mixture obtained in step II to the integral intermediate (5) is as described above, and the amount of vinyl monomer added is 3 to 50 times, preferably 4 to 40 times by weight relative to the integral intermediate (5). In this way, a composite integral body having a moderate opening diameter and a specific skeleton, namely the fifth integral body, can be obtained. In the reaction container, the vinyl monomer and the crosslinking agent in the mixture are adsorbed and distributed on the skeleton of the integral intermediate (5) after standing, and polymerization is carried out within the skeleton of the integral intermediate (5).

[0223] In the step III involved in the method for producing the fifth integral body, various conditions can be selected for the polymerization conditions depending on the type of monomer and the type of initiator. For example, when 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), benzoyl peroxide, lauroyl peroxide, etc. are used as initiators, the polymerization can be carried out by heating at 20 to 100°C for 1 to 48 hours in a sealed container under an inert atmosphere. By heating the polymerization, the vinyl monomer and the crosslinking agent adsorbed and distributed on the skeleton of the integral intermediate (5) are polymerized in the skeleton to form the specific skeleton structure. After the polymerization is completed, the contents are taken out, and in order to remove the unreacted vinyl monomer and the organic solvent, extraction is performed using a solvent such as acetone to obtain a composite integral body with a specific skeleton structure, i.e., the fifth integral body.

[0224] When manufacturing the above-mentioned fifth integral body, if step II or step III is carried out under the condition that at least one of the following conditions (1) to (5) is satisfied, the characteristic structure of the fifth integral body, i.e., an integral body with granules etc. formed on the skeleton surface, can be manufactured.

[0225] (1) The polymerization temperature in step III is at least 5° C. lower than the 10-hour half-life temperature of the polymerization initiator.

[0226] (2) The mol % of the cross-linking agent used in step II is at least twice the mol % of the cross-linking agent used in step I.

[0227] (3) The vinyl monomer used in step II has a structure different from that of the oil-soluble monomer used in step I.

[0228] (4) The organic solvent used in step II is a polyether having a molecular weight of 200 or more.

[0229] (5) The concentration of the vinyl monomer used in step II is 30% by weight or less in the mixture of step II.

[0230] (Explanation of (1) above)

[0231] The 10-hour half-life temperature is a characteristic value of the polymerization initiator. If the polymerization initiator used is determined, the 10-hour half-life temperature can be known. In addition, if there is a desired 10-hour half-life temperature, the polymerization initiator corresponding to it can be selected. In step III, by lowering the polymerization temperature,

[0232] The polymerization rate is reduced, and particles can be formed on the surface of the skeleton phase. The reason is believed to be that the monomer concentration inside the skeleton phase of the overall intermediate decreases slowly, and the distribution rate of the monomer from the liquid phase to the overall intermediate decreases, so the remaining monomer is concentrated near the surface of the skeleton layer of the overall intermediate, and polymerization is carried out at this time.

[0233] In the step III of the fifth overall manufacturing method, the preferred polymerization temperature is a temperature at least 10°C lower than the 10-hour half-life temperature of the polymerization initiator used. The lower limit of the polymerization temperature is not particularly limited, but the lower the temperature, the lower the polymerization rate, and the longer the polymerization time is to a practically unacceptable degree, so it is preferred to set the polymerization temperature to a range of 5 to 20°C lower than the 10-hour half-life temperature.

[0234] (Explanation of (2) above)

[0235] If the mole % of the crosslinking agent used in the II process involved in the manufacturing method of the 5th whole is set to more than 2 times the mole % of the crosslinking agent used in the I process and polymerization is carried out, a whole with a composite structure can be obtained. It is believed that the reason is that the compatibility of the whole intermediate and the polymer generated by impregnation polymerization is reduced and phase separation is carried out, so the polymer generated by impregnation polymerization is excluded from the surface of the skeleton phase of the whole intermediate, and granules and other concave-convex bodies are formed on the surface of the skeleton phase. It should be noted that the mole % of the crosslinking agent is the crosslinking density mole %, which refers to the crosslinking amount (mole %) relative to the total amount of the vinyl monomer and the crosslinking agent.

[0236] The upper limit of the crosslinking agent mol% used in the II process involved in the manufacturing method of the 5th whole is not particularly limited. If the crosslinking agent mol% becomes significantly larger, cracks will be generated in the whole after polymerization, and the whole will become brittle and lose flexibility. In addition, when the ion exchange group is introduced, the problem of the reduced amount of the ion exchange group introduced sometimes occurs, so it is not preferred. The preferred multiple of the crosslinking agent mol% is 2 times to 10 times. On the other hand, even if the crosslinking agent mol% used in the I process is set to more than 2 times the crosslinking agent mol% used in the II process, it will not cause the formation of particles on the surface of the skeleton phase, and the 5th whole cannot be obtained.

[0237] (Explanation of (3) above)

[0238] If the vinyl monomer used in the II process involved in the manufacturing method of the 5th whole is a vinyl monomer of a structure different from the oil-soluble monomer used in the I process, the 5th whole can be obtained. For example, as styrene and vinylbenzyl chloride, if the structure of the vinyl monomer is slightly different, a composite integral porous body with granules etc. formed on the surface of the skeleton phase is generated. Usually, the two homopolymers obtained by two monomers with slightly different structures are incompatible with each other. Therefore, it is believed that if a monomer of a structure different from the monomer used in the formation of the overall intermediate used in the I process is used in the II process and polymerized in the III process, the monomer used in the II process is evenly distributed or impregnated in the overall intermediate, but if polymerization is carried out to generate a polymer, the generated polymer is not compatible with the overall intermediate, so phase separation is performed, and the generated polymer is excluded near the surface of the skeleton phase of the overall intermediate, and granules etc. are formed on the surface of the skeleton phase.

[0239] (Explanation of (4) above)

[0240] If the organic solvent used in the II process involved in the manufacturing method of the 5th whole is a polyether with a molecular weight of more than 200, the 5th whole can be obtained. The affinity of the polyether to the whole intermediate is high, and especially the low molecular weight cyclic polyether is a good solvent for polystyrene. The low molecular weight chain polyether is not a good solvent, but has considerable affinity. However, if the molecular weight of the polyether becomes large, the affinity with the whole intermediate is sharply reduced, and the whole intermediate hardly shows affinity. If this type of solvent lacking affinity is used for the organic solvent, the diffusion of the whole intermediate of the monomer inside the skeleton is hindered, and as a result, it is believed that the monomer is polymerized only near the surface of the skeleton of the whole intermediate, so particles are formed on the surface of the skeleton phase, and concave and convex are formed on the surface of the skeleton.

[0241] The molecular weight of the polyether used in the step II of the fifth overall manufacturing method is not particularly limited to the upper limit as long as it is 200 or more. If the molecular weight is too high, the viscosity of the mixture prepared in the step II becomes high, and it is difficult to impregnate the entire intermediate body, so it is not preferred. The molecular weight of the polyether is preferably 200 to 100,000, and particularly preferably 200 to 10,000. In addition, the terminal structure of the polyether may be an unmodified hydroxyl group, or may be etherified by an alkyl group such as a methyl group or an ethyl group, or may be esterified by acetic acid, oleic acid, lauric acid, stearic acid, or the like.

[0242] (Explanation of (5) above)

[0243] If the concentration of the vinyl monomer used in step II of the manufacturing method of the fifth whole is less than 30% by weight in the mixture in step II, the fifth whole can be obtained. By reducing the monomer concentration in step II, the polymerization rate is reduced. Based on the same reasons as those in (1) above, particles can be formed on the surface of the skeleton phase, and concavities and convexities can be formed on the surface of the skeleton phase. The lower limit of the monomer concentration is not particularly limited. The lower the monomer concentration, the lower the polymerization rate, and the longer the polymerization time will be to a level that is not practically acceptable. Therefore, the monomer concentration is preferably set to 10 to 30% by weight.

[0244] Preferred structures of the fifth integral body thus obtained include a continuous macroporous structure in which bubble-like macropores overlap with each other, and the overlapping parts become openings with an average diameter of 10 to 120 μm in the dry state ("the fifth-1 integral body"), and a co-continuous structure comprising a three-dimensional continuous skeleton with an average thickness of 0.8 to 40 μm in the dry state and three-dimensional continuous pores with a diameter of 8 to 80 μm in the dry state between the skeletons ("the fifth-2 integral body").

[0245] In the case where the 5th whole is the 5-1 whole, the 5-1 whole is a bubble-like macropore that overlaps each other, and the overlapping portion becomes a continuous macroporous structure with an opening (mesopore) having an average diameter of 10 to 120 μm, preferably 20 to 120 μm, and particularly preferably 25 to 120 μm in a dry state, and the bubbles formed by the macropores and the openings (mesopores) become a flow path. The continuous macroporous structure is preferably a uniform structure in which the size of the macropores and the diameter of the openings are consistent, but it is not limited to this, and non-uniform macropores larger than the uniform macropore size can also be dispersed in the uniform structure. If the average diameter of the openings of the 5-1 whole in a dry state is less than 10 μm, the pressure loss during the liquid flow becomes large, so it is not preferred. In addition, if the average diameter of the openings in a dry state exceeds 120 μm, the contact between the reaction liquid and the whole ion exchanger and the loaded platinum group metal particles becomes insufficient, and as a result, the catalytic activity is reduced, so it is not preferred.

[0246] In the case of the 5-2 whole, the 5-2 whole is a co-continuous structure having a three-dimensional continuous skeleton with an average thickness of 0.8 to 40 μm in a dry state and a three-dimensional continuous pore with an average diameter of 8 to 80 μm in a dry state between the skeletons. If the average diameter of the three-dimensional continuous pores of the 5-2 whole in a dry state is less than 8 μm, the pressure loss during liquid flow becomes large, so it is not preferred. In addition, if it exceeds 80 μm, the contact between the reaction liquid and the whole or the whole ion exchanger and the loaded platinum group metal particles becomes insufficient, and as a result, the catalytic activity decreases, so it is not preferred. In addition, if the average thickness of the skeleton of the 5-2 whole in a dry state is less than 0.8 μm, when the ion exchange group is introduced, the ion exchange capacity per unit volume of the whole ion exchanger is reduced. In addition, the mechanical strength is reduced, especially when the liquid is passed at a high flow rate, the whole or the whole ion exchanger is greatly deformed, so it is not preferred. On the other hand, if the average thickness of the skeleton in a dry state exceeds 80 μm, the pressure loss during liquid flow increases, so it is not preferred.

[0247] The fifth bulk ion exchanger is obtained by performing the following step IV, wherein ion exchange groups are introduced into the fifth bulk obtained in step III.

[0248] The method for introducing ion exchange groups into the fifth entity is the same as the method for introducing ion exchange groups into the first entity.

[0249] The platinum group metal supported catalyst involved in the carbon-carbon bond forming method of the present invention comprises a continuous skeleton phase and a continuous pore phase, the thickness of the continuous skeleton is 1 to 100 μm, the average diameter of the continuous pores is 1 to 1000 μm, the total pore volume is 0.5 to 50 ml / g, and the ion exchange capacity per unit weight in a dry state is 1 to 9 mg equivalent / g. In the above-mentioned non-granular organic porous ion exchanger (the above-mentioned monolithic organic porous ion exchanger) in which ion exchange groups are uniformly distributed in the organic porous ion exchanger, there is a platinum group metal supported catalyst loaded with platinum group metal particles with an average particle size of 1 to 100 nm, and the loading amount of the platinum group metal particles in a dry state is 0.004 to 20 weight %.

[0250] The platinum group metal supported catalyst of the present invention is a platinum group metal supported catalyst in which platinum group metal particles having an average particle size of 1 to 100 nm are supported on any of the above-mentioned monolithic organic porous ion exchangers, for example, the first monolithic ion exchanger to the fifth monolithic ion exchanger.

[0251] Platinum group metals are ruthenium, rhodium, palladium, osmium, iridium, and platinum. These platinum group metals can be used alone or in combination of two or more metals, or in alloys of two or more metals. Among them, platinum, palladium, and platinum / palladium alloys have high catalytic activity and are preferably used.

[0252] The average particle size of the platinum group metal particles supported on the platinum group metal catalyst is 1 to 100 nm, preferably 1 to 50 nm, and more preferably 1 to 20 nm. If the average particle size is less than 1 nm, the possibility of the platinum group metal particles detaching from the carrier becomes high, so it is not preferred. On the other hand, if the average particle size exceeds 100 nm, the surface area per unit mass of the metal becomes small, and the catalytic effect cannot be obtained efficiently, so it is not preferred. It should be noted that in the present invention, the average particle size of the platinum group metal particles is obtained by performing image analysis on the TEM image obtained by transmission electron microscopy (TEM) analysis. Specifically, first, TEM analysis is performed on the surface of the platinum group metal supported catalyst. Then, in the obtained TEM image, a field of view with more than 200 particles is arbitrarily selected, and the TEM image of the field of view is image analyzed to measure the particle size of all particles in the field of view. It should be noted that when the number of platinum group metal particles supported in one field of view is less than 200, two or more fields of view are arbitrarily selected, and the particle size of all particles in the selected two or more fields of view is measured. Next, the average particle size of the platinum group metal particles was calculated by the following formula: "average particle size of platinum group metal particles (nm) = total particle size of all particles measured (nm) / number of particles measured (pieces)".

[0253] The amount of platinum group metal particles loaded in the platinum group metal loaded catalyst ((platinum group metal particles / platinum group metal loaded catalyst in a dry state)×100) is 0.004 to 20% by weight, preferably 0.005 to 15% by weight. If the amount of platinum group metal particles loaded is less than 0.004% by weight, the catalytic activity becomes insufficient, which is not preferred. On the other hand, if the amount of platinum group metal particles loaded exceeds 20% by weight, it is confirmed that the metal dissolves in water, which is not preferred.

[0254] The method for producing the platinum group metal supported catalyst is not particularly limited. The platinum group metal supported catalyst can be obtained by loading the nanoparticles of the platinum group metal on the integral ion exchanger by a known method. For example, the following methods can be cited: the integral ion exchanger in a dry state is immersed in a methanol solution of a platinum group metal compound such as palladium acetate, and the palladium ions are adsorbed on the integral ion exchanger by ion exchange, and then the palladium metal nanoparticles are loaded on the integral ion exchanger by contact with a reducing agent; the integral ion exchanger is immersed in an aqueous solution of a platinum group metal compound such as a tetraammine palladium complex, and the palladium ions are adsorbed on the integral ion exchanger by ion exchange, and then the palladium metal nanoparticles are loaded on the integral ion exchanger by contact with a reducing agent.

[0255] The introduction of palladium ions into the monolithic ion exchanger and the loading of palladium metal nanoparticles may be carried out in a batch manner or in a flow manner, and there are no particular restrictions.

[0256] The platinum group metal compound used in the method for producing a platinum group metal supported catalyst may be any of organic salts / inorganic salts, and halides, sulfates, nitrates, phosphates, organic acid salts, inorganic complex salts, etc. may be used. Specific examples of the platinum group metal compound include palladium chloride, palladium nitrate, palladium sulfate, palladium acetate, tetraamminepalladium chloride, tetraamminepalladium nitrate, platinum chloride, tetraammineplatinum chloride, tetraammineplatinum nitrate, triammineplatinum chloride, hexaammineplatinum chloride, hexaammineplatinum sulfate, pentaammineplatinum chloride, cis-tetrachlorodiammineplatinum chloride, trans-tetrachlorodiammineplatinum chloride, rhodium chloride, rhodium acetate, hexaamminerhodium chloride, hexaamminerhodium bromide, hexaamminerhodium sulfate, pentaamminehydrorhodium chloride, pentaammine Rhodium nitrate, cis-dichlorotetraamminerhodium chloride, trans-dichlorotetraamminerhodium chloride, ruthenium chloride, hexaammineruthenium chloride, hexaammineruthenium bromide, hexaammineruthenium iodide, pentaammineruthenium chloride, cis-dichlorotetraammineruthenium chloride, trans-dichlorotetraamminerhodium chloride, iridium (III) chloride, iridium (IV) chloride, hexaammineiridium chloride, hexaammineiridium nitrate, pentaammineiridium chloride, pentaammineiridium bromide, hexaammineosmium chloride, hexaammineosmium bromide, hexaammineosmium iodide, etc. The amount of these compounds used is 0.005 to 30% by weight in terms of metal relative to the support, i.e., the entire ion exchanger.

[0257] The platinum group metal compound is usually dissolved in a solvent for use. As the solvent, water; alcohols such as methanol, ethanol, propanol, butanol, benzyl alcohol; ketones such as acetone, methyl ethyl ketone; nitriles such as acetonitrile; amides such as dimethylformamide, dimethylacetamide, N-methylpyrrolidone, or mixtures thereof may be used. In addition, in order to improve the solubility of the platinum group metal compound in the solvent, an acid such as hydrochloric acid, sulfuric acid, nitric acid, or a base such as sodium hydroxide or tetramethylammonium hydroxide may be added.

[0258] The reducing agent used in the method for producing the platinum group metal supported catalyst is also not particularly limited, and examples thereof include reducing gases such as hydrogen, carbon monoxide, and ethylene; alcohols such as methanol, ethanol, propanol, butanol, and benzyl alcohol; carboxylic acids or their salts such as formic acid, ammonium formate, oxalic acid, citric acid, sodium citrate, ascorbic acid, and calcium ascorbate; ketones such as acetone and methyl ethyl ketone; aldehydes such as formaldehyde and acetaldehyde; hydrazines such as hydrazine, methylhydrazine, ethylhydrazine, butylhydrazine, allylhydrazine, and phenylhydrazine; hypophosphites such as sodium hypophosphite and potassium hypophosphite; sodium borohydride, and the like.

[0259] The reaction conditions of the reduction reaction are not particularly limited, and the reaction is usually carried out at -20°C to 150°C for 1 minute to 20 hours to reduce the platinum group metal compound to a zero-valent platinum group metal.

[0260] In addition, the carbon-carbon bond forming method of the present invention is a carbon-carbon bond forming method in which the raw material liquid of the reaction, that is, the raw material liquid (i), the raw material liquid (ii) or the raw material liquid (iii) is passed through the platinum group metal supported catalyst of the present invention, so that the raw material liquid is in contact with the platinum group metal supported catalyst of the present invention, thereby performing a carbon-carbon bond forming reaction. It should be noted that in the carbon-carbon bond forming method of the present invention, in the carbon-carbon bond forming reaction, (1) in the case of the reaction of an aromatic halide with an organic boron compound, the raw material liquid is a raw material liquid (i) containing an aromatic halide and an organic boron compound. In addition, in the carbon-carbon bond forming method of the present invention, in the carbon-carbon bond forming reaction, in the case of (2) the reaction of an aromatic halide with a compound having an alkynyl group at the end, the raw material liquid is a raw material liquid (ii) containing an aromatic halide and a compound having an alkynyl group at the end. In the carbon-carbon bond forming method of the present invention, in the case of the carbon-carbon bond forming reaction (3) the reaction of an aromatic halide and a compound having an alkenyl group, the raw material liquid is a raw material liquid (iii) containing an aromatic halide and a compound having an alkenyl group.

[0261] In the carbon-carbon bond forming method of the present invention, the platinum group metal supported catalyst of the present invention is filled in a filling container. Then, the raw material liquid is introduced into the filling container from the introduction path of the filling container filled with the platinum group metal supported catalyst of the present invention, the raw material liquid is passed to the platinum group metal supported catalyst, and the reaction liquid is discharged from the discharge path of the filling container, so that the reaction raw material liquid passes through the continuous pores of the porous structure of the platinum group metal supported catalyst of the present invention. At this time, the platinum group metal in the continuous pores of the porous structure of the platinum group metal supported catalyst of the present invention contacts the reaction raw material liquid, and a carbon-carbon bond forming reaction based on the platinum group metal occurs. That is, the carbon-carbon bond forming method of the present invention is a fixed bed continuous flow reaction method.

[0262] A flow chart showing an example of a reaction apparatus for carrying out the carbon-carbon bond forming method of the present invention is shown in FIG. Fig. 20 . Fig. 20In the embodiment, the carbon-carbon bond forming reaction device 50 includes: a cylindrical filling container 51 filled with a platinum group metal supported catalyst according to the present invention; a raw material container 53 filled with a raw material liquid 52 for reaction; a raw material liquid supply pump 54 for supplying the raw material liquid 52 to the filling container 51; a reaction liquid receiver 56 for receiving a reaction liquid 55 discharged from the filling container 51; a raw material liquid introduction pipe 57 connecting the raw material container 53 and the filling container 51 to form an introduction path for the raw material liquid; a reaction liquid discharge pipe 59 connecting the filling container 51 and the reaction liquid receiver 56 and having a switching valve 58 in the middle; and a circulation pipe 60 branched from the reaction liquid discharge pipe 59 at the switching valve 58 and connected to the raw material liquid introduction pipe 57. In addition, a heating member or a heating device for heating the inside of the filling container 51 is installed in the filling container 51 as needed.

[0263] In addition, in the carbon-carbon bond forming reaction device 50, the raw material liquid 52 is continuously supplied from the raw material container 53 to the filling container 51 by the raw material liquid supply pump 54. The raw material liquid supplied to the filling container 51 is filled in the platinum group metal supported catalyst of the present invention in the filling container 51, specifically, in the continuous pores of the organic porous body. As a result, the raw material liquid is continuously contacted with the platinum group metal supported catalyst of the present invention, and the raw material in the raw material liquid reacts to form a carbon-carbon bond. Then, the reaction liquid 55 after the carbon-carbon bond formation is sent to the reaction liquid receiver 56 via the reaction liquid discharge pipe 59. Alternatively, the reaction liquid 55 after the carbon-carbon bond formation is returned to the raw material container 53 via the circulation pipe 60 branched from the reaction liquid discharge pipe 59. It should be noted that the switching of the liquid delivery of the reaction liquid 55 to the reaction liquid receiver 56 and the return to the raw material container 53 is performed by the switching valve 58. In addition, by switching the delivery of the reaction liquid 55 to the reaction liquid receiver 56 and the return to the raw material container 53, the layer of the platinum group metal loaded catalyst involved in the present invention can be reacted by passing the liquid only once, or the catalyst layer can be reacted by passing the liquid more than twice.

[0264] In the carbon-carbon bond forming method of the present invention, the size of the filling container, the thickness of the catalyst filling layer, the flow rate of the solvent and the reaction raw materials, the type of solvent, the flow direction of the solution or hydrogen (upward, downward or horizontal), etc., can be appropriately selected according to the type of reaction or the reaction conditions. In the carbon-carbon bond forming method of the present invention, the raw material liquid can be passed through the platinum group metal supported catalyst of the present invention only once, or after the raw material liquid is passed through the platinum group metal supported catalyst of the present invention, the obtained reaction liquid is passed through the platinum group metal supported catalyst of the present invention again. In the case where the raw material liquid is passed through the platinum group metal supported catalyst of the present invention, the reaction liquid can be directly passed through the platinum group metal supported catalyst of the present invention again, or the raw material liquid can be mixed in the reaction liquid, and the mixed liquid is passed through the platinum group metal supported catalyst of the present invention.

[0265] The first method of the carbon-carbon bond forming method of the present invention (hereinafter also referred to as the carbon-carbon bond forming method (1)) is to pass a raw material liquid (i) containing an aromatic halide and an organic boron compound into the above-mentioned platinum group metal supported catalyst of the present invention to allow the aromatic halide to react with the organic boron compound to generate a carbon-carbon single bond.

[0266] The organoboron compound used in the carbon-carbon bond forming method (1) is an organoboron compound represented by the general formula (I) to (III).

[0267] [Chemical formula 1]

[0268]

[0269] [Chemical formula 2]

[0270]

[0271] [Chemical formula 3]

[0272]

[0273] In the formula, R is an organic group. As long as it is an organic group, there is no particular limitation. For example, linear alkyl groups, branched alkyl groups, cyclic alkyl groups, aromatic carbocyclic groups, aromatic heterocyclic groups, etc. can be mentioned. As long as it does not hinder the effect of the present invention, amino groups, methoxy groups, ethoxy groups, carboxyl groups, acetyl groups, nitro groups, cyano groups, etc. can be introduced into these organic groups R.

[0274] Furthermore, as the organic boron compound used in the carbon-carbon bond forming method (1), an aromatic boron compound represented by the following general formulas (IV) to (VI) is preferred.

[0275] [Chemical formula 4]

[0276]

[0277] [Chemical formula 5]

[0278]

[0279] [Chemical formula 6]

[0280]

[0281] (Where Ar 1 They are respectively aromatic carbocyclic groups or aromatic heterocyclic groups having 6 to 18 carbon atoms.

[0282] In formulas (IV) to (VI), Ar 1 Examples of the aromatic carbocyclic group or aromatic heterocyclic group involved include phenyl, naphthyl, biphenyl, anthracenyl, pyridyl, pyrimidyl, indolyl, benzimidazolyl, quinolyl, benzofuranyl, indanyl, indenyl, dibenzofuranyl, etc. The position where boron is bonded to the aromatic carbocyclic group or aromatic heterocyclic group is not particularly limited, and it can be bonded to any position. In addition, one or more substituents can also be introduced into the aromatic carbocyclic group or aromatic heterocyclic group. Examples of substituents include hydrocarbon groups such as methyl, ethyl, propyl, butyl, hexyl, and benzyl; alkoxy groups such as methoxy, ethoxy, propoxy, and butoxy; 9-fluorenylmethoxycarbonyl, butoxycarbonyl, benzyloxycarbonyl, nitro, and cyano.

[0283] The aromatic halide used in the carbon-carbon bond forming method (1) is an aromatic halide represented by the following general formula (VII).

[0284] Ar 2 -X (VII)

[0285] (Where Ar 2 is an aromatic carbocyclic group or aromatic heterocyclic group having 6 to 18 carbon atoms, and X is a halogen atom.

[0286] In formula (VII), Ar 2Examples of the aromatic carbocyclic group or aromatic heterocyclic group involved include phenyl, naphthyl, biphenyl, anthracenyl, pyridyl, pyrimidyl, indolyl, benzimidazolyl, quinolyl, benzofuranyl, indanyl, indenyl, dibenzofuranyl, etc. The position where the halogen atom is bonded to the aromatic carbocyclic group or aromatic heterocyclic group is not particularly limited and can be bonded to any position. In addition, one or more substituents can also be introduced into the aromatic carbocyclic group or aromatic heterocyclic group. As examples of substituents, hydrocarbon groups such as methyl, ethyl, propyl, butyl, hexyl, and benzyl; alkoxy groups such as methoxy, ethoxy, propoxy, and butoxy; 9-fluorenylmethoxycarbonyl, butoxycarbonyl, benzyloxycarbonyl, nitro, cyano, carboxyl, and amino groups that can be substituted by organic groups. It should be noted that X is a halogen atom, specifically a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0287] The formation of a carbon-carbon bond based on the carbon-carbon bond formation method (1) refers to the formation of a carbon-carbon bond between an organic group obtained by removing a boron-containing functional group from an organic boron compound and an aromatic residue obtained by removing a halogen from an aromatic halide. For example, when the organic boron compound is an aromatic boron compound represented by formula (IV) to (VI) and the aromatic halide is an aromatic halide represented by formula (VII), the resulting coupling product is a compound represented by formula (VIII).

[0288] Ar 1 -Ar 2 (VIII)

[0289] (Where Ar 1 and Ar 2 Same as the above formulas (IV) to (VII).

[0290] The aromatic boron compound and the aromatic halide used in the carbon-carbon bond forming method (1) are preferably used in an equimolar ratio. If the molar ratio is in the range of aromatic boron compound:aromatic halide = 0.5 to 2:1, the reaction can be performed without any problem.

[0291] The second method of the carbon-carbon bond forming method of the present invention (hereinafter also referred to as the carbon-carbon bond forming method (2)) is to pass a raw material liquid (ii) containing an aromatic halide and a compound having an alkynyl group at the terminal into the above-mentioned platinum group metal supported catalyst of the present invention to react the aromatic halide with the compound having an alkynyl group at the terminal, thereby generating a carbon-carbon single bond.

[0292] The aromatic halide used in the carbon-carbon bond forming method (2) is an aromatic halide represented by formula (VII).

[0293] The compound having an alkynyl group at the terminal used in the carbon-carbon bond forming method (2) is a compound represented by the formula (IX).

[0294] HC≡CR 1 (IX)

[0295] (Where R 1 A hydrogen atom, an aromatic carbocyclic group or aromatic heterocyclic group having 6 to 18 carbon atoms which may have a substituent, an aliphatic hydrocarbon group having 1 to 18 carbon atoms which may have a substituent, an alkenyl group having 2 to 18 carbon atoms which may have a substituent, an alkynyl group having 2 to 10 carbon atoms which may have a substituent, or a silyl group having 1 to 18 carbon atoms which may have a substituent.

[0296] In formula (IX), R 1 Examples of the aromatic carbocyclic group or aromatic heterocyclic group having 6 to 18 carbon atoms which may have a substituent are as follows: 1 and Ar 2 In addition, in formula (IX), R 1 Examples of the aliphatic hydrocarbon group having 1 to 18 carbon atoms and optionally having a substituent include methyl, ethyl, propyl, butyl, hexyl, octyl, dodecyl, octadecyl, and the like. 1 Examples of the alkenyl group having 2 to 18 carbon atoms and optionally having a substituent include vinyl, allyl, methallyl, propenyl, butenyl, hexenyl, octenyl, decenyl, octadecenyl, and the like. 1 Examples of the alkynyl group having 2 to 10 carbon atoms and optionally having a substituent include ethynyl, propynyl, hexynyl, octynyl, etc. As substituents of these aliphatic hydrocarbon groups, alkenyl groups, and alkynyl groups, hydroxyl groups, hydrocarbon groups, heteroatom-containing hydrocarbon groups, etc. are mentioned. In addition, examples of the silyl group having 1 to 18 carbon atoms and optionally having a substituent include trimethylsilyl, triethylsilyl, triisopropylsilyl, tert-butyldimethylsilyl, tert-butyldiphenylsilyl, etc. are mentioned.

[0297] In the carbon-carbon bond forming method (2), an aromatic halide represented by formula (VII) reacts with a compound represented by formula (IX) via the platinum group metal supported catalyst of the present invention to produce a product represented by formula (X).

[0298] Ar 2 -C≡CR 1 (X)

[0299] (Where Ar 2 and R 1Same as formula (VII)) and (IX).

[0300] The aromatic halide and the terminal alkynyl group-containing compound used in the carbon-carbon bond forming method (2) are preferably used in an equimolar ratio. If the molar ratio of aromatic halide:terminal alkynyl group-containing compound is in the range of 0.5 to 3:1, the reaction can be carried out without any problems.

[0301] The third method of the carbon-carbon bond forming method of the present invention (hereinafter also referred to as the carbon-carbon bond forming method (3)) is: a raw material liquid (iii) containing an aromatic halide and a compound having an alkenyl group is passed through the above-mentioned platinum group metal supported catalyst of the present invention to allow the aromatic halide to react with the compound having an alkenyl group, thereby generating a carbon-carbon single bond.

[0302] The aromatic halide used in the carbon-carbon bond forming method (3) is an aromatic halide represented by the formula (VII).

[0303] The compound having an alkenyl group used in the carbon-carbon bond forming method (3) is a compound represented by the formula (XI).

[0304] R 2 HC=CR 3 R 4 (XI)

[0305] (Where R 2 , R 3 , R 4 Each is independently a hydrogen atom, an aromatic carbocyclic group or aromatic heterocyclic group having 6 to 18 carbon atoms which may have a substituent, an aliphatic hydrocarbon group having 1 to 18 carbon atoms which may have a substituent, a carboxylic acid derivative, an amide derivative or a cyano group.

[0306] In formula (XI), R 2 , R 3 and R 4 Examples of the aromatic carbocyclic group or aromatic heterocyclic group having 6 to 18 carbon atoms which may have a substituent, and the aliphatic hydrocarbon group having 1 to 18 carbon atoms which may have a substituent, and R in formula (IX) 1 In addition, as R in formula (XI) 2 , R 3 and R 4 Examples of carboxylic acid derivatives include alkoxycarbonyl groups such as methoxycarbonyl, ethoxycarbonyl, and butoxycarbonyl. 2 , R 3 and R 4 Examples of the amide derivatives include carbamoyl groups such as N-methylcarbamoyl and N,N-dimethylcarbamoyl.

[0307] In the carbon-carbon bond forming method (3), the aromatic halide represented by the formula (VII) reacts with the compound represented by the formula (XI) via the platinum group metal supported catalyst of the present invention to produce a product represented by the formula (XII).

[0308] R 2 Ar 2 C=CR 3 R 4 (XII)

[0309] (Where Ar 2 , R 2 , R 3 and R 4 Same as formula (VII) and (XI).

[0310] The ratio of the aromatic halide to the terminal alkynyl group compound used in the carbon-carbon bond forming method (3) is not particularly limited, and can be used for the reaction without any problem as long as the molar ratio of aromatic halide:alkenyl group compound is in the range of 0.5 to 2:1.

[0311] In the carbon-carbon bond forming reactions (1) to (3) of the present invention, the amount of the platinum group metal supported catalyst used is 0.01 to 20 mol % in terms of platinum group metal relative to the aromatic halide.

[0312] In the carbon-carbon bond forming reaction of the present invention, it is preferred that a base is present in the raw material solution. Examples of the base used include sodium carbonate, sodium bicarbonate, potassium carbonate, cesium carbonate, potassium acetate, sodium phosphate, potassium phosphate, potassium phenate, barium hydroxide, sodium methoxide, sodium ethoxide, potassium butoxide, trimethylamine, and triethylamine. The amount of these bases used is set to a range of 50 to 300 mol% relative to the aromatic halide.

[0313] In the carbon-carbon bond forming method of the present invention, a solvent can be used to carry out the carbon-carbon bond forming reaction, or the carbon-carbon bond forming reaction can be carried out in the absence of a solvent. As the solvent used, water, an organic solvent, or a mixed solvent of water and an organic solvent can be cited. As the organic solvent, alcohols such as methanol, ethanol, propanol, 2-propanol, butanol, ethylene glycol, propylene glycol, and glycerol can be cited; cyclic ethers such as tetrahydrofuran and dioxane; amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone. Considering the cheapness and easy use of inorganic bases, water is preferred, and a mixed solvent of water and 2-propanol or propylene glycol is particularly preferred.

[0314] In addition, the atmosphere for carrying out the carbon-carbon bond forming method of the present invention may be air, preferably an inert gas atmosphere such as nitrogen or argon. The reaction temperature is not particularly limited and may be set arbitrarily in the range of -20°C to 150°C, preferably 0°C to 120°C, and particularly preferably 20°C to 100°C. In the carbon-carbon bond forming reaction of the present invention, the liquid delivery of the reaction solution is SV = 0.1h -1 ~10000h -1 The process can be carried out at any flow rate within the range of SV=0.5h-1, but from the viewpoint of increasing the yield, SV=0.5h-1 is preferred. -1 ~2000h -1 SV=1h is particularly preferred -1 ~1000h -1 .

[0315] In the carbon-carbon bond forming method of the present invention, the filling container is a container filled with the platinum group metal supported catalyst of the present invention, and it has: an introduction path for the raw material liquid, which is a path for feeding the raw material liquid to one end side of the platinum group metal supported catalyst of the present invention; and a discharge path for the reaction liquid, which is a path for feeding the reaction liquid discharged from the other end side of the platinum group metal supported catalyst of the present invention to the outside of the filling container. In addition, the shape of the filling container is not particularly limited, and for example, the cross-sectional shape when cut on a surface perpendicular to the liquid flow direction can be circular, rectangular, hexagonal, etc. In addition, in the carbon-carbon bond forming method of the present invention, in terms of being able to selectively pass the raw material solution into the continuous pores in the platinum group metal supported catalyst of the present invention, it is preferred that the gap between the filling container and the platinum group metal supported catalyst is as small as possible.

[0316] In the carbon-carbon bond forming method of the present invention, the platinum group metal supported catalyst of the present invention is filled in a filling container, and a raw material solution is passed through the platinum group metal supported catalyst of the present invention, thereby allowing the carbon-carbon bond forming reaction to selectively occur in the continuous pores of the platinum group metal supported catalyst of the present invention, and the contact time between the catalyst and the raw material solution and the contact mode between the catalyst and the raw material solution can be made uniform, thereby increasing the selectivity of the target product.

[0317] On the other hand, when the raw material liquid and the platinum group metal-loaded catalyst of the present invention are mixed and contacted in a reaction container by an intermittent reaction method, the contact time between the catalyst and the raw material liquid becomes longer. In particular, when heating is required during the reaction, the heating time of the raw material liquid also becomes longer, and the side reactions cannot be controlled, so the selectivity of the target product becomes low.

[0318] In the case where the overall ion exchanger involved in the platinum group metal supported catalyst of the present invention is an overall anion exchanger, the ion exchange group introduced is not particularly limited, and is preferably a weak anion group in terms of high reactivity and high yield. As the weak anion group introduced into the overall anion exchanger, for example, tertiary amino, secondary amino, primary amino, tertiary sulfonium, phosphonium, etc. can be cited. As the tertiary amino group introduced into the overall anion exchanger, for example, dimethylamino, diethylamino, dipropylamino, dibutylamino, methylhydroxyethylamino, methylhydroxypropylamino, etc. can be cited. As the secondary amino group introduced into the overall anion exchanger, for example, methylamino, ethylamino, propylamino, butylamino, hydroxyethylamino, hydroxybutylamino, etc. can be cited.

[0319] In the case where the integral ion exchanger involved in the platinum group metal supported catalyst of the present invention is an integral anion exchanger, the type of anion is not particularly limited. Anions of the integral anion exchanger include hydroxide ions, fluoride ions, chloride ions, bromide ions, iodide ions, nitrate ions, nitrite ions, sulfate ions, hydrogen sulfate ions, carbonate ions, and hydrogen carbonate ions. In terms of high catalytic activity, halide ions such as chloride ions, bromide ions, and iodide ions are preferred, and chloride ions and iodide ions are particularly preferred.

[0320] When the integral ion exchanger involved in the platinum group metal supported catalyst of the present invention is an integral cation exchanger, the type of cation is not particularly limited, and examples thereof include hydrogen ions, sodium ions, potassium ions, rubidium ions, magnesium ions, calcium ions, etc. Since hydrogen ions and sodium ions are high in catalytic activity, hydrogen ions are preferred, and hydrogen ions are particularly preferred.

[0321] (Example)

[0322] Next, the present invention will be specifically described with reference to Examples, but these are merely illustrative and do not limit the present invention.

[0323] Example

[0324] (Reference Example 1) Production of Monolithic Cation Exchanger

[0325] (Production of Overall Intermediate (Step I))

[0326] Mix 9.28 g of styrene, 0.19 g of divinylbenzene, 0.50 g of sorbitan monooleate (hereinafter abbreviated as SMO) and 0.25 g of 2,2'-azobis(isobutyronitrile) and dissolve them evenly. Next, add the styrene / divinylbenzene / SMO / 2,2'-azobis(isobutyronitrile) mixture to 180 g of pure water and stir it under reduced pressure using a planetary stirring device, i.e., a vacuum stirring and degassing mixer (manufactured by EME), to obtain an oil-in-water emulsion. The emulsion is quickly transferred to a reaction container, sealed, and allowed to stand for polymerization at 60°C for 24 hours. After the polymerization is completed, take out the contents, extract with methanol, and then dry under reduced pressure to produce an integral intermediate with a continuous macroporous structure. The internal structure of the integral intermediate (dried body) thus obtained is observed by SEM. The SEM image is shown in Fig.10 Although the wall dividing two adjacent macropores is in the shape of very thin rods, it has a continuous bubble structure. The average diameter of the openings (mesopores) of the overlapping parts of the macropores measured by mercury penetration is 40 μm, and the total pore volume is 18.2 ml / g.

[0327] (Overall Manufacturing)

[0328] Next, 216.6 g of styrene, 4.4 g of divinylbenzene, 220 g of 1-decanol, and 0.8 g of 2,2'-azobis(2,4-dimethylvaleronitrile) were mixed and uniformly dissolved (step II). Next, the above-mentioned overall intermediate was placed in a reaction container and immersed in the styrene / divinylbenzene / 1-decanol / 2,2'-azobis(2,4-dimethylvaleronitrile) mixture. After degassing in a reduced pressure chamber, the reaction container was sealed and polymerized at 50°C for 24 hours. After the polymerization was completed, the contents were taken out, Soxhlet extraction was performed with acetone, and then reduced pressure drying was performed (step III).

[0329] The internal structure of the whole (dried body) containing 1.2 mol% of the crosslinking component was observed by SEM. The results are shown in FIG. Fig.11 , the crosslinked styrene / divinylbenzene copolymer thus obtained is included. Fig.11 It can be seen that the whole is a co-continuous structure in which the skeleton and the pores are three-dimensionally continuous and the two phases are interwoven. In addition, the average thickness of the skeleton measured by the SEM image is 20 μm. In addition, the average diameter of the three-dimensional continuous pores of the whole measured by mercury penetration method is 70 μm, and the total pore volume is 4.4 ml / g. It should be noted that the average diameter of the pores is obtained based on the maximum value of the pore distribution curve obtained by mercury penetration method.

[0330] (Manufacturing of Monolithic Cation Exchangers)

[0331] The whole obtained by the above method is placed in a columnar reactor, and a solution containing 500 g of chlorosulfonic acid and 4 L of dichloromethane is passed through the reactor, and the reaction is carried out at 20°C for 3 hours. After the reaction is completed, methanol is added to the system to deactivate the unreacted chlorosulfonic acid, and the product is further washed with methanol to take out the product. Finally, the whole cation exchanger is washed with pure water to obtain a whole cation exchanger.

[0332] The cation exchange capacity of the obtained overall cation exchanger was 4.7 mg equivalent / g in a dry state, and it was confirmed that the sulfonic acid groups were quantitatively introduced. Fig.11 It can be seen that the overall cation exchanger is a co-continuous structure in which the skeleton and the pores are three-dimensionally continuous and intertwined. In addition, the average thickness of the skeleton in a dry state measured by SEM images is 20 μm, and the average diameter of the three-dimensional continuous pores of the overall cation exchanger in a dry state determined by mercury penetration is 70 μm, and the total pore volume in a dry state is 4.4 ml / g.

[0333] Next, in order to confirm the distribution state of the sulfonic acid groups in the whole cation exchanger, the distribution state of sulfur was observed by EPMA. The distribution state of sulfur on the surface of the whole cation exchanger is shown in FIG. Fig.12 , the distribution of sulfur in the skeleton cross section is shown in Fig.13 The sulfur was evenly distributed not only on the surface of the skeleton of the whole cation exchanger but also inside the skeleton. It was confirmed that the sulfonic acid groups were evenly introduced into the whole cation exchanger.

[0334] (Reference Example 2) Preparation of platinum group metal supported catalyst (Pd monolithic cation exchanger)

[0335] The whole cation exchanger of reference example 1 is dried under reduced pressure, and the whole cation exchanger after drying is cut into small pieces of about 3mm by scraper. Make this small piece 1.5g dispersed in 30ml of methanol, further add 160mg of palladium acetate, stir at room temperature for 6 days, make palladium ion load on the whole cation exchanger. Then, carry out solid-liquid separation, take out the whole cation exchanger, be dispersed in 50ml of pure water, add 10 millimoles of hydrazine hydrate and reduce. Under the state that palladium ion loads on the whole cation exchanger, the yellow sample becomes black after reduction, so prompts to generate palladium nanoparticles. After utilizing pure water to wash the sample after reduction for several times, make it dry by drying under reduced pressure.

[0336] The palladium loading was determined by ICP emission spectrometry, and the result showed that the palladium loading was 4.0 wt %. In order to confirm the distribution of palladium loaded on the overall cation exchanger, the distribution of palladium was observed by EPMA. The distribution of palladium in the skeleton cross section of the overall cation exchanger is shown in FIG. Fig.14It can be confirmed that palladium is distributed not only on the surface of the skeleton of the overall cation exchanger, but also inside the skeleton. The concentration inside is slightly higher, but the distribution is relatively uniform. In addition, in order to determine the average particle size of the loaded palladium particles, transmission electron microscopy (TEM) observation was performed. The obtained TEM image is shown in Fig.15 The average particle size of the palladium nanoparticles is 10 nm.

[0337] Hereinafter, the platinum group metal-supported catalyst obtained in Reference Example 2 is described as a “Pd bulk cation exchanger”.

[0338] (Reference Example 3) Preparation of a monolithic anion exchanger (strong anion group)

[0339] (Manufacturing of Monolithic Anion Exchangers)

[0340] The whole prepared in Reference Example 1 was placed in a columnar reactor, and a solution containing 1600 g of chlorosulfonic acid, 400 g of tin tetrachloride, and 2500 ml of dimethoxymethane was circulated and passed through, and the reaction was carried out at 30° C. for 5 hours to introduce chloromethyl groups. After the reaction was completed, the chloromethylation whole was washed with a mixed solvent of THF / water = 2 / 1, and further washed with THF to obtain a chloromethylation whole. THF 1600 ml and 1400 ml of a 30% aqueous solution of trimethylamine were added to the chloromethylation whole, and the reaction was carried out at 60° C. for 6 hours. After the reaction was completed, the product was washed with methanol, and then washed with pure water to obtain a whole anion exchanger.

[0341] The anion exchange capacity of the obtained monolithic anion exchanger was 4.2 mg equivalent / g in a dry state, confirming that the quaternary ammonium groups were quantitatively introduced. In addition, the average thickness of the skeleton in a dry state measured by SEM images was 20 μm, the average diameter of the three-dimensional continuous pores of the monolithic anion exchanger in a dry state determined by mercury intrusion porosimetry was 70 μm, and the total pore volume in a dry state was 4.4 ml / g.

[0342] Next, in order to confirm the distribution state of the quaternary ammonium groups in the integral anion exchanger, the integral anion exchanger was treated with a hydrochloric acid aqueous solution to make it into a chloride type, and then the distribution state of chloride ions was observed by EPMA. The distribution state of chloride ions on the surface of the integral anion exchanger is shown in Fig.16 , the distribution of chloride ions in the skeleton cross section is shown in Fig.17 It can be confirmed that the chloride ions are uniformly distributed not only on the surface of the skeleton of the whole anion exchanger, but also uniformly distributed inside the skeleton, and the quaternary ammonium groups are uniformly introduced into the whole anion exchanger.

[0343] (Reference Example 4) Production of Platinum Group Metal Supported Catalyst (Pd Monolithic Strong Anion Exchanger (Cl Type))

[0344] After the whole anion exchanger of reference example 3 was ion-exchanged into the Cl type, it was cut into a cylindrical shape in a dry state and dried under reduced pressure. The weight of the whole anion exchanger after drying was 1.2g. The whole anion exchanger in the dry state was immersed in dilute hydrochloric acid in which 100mg of palladium chloride was dissolved for 24 hours, and ion exchanged into palladium chloride acid type. After the immersion was completed, the whole anion exchanger was washed with pure water several times and immersed in a hydrazine aqueous solution for 24 hours for reduction treatment. The whole anion exchanger of palladium chloride acid type was brown, while the whole anion exchanger after the reduction treatment was colored black, indicating the generation of palladium nanoparticles. After the sample after reduction was washed with pure water several times, the ion exchange was changed into the Cl type, and it was dried by drying under reduced pressure.

[0345] The palladium loading was determined by ICP emission spectrometry, and the result showed that the palladium loading was 3.9 wt %. In order to confirm the distribution of palladium loaded on the whole anion exchanger, the distribution of palladium was observed by EPMA. The distribution of palladium in the skeleton cross section of the whole anion exchanger is shown in FIG. Fig.18 It can be confirmed that palladium is distributed not only on the surface of the skeleton of the overall anion exchanger, but also inside the skeleton. Although the concentration inside is slightly higher, the distribution is relatively uniform. In addition, in order to measure the average particle size of the loaded palladium particles, transmission electron microscopy (TEM) observation is performed. The obtained TEM image is shown in Fig.19 The average particle size of the palladium nanoparticles is 8 nm.

[0346] Hereinafter, the platinum group metal-supported catalyst obtained in Reference Example 4 is described as “Pd bulk strong anion exchanger (Cl type)”.

[0347] (Reference Example 5) Preparation of Platinum Group Metal Supported Catalyst (Pd Monolithic Strong Anion Exchanger (Type I))

[0348] A platinum group metal-supported catalyst was obtained in the same manner as in Reference Example 4, except that the bulk anion exchanger of Reference Example 3 was ion-exchanged into the I type instead of the Cl type.

[0349] Hereinafter, the platinum group metal-supported catalyst obtained in Reference Example 5 is described as “Pd bulk strong anion exchanger (Type I)”.

[0350] (Reference Example 6) Preparation of a monolithic anion exchanger (weak anion group)

[0351] (Manufacturing of Monolithic Anion Exchangers)

[0352] The chloromethylation whole prepared in Reference Example 3 was dried under reduced pressure. The weight of the chloromethylation whole after drying was 8.4 g. The chloromethylation whole was placed in a separable flask equipped with a stirrer, and a solution containing 56 ml of a 50% aqueous solution of dimethylamine and 180 ml of THF was introduced into the separable flask, and stirred for 10 hours under reflux. After the reaction was completed, the product was washed with methanol, and then washed to obtain a whole anion exchanger.

[0353] The total anion exchange capacity of the obtained monolithic anion exchanger in a dry state was 4.7 mg equivalent / g, and the weak anion exchange capacity was 4.3 mg equivalent / g. The average thickness of the skeleton in a dry state measured from an SEM image was 25 μm.

[0354] (Reference Example 7) Preparation of Platinum Group Metal Supported Catalyst (Pd Bulk Weak Anion Exchanger)

[0355] The whole anion exchanger of reference example 6 is dried under reduced pressure. The weight of the whole anion exchanger after drying is 8.7g. The whole in the dried state is placed in a separable flask equipped with a stirrer, and an ethyl acetate solution of 1.4g of palladium acetate is further introduced, and stirred at room temperature for 5 days to load palladium ions on the whole anion exchanger. The whole anion exchanger is washed with methanol and then washed with pure water. The whole anion exchanger obtained is immersed in 300ml of pure water obtained by adding 60 mmoles of hydrazine hydrate monohydrate, and reduced. Under the state that palladium ions are loaded on the whole cation exchanger, the yellow sample becomes black after reduction, so it is prompted to generate palladium nanoparticles. After the sample after reduction is washed with pure water several times, it is dried by drying under reduced pressure. The loading amount of palladium is obtained by XRD, and the palladium loading amount is 10 weight %.

[0356] Hereinafter, the platinum group metal-supported catalyst obtained in Reference Example 7 is described as “Pd bulk weak anion exchanger”.

[0357] (Example 1)

[0358] [Chemical formula 7]

[0359]

[0360] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. -The resulting solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL x 2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was quantitatively obtained.

[0361] (Example 2)

[0362] [Chemical formula 8]

[0363]

[0364] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 40°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained with a yield of 78%.

[0365] (Example 3)

[0366] [Chemical formula 9]

[0367]

[0368] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at room temperature at a flow rate of 1.0 mL / min. – The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL x 2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained in a yield of 78%.

[0369] (Example 4)

[0370] [Chemical formula 10]

[0371]

[0372] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The resulting solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL x 2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was quantitatively obtained.

[0373] (Example 5)

[0374] [Chemical formula 11]

[0375]

[0376] A 0.12 M aqueous sodium hydroxide solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The resulting solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL x 2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was quantitatively obtained.

[0377] (Example 6)

[0378] [Chemical formula 12]

[0379]

[0380] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained with a yield of 95%.

[0381] (Example 7)

[0382] [Chemical formula 13]

[0383]

[0384] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained with a yield of 77%.

[0385] (Example 8)

[0386] [Chemical formula 14]

[0387]

[0388] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained with a yield of 43%.

[0389] (Example 9)

[0390] [Chemical formula 15]

[0391]

[0392] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I -The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained with a yield of 38%.

[0393] (Example 10)

[0394] [Chemical formula 16]

[0395]

[0396] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (OH) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained with a yield of 95%.

[0397] (Example 11)

[0398] [Chemical formula 17]

[0399]

[0400] A 0.12 M potassium phosphate aqueous solution (150 mL, 18 mmol) was added to a 2-propanol (150 mL) solution of 4-iodoacetophenone (1.48 g, 6.0 mmol) and phenylboronic acid (0.804 g, 6.6 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The mixture was placed in a SUS column (type, φ4.6×30mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (200mL) and extracted with ethyl acetate (120mL×2). The combined organic layer was dried over sodium sulfate and filtered, and the solvent was distilled off from the filtrate under reduced pressure. The obtained crude product was purified by silica gel column chromatography (hexane / ethyl acetate=15:1) to obtain 4-acetylbiphenyl (0.190g, yield 97%) as a white solid.

[0401] (Example 12)

[0402] [Chemical formula 18]

[0403]

[0404] A 0.12M potassium phosphate aqueous solution (150 mL, 18 mmol) was added to a 2-propanol (150 mL) solution of 4-iodoacetophenone (1.48 g, 6.0 mmol) and phenylboronic acid (0.804 g, 6.6 mmol) and stirred. The solution was passed through a SUS column filled with a Pd monolithic strong cation exchanger (H type, φ4.6×30 mm) and heated to 80°C at a flow rate of 1.0 mL / min. The obtained solution was washed with a saturated sodium chloride solution (200 mL) and extracted with ethyl acetate (120 mL×2). The combined organic layers were dried with sodium sulfate and filtered, and the solvent was distilled off from the filtrate under reduced pressure. The obtained crude product was purified by silica gel column chromatography (hexane / ethyl acetate=15:1) to obtain 4-acetylbiphenyl (0.181 g, yield 92%) as a white solid.

[0405] (Example 13)

[0406] [Chemical formula 19]

[0407]

[0408] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 3-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 3-acetylbiphenyl was obtained with a yield of 74%.

[0409] (Example 14)

[0410] [Chemical formula 20]

[0411]

[0412] A 0.30 M potassium phosphate aqueous solution (10 mL, 3.0 mmol) was added to a solution of 3-iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) in propylene glycol (40 mL) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. -The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 110°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with toluene (30 mL×2). The combined organic layer was analyzed by GC, and 3-acetylbiphenyl was obtained in a yield of 58%.

[0413] (Example 15)

[0414] [Chemical formula 21]

[0415]

[0416] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-bromoacetophenone (0.199 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained with a yield of 52%.

[0417] (Example 16)

[0418] [Chemical formula 22]

[0419]

[0420] A 0.30M potassium phosphate aqueous solution (10 mL, 3.0 mmol) was added to a propylene glycol (40 mL) solution of 4-bromoacetophenone (0.199 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a SUS column filled with a Pd monolithic strong anion exchanger (Cl-type, φ4.6×30 mm) and heated to 110°C at a flow rate of 1.0 mL / min. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with toluene (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained with a yield of 95%.

[0421] (Example 17)

[0422] [Chemical formula 23]

[0423]

[0424] 0.12M potassium phosphate aqueous solution (25mL, 3.0mmol) was added to a 2-propanol (25mL) solution of 4-bromoacetophenone (0.199g, 1.0mmol) and phenylboronic acid (0.134g, 1.1mmol) and stirred. The solution was passed through a SUS column filled with a Pd integral weak anion exchanger (NMe2 type, φ4.6×30mm) and heated to 80°C at a flow rate of 1.0mL / min. The obtained solution was washed with a saturated sodium chloride solution (40mL) and extracted with ethyl acetate (30mL×2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained with a yield of 95%.

[0425] (Example 18)

[0426] [Chemical formula 24]

[0427]

[0428] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of iodobenzene (0.204 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL x 2). The combined organic layer was analyzed by GC, and biphenyl was obtained in a yield of 48%.

[0429] (Example 19)

[0430] [Chemical formula 25]

[0431]

[0432] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of iodobenzene (0.204 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL x 2). The combined organic layer was analyzed by GC, and biphenyl was obtained in a yield of 93%.

[0433] (Example 20)

[0434] [Chemical formula 26]

[0435]

[0436] A 0.30 M potassium phosphate aqueous solution (10 mL, 3.0 mmol) was added to a solution of iodobenzene (0.204 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) in propylene glycol (40 mL) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL x 2). The combined organic layer was analyzed by GC, and biphenyl was obtained at a yield of 45%.

[0437] (Example 21)

[0438] [Chemical formula 27]

[0439]

[0440] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of bromobenzene (0.157 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL x 2). The combined organic layer was analyzed by GC, and biphenyl was obtained in a yield of 35%.

[0441] (Example 22)

[0442] [Chemical formula 28]

[0443]

[0444] A 0.30 M potassium phosphate aqueous solution (10 mL, 3.0 mmol) was added to a solution of bromobenzene (0.157 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) in propylene glycol (40 mL) and stirred. The solution was passed through a solid anion exchanger (Cl) filled with Pd at a flow rate of 1.0 mL / min. -The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL x 2). The combined organic layer was analyzed by GC, and biphenyl was obtained at a yield of 26%.

[0445] (Example 23)

[0446] [Chemical formula 29]

[0447]

[0448] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodotoluene (0.218 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-methylbiphenyl was obtained at a yield of 48%.

[0449] (Example 24)

[0450] [Chemical formula 30]

[0451]

[0452] A 0.30 M potassium phosphate aqueous solution (10 mL, 3.0 mmol) was added to a solution of 4-iodotoluene (0.218 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) in propylene glycol (40 mL) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 110°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-methylbiphenyl was obtained with a yield of 70%.

[0453] (Example 25)

[0454] [Chemical formula 31]

[0455]

[0456] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (50 mL) solution of 4-iodinitrobenzene (0.249 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (60 mL) and extracted with ethyl acetate (40 mL×2). The combined organic layer was analyzed by GC, and 4-nitrobiphenyl was obtained with a yield of 92%.

[0457] (Example 26)

[0458] [Chemical formula 32]

[0459]

[0460] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodobenzonitrile (0.229 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-cyanobiphenyl was obtained with a yield of 96%.

[0461] (Example 27)

[0462] [Chemical formula 33]

[0463]

[0464] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-bromotrifluorotoluene (0.225 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-(trifluoroacetyl)biphenyl was obtained with a yield of 49%.

[0465] (Example 28)

[0466] [Chemical formula 34]

[0467]

[0468] A 0.30 M potassium phosphate aqueous solution (10 mL, 3.0 mmol) was added to a solution of 4-bromotrifluorotoluene (0.225 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) in propylene glycol (40 mL) and stirred. The solution was passed through a solid anion exchanger (Cl) filled with Pd at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 110°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-(trifluoroacetyl)biphenyl was obtained with a yield of 21%.

[0469] (Example 29)

[0470] [Chemical formula 35]

[0471]

[0472] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and 4-methylphenylboronic acid (0.150 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetyl-4'-methylbiphenyl was obtained with a yield of 93%.

[0473] (Example 30)

[0474] [Chemical formula 36]

[0475]

[0476] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and 3-methylphenylboronic acid (0.150 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetyl-3'-methylbiphenyl was obtained with a yield of 94%.

[0477] (Example 31)

[0478] [Chemical formula 37]

[0479]

[0480] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and 2-methylphenylboronic acid (0.150 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetyl-2'-methylbiphenyl was obtained with a yield of 97%.

[0481] (Example 32)

[0482] [Chemical formula 38]

[0483]

[0484] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and 4-methoxyphenylboronic acid (0.167 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. -The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4'-acetyl-4-methoxybiphenyl was obtained with a yield of 95%.

[0485] (Example 33)

[0486] [Chemical formula 39]

[0487]

[0488] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and 4-chlorophenylboronic acid (0.172 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4'-acetyl-4-chlorobiphenyl was obtained with a yield of 95%.

[0489] (Example 34)

[0490] [Chemical formula 40]

[0491]

[0492] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and 4-acetylphenylboronic acid (0.180 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4,4'-diacetylbiphenyl was obtained with a yield of 79%.

[0493] (Example 35)

[0494] [Chemical formula 41]

[0495]

[0496] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and 4-(trifluoromethyl)phenylboronic acid (0.209 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4'-acetyl-4-(trifluoromethyl)biphenyl was obtained with a yield of 89%.

[0497] (Example 36)

[0498] [Chemical formula 42]

[0499]

[0500] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and 2-phenyl-4,4,5,5-tetramethyl-1,3,2-dioxaborolane (0.224 g, 1.1 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 80°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained with a yield of 86%.

[0501] (Example 37)

[0502] [Chemical formula 43]

[0503]

[0504] 0.12M potassium phosphate aqueous solution (25mL, 3.0mmol) was added to a 2-propanol (25mL) solution of 4-iodoacetophenone (0.246g, 1.0mmol) and potassium phenyltrifluoroborate (0.202g, 1.1mmol) and stirred. The solution was passed through a SUS column filled with a Pd integral strong anion exchanger (type I, φ4.6×30mm) and heated to 80°C at a flow rate of 1.0mL / min. The obtained solution was washed with a saturated sodium chloride solution (40mL) and extracted with ethyl acetate (30mL×2). The combined organic layer was analyzed by GC, and 4-acetylbiphenyl was obtained with a yield of 75%.

[0505] (Example 38)

[0506] [Chemical formula 44]

[0507]

[0508] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of iodobenzene (0.204 g, 1.0 mmol) and ethynylbenzene (0.123 g, 1.2 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL x 2). The combined organic layer was analyzed by GC, and biphenylacetylene was obtained at a yield of 25%.

[0509] (Example 39)

[0510] [Chemical formula 45]

[0511]

[0512] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and ethynylbenzene (0.123 g, 1.2 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 85°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-(phenylethynyl)acetophenone was obtained with a yield of 61%.

[0513] (Example 40)

[0514] [Chemical formula 46]

[0515]

[0516] 0.12M potassium phosphate aqueous solution (25mL, 3.0mmol) was added to a 2-propanol (25mL) solution of 4-iodoacetophenone (0.246g, 1.0mmol) and ethynylbenzene (0.123g, 1.2mmol) and stirred. The solution was passed through a SUS column filled with a Pd integral weak anion exchanger (NMe2 type, φ4.6×30mm) and heated to 85°C at a flow rate of 1.0mL / min. The obtained solution was washed with a saturated sodium chloride solution (40mL) and extracted with ethyl acetate (30mL×2). The combined organic layer was analyzed by GC, and 4-(phenylethynyl)acetophenone was obtained with a yield of 97%.

[0517] (Example 41)

[0518] [Chemical formula 47]

[0519]

[0520] 0.12M potassium phosphate aqueous solution (25mL, 3.0mmol) was added to a solution of 3-iodoacetophenone (0.246g, 1.0mmol) and ethynylbenzene (0.123g, 1.2mmol) in 2-propanol (25mL) and stirred. The solution was passed through a SUS column filled with a Pd monolithic strong anion exchanger (Cl type, φ4.6×30mm) and heated to 85°C at a flow rate of 1.0mL / min. The obtained solution was washed with a saturated sodium chloride solution (40mL) and extracted with ethyl acetate (30mL×2). The combined organic layer was analyzed by GC, and 3-(phenylethynyl)acetophenone was obtained with a yield of 50%.

[0521] (Example 42)

[0522] [Chemical formula 48]

[0523]

[0524] 0.12M potassium phosphate aqueous solution (25mL, 3.0mmol) was added to a 2-propanol (25mL) solution of 4-iodobenzonitrile (0.229g, 1.0mmol) and ethynylbenzene (0.123g, 1.2mmol) and stirred. The solution was passed through a SUS column filled with a Pd integral strong anion exchanger (Cl type, φ4.6×30mm) and heated to 85°C at a flow rate of 1.0mL / min. The obtained solution was washed with a saturated sodium chloride solution (40mL) and extracted with ethyl acetate (30mL×2). The combined organic layer was analyzed by GC, and 4-(phenylethynyl)benzonitrile was obtained with a yield of 90%.

[0525] (Example 43)

[0526] [Chemical formula 49]

[0527]

[0528] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodotoluene (0.218 g, 1.0 mmol) and ethynylbenzene (0.123 g, 1.2 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 85°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-(phenylethynyl)toluene was obtained with a yield of 38%.

[0529] (Example 44)

[0530] [Chemical formula 50]

[0531]

[0532] A 0.12 M potassium phosphate aqueous solution (25 mL, 3.0 mmol) was added to a 2-propanol (25 mL) solution of 4-iodoacetophenone (0.246 g, 1.0 mmol) and triisopropylsilyl acetylene (0.219 g, 1.2 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (I - The mixture was placed in a SUS column (type, φ4.6×30 mm) and heated to 85°C. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 4-(triisopropylsilylethynyl)acetophenone was obtained with a yield of 29%.

[0533] (Example 45)

[0534] [Chemical formula 51]

[0535]

[0536] A 0.12 M potassium phosphate aqueous solution (50 mL, 3.0 mmol) was added to a 2-propanol (50 mL) solution of ethyl 4-iodobenzoate (0.552 g, 2.0 mmol) and phenylboronic acid (0.268 g, 2.2 mmol) and stirred. The solution was passed through a Pd monolithic strong anion exchanger (Cl) at a flow rate of 1.0 mL / min. - The solution was washed with 1N hydrochloric acid (80 mL) and extracted with ethyl acetate (60 mL x 2). 1 The combined organic layers were analyzed by H-NMR, and as a result, ethyl 4-phenylbenzoate was obtained in a yield of 51%. It should be noted that 4-phenylbenzoic acid, which is a hydrolyzate, was not obtained.

[0537] (Comparative Example 1)

[0538] [Chemical formula 52]

[0539]

[0540] To a 2-propanol (50 mL) solution of ethyl 4-iodobenzoate (0.552 g, 2.0 mmol) and phenylboronic acid (0.268 g, 2.2 mmol), add 0.12 M potassium phosphate aqueous solution (50 mL, 3.0 mmol) and stir. Mix the Pd monolithic strong anion exchanger (Cl type, φ4.6×3.0 mm×10) in the solution and stir at 80°C for 1 hour and 40 minutes. After cooling the reaction solution to room temperature, wash it with 1N hydrochloric acid (80 mL) and extract it with ethyl acetate (60 mL×2). 1 The combined organic layers were analyzed by H-NMR, whereby ethyl 4-phenylbenzoate (yield 68%) and its hydrolyzate, 4-phenylbenzoic acid (yield 10%) were obtained.

[0541] That is, in Comparative Example 1, the reaction was performed in a batch system instead of a fixed bed continuous flow system.

[0542] In Example 45, the target product (ethyl 4-phenylbenzoate) was obtained selectively. In contrast, in Comparative Example 1, in addition to the target product (ethyl 4-phenylbenzoate), a by-product (4-phenylbenzoic acid) was also generated. Therefore, it can be seen that the selectivity of the target product can be improved by conducting the reaction in a fixed bed continuous flow manner.

[0543] (Example 46)

[0544] [Chemical formula 53]

[0545]

[0546] 3-Iodoacetophenone (0.246 g, 1.0 mmol) and phenylboronic acid (0.134 g, 1.1 mmol) were added to a 0.06 M potassium phosphate aqueous solution (50 mL, 3.0 mmol) and stirred. The suspension was passed through a solid anion exchanger (Cl) filled with Pd at a flow rate of 1.0 mL / min. - The resulting solution was extracted with ethyl acetate (30 mL x 2). The combined organic layers were analyzed by GC, and 3-acetylbiphenyl was obtained at a yield of 23%.

[0547] (Example 47)

[0548] [Chemical formula 54]

[0549]

[0550] Tripropylamine (0.158 g, 1.1 mmol) was added to a solution of 4-iodinitrobenzene (0.249 g, 1.0 mmol) and butyl acrylate (0.154 g, 1.2 mmol) in N,N-dimethylacetamide (50 mL) and stirred. The solution was passed through a SUS column filled with a Pd integral weak anion exchanger (NMe2 type, φ4.6×30 mm) and heated to 100°C at a flow rate of 1.0 mL / min. The obtained solution was washed with a saturated sodium chloride solution (40 mL) and extracted with ethyl acetate (30 mL×2). The combined organic layer was analyzed by GC, and 3-(4-nitrophenyl)butyl acrylate was obtained with a yield of 24%.

[0551] Explanation of symbols

[0552] 1 Skeleton phase

[0553] 2 Hole phase

[0554] 10 Overall

[0555] 11 Image area

[0556] 12 Cross-section representation of the skeleton

[0557] 13 Big Hole

[0558] 21 Skeleton surface

[0559] 22 protrusions

[0560] 30 Whole (whole ion exchanger)

[0561] 31 Big Hole

[0562] 32 Opening

[0563] 33 Inner layer

[0564] 34 Surface

[0565] 35 Gas phase (bubble phase)

[0566] 36 Wall (frame)

[0567] 37 Pores

[0568] 50 Carbon-carbon bond formation reaction apparatus

[0569] 51 Filling container

[0570] 52 Raw material liquid

[0571] 53 Raw material container

[0572] 54 Raw material liquid supply pump

[0573] 55 Reaction solution

[0574] 56 Reaction liquid receiver

[0575] 57 Raw material liquid introduction tube

[0576] 58 Switching valve

[0577] 59 Reaction liquid discharge pipe

[0578] 60 Circulation tube.

Claims

1. A method for forming a carbon-carbon bond, characterized in that: (1) a reaction of an aromatic halide with an organic boron compound, (2) a reaction of an aromatic halide with a compound having an alkynyl group at the terminal, or (3) a reaction of an aromatic halide with a compound having an alkenyl group to form a carbon-carbon bond, wherein: A raw material solution (i) containing an aromatic halide and an organic boron compound, a raw material solution (ii) containing an aromatic halide and a compound having an alkynyl group at a terminal, or a raw material solution (iii) containing an aromatic halide and a compound having an alkenyl group is introduced into the filled container from an introduction path of the filled container filled with a platinum group metal supported catalyst, the raw material solution is passed through the platinum group metal supported catalyst, and the reaction solution is discharged from the discharge path of the filled container, thereby performing a carbon-carbon bond forming reaction. The platinum group metal supported catalyst is a platinum group metal supported catalyst in which nanoparticles of platinum group metal with an average particle size of 1 to 100 nm are supported in a non-granular organic porous weak anion exchanger. The weak anion exchange group of the non-granular organic porous weak anion exchanger is a tertiary amino group or a secondary amino group. The non-granular organic porous weak anion exchanger comprises a continuous skeleton phase and a continuous pore phase. The thickness of the continuous skeleton is 1 to 100 nm. μ m, the average diameter of continuous pores is 1 to 1000 μ m, the total pore volume of the non-granular organic porous weak anion exchanger is 0.5-50 ml / g, the weak anion exchange capacity per unit weight in a dry state is 1-9 mg equivalent / g, the weak anion exchange groups are uniformly distributed in the organic porous weak anion exchanger, and the loading amount of the platinum group metal in a dry state is 0.004-20 weight %.

2. The method for forming a carbon-carbon bond according to claim 1, characterized in that: The non-granular organic porous weak anion exchanger has: macropores connected to each other and macropore walls having an average diameter of 1 to 1000 μ The invention discloses a continuous bubble structure with a common opening of m, a total pore volume of 1 to 50 ml / g, a weak anion exchange capacity per unit weight in a dry state of 1 to 9 mg equivalent / g, and weak anion exchange groups are uniformly distributed in the organic porous weak anion exchanger.

3. The method for forming a carbon-carbon bond according to claim 1, characterized in that: The non-granular organic porous weak anion exchanger has an average particle size of 1 to 50 μ The organic polymer particles of m are aggregated to form a three-dimensional continuous skeleton part, and there are 20~100 μ The organic porous weak anion exchange body has three-dimensional continuous pores of 1-10 ml / g and a total pore volume of 1-10 ml / g. The weak anion exchange capacity per unit weight in a dry state is 1-9 mg equivalent / g. The weak anion exchange groups are uniformly distributed in the organic porous weak anion exchange body.

4. The carbon-carbon bond forming method according to claim 1, characterized in that: The non-granular organic porous weak anion exchanger is composed of bubble-shaped macropores overlapping each other, and the overlapping part forms an average diameter of 30 to 300 μ The invention discloses a continuous macroporous structure having an opening of m, a total pore volume of 0.5 to 10 ml / g, a weak anion exchange capacity per unit weight in a dry state of 1 to 9 mg equivalent / g, weak anion exchange groups are uniformly distributed in the organic porous weak anion exchanger, and in the SEM image of the cross section of the continuous macroporous structure in a dry state, the area of ​​the skeleton portion shown in the cross section is 25 to 50% in the image area.

5. The method for forming a carbon-carbon bond according to claim 1, characterized in that: The non-granular organic porous weak anion exchanger is a co-continuous structure comprising a skeleton and pores; the skeleton is an aromatic vinyl polymer having an average thickness of 1 to 60 μ m three-dimensional continuous skeleton, wherein the aromatic vinyl polymer contains 0.1 to 5.0 mol % of cross-linked structural units in all structural units introduced with weak anion exchange groups; the pores are 10 to 200 m in average diameter between the skeletons. μ m three-dimensional continuous pores, The total pore volume of the non-granular organic porous weak anion exchanger is 0.5-10 ml / g, the weak anion exchange capacity per unit weight in a dry state is 1-9 mg equivalent / g, and the weak anion exchange groups are uniformly distributed in the organic porous weak anion exchanger.

6. The method for forming a carbon-carbon bond according to claim 1, characterized in that: The non-granular organic porous weak anion exchanger comprises a continuous skeleton phase and a continuous pore phase, wherein the skeleton has a diameter of 4 to 40 mm fixed to the surface. μ A plurality of particles of 4 to 40 m in size formed on the surface of the skeleton of the organic porous body μ Multiple protrusions of m, the average diameter of the continuous pores is 10 to 200 μ m, The total pore volume of the non-granular organic porous weak anion exchanger is 0.5-10 ml / g, the weak anion exchange capacity per unit weight in a dry state is 1-9 mg equivalent / g, and the weak anion exchange groups are uniformly distributed in the organic porous weak anion exchanger.

Citation Information

Patent Citations

  • Plate for construction

    JP1977055215A

  • Semiconductor device

    JP1981038862A

  • Columns with macroporous polymeric media

    JP1995501140A

  • Porous ion exchanger and production of deionized water

    JP1996252579A

  • Porous ion exchanger, deionizing module using the same, and electrical device for producing deionized water

    JP2002306976A